Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Cervico-vaginal secretion cytokine profile: A non-invasive approach to study the endometrial receptivity in IVF cycles. - Zanotta, Nunzia; Monasta, Lorenzo; Skerk, Kristina; Luppi, Stefania; Martinelli, Monica; Ricci, Giuseppe; Comar, Manola (Am J Reprod Immunol, 2019)
PROBLEM: Cytokines have a significant role in the process of embryo implantation, trophoblast growth, and differentiation by modulating the immune and endocrine system. The aim of this study was to investigate the profile of a large set of cytokines in the cervico-vaginal washing of women undergoing IVF, to explore the association of these proteins with a good receptive endometrium. METHOD OF STUDY: A cohort of 155 women scheduled for IVF cycle was recruited. All patients were asymptomatic for genitourinary infections and had been screened for chlamydia, mycoplasma, and other bacterial infections. All IVF subjects were treated according to standard clinical and laboratory protocols. A panel of 48 immune factors was analyzed on cervico-vaginal washing, using magnetic bead-based multiplex immunoassays (Bio-Plex, BIO-RAD Laboratories, Milano, Italy). RESULTS: A total of 99 patients reached embryo transfer, of which 31 had a clinical pregnancy. A pattern of four pro-inflammatory immune molecules, IL-12p40, IFN-a, MIF, and MCP3 (P < 0.001), was found significantly up-regulated in the cervico-vaginal fluid of women with clinical pregnancy. A significantly increased expression of IL-9, Gro , and SDF-1 (P < 0.05) was observed in the presence of endometriosis, while high levels of IL-13 and L-15 were associated with ovulatory infertility factor (P < 0.05). CONCLUSION: In this pilot study, we demonstrated that the expression of specific cytokines in the cervico-vaginal washing on the day of oocyte retrieval might have a positive correlation with the potential clinical pregnancy. Therefore, cervico-vaginal secretion cytokine profiling might be a new, non-invasive approach to study the endometrial receptivity in IVF management.

An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M; Carrozzi, Marco; Skabar, Aldo; Sugden, David A; Barnett, Anna L; Henderson, Sheila E (Res Dev Disabil, 2019)
BACKGROUND: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. AIM: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. METHOD: A total of 718 Italian (IT) and 765 British (UK) children, aged 3-10 years, were individually tested on the age-appropriate items of the MABC-2 Test. RESULTS: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. CONCLUSION: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.

First urinary tract infections in children: the role of the risk factors proposed by the Italian recommendations. - Alberici, I; La Manna, A; Pennesi, M; Starc, M; Scozzola, F; Nicolini, G; Toffolo, A; Marra, G; Chimenz, R; Sica, F; Maringhini, S; Monasta, L; et al. (Acta Paediatr, 2019)
AIM: In 2009, the Italian society for paediatric nephrology suggested the need for cystography, following a first febrile urinary tract infection (UTI), only in children at high risk for dilating vesicoureteral reflux or in the event of a second infection. The aim of this study was to evaluate the adequacy of the risk factors proposed by the Italian guidelines. METHODS: Children aged 2-36 months, managed by 10 Italian hospitals between 2009 and 2013, with a first febrile UTI were retrospectively evaluated. RESULTS: Four hundred and fourteen children were included: 51% female, mean age eight months. Escherichia coli was responsible of 84% UTIs. 269 children (65%) presented at least one risk factor, thus were further investigated: 44% had a reflux. The presence of a pathogen other than E. coli significantly predicted high-grade reflux, both in the univariate (Odd Ratio 2.52, 95% Confidence Interval 1.32-4.81, p < 0.005) and multivariate analysis (OR 2.74, 95% CI: 1.39-5.41, p: 0.003). 26/145 children (18%) with no risk factors experienced a second UTI, which prompted the execution of cystography, showing a dilating reflux in 11. CONCLUSION: Among the risk factors proposed by the Italian guidelines, only the presence of a pathogen other than E. coli significantly predicted reflux. Cystography can be postponed in children with no risk factors.

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

Anaphylaxis in atypical cold urticaria: case report and review of literature. - Benelli, Elisa; Longo, Giorgio; Barbi, Egidio; Berti, Irene (Ital J Pediatr, 2018)
BACKGROUND: Cold-induced urticaria is a kind of physical urticaria characterized by the appearance of wheals after exposure to cold. The atypical form is a rare sub-type characterized by appearance of hives even in areas not directly exposed to the cold and by a negative cold stimulation test. Its diagnosis is often challenging because of the lack of specific tests and it is usually based on the patient's clinical history. Hypotension due to generalized exposure to the cold is described both in the typical and the atypical forms. CASE PRESENTATION: We describe a 9-year-old boy who, at the beginning of the summer after the first swim in the sea, developed generalized urticaria, dyspnea, conjunctival hyperemia, blurred vision and loss of strength. The child was treated with intramuscular steroid and intravenous antihistamine, and the symptoms quickly resolved. Insect bite, contact with fish and drug ingestion were denied, and no unusual food had been eaten before the swim. A tentative diagnosis was made of either aquagenic urticaria or cold urticaria, but the specific tests were negative. Although the cause was unknown, prophylactic treatment with antihistamines was prescribed but in spite of this, wheals developed all over the body, after every swim in the sea. The child then came to our attention and relying on clinical history a diagnosis of atypical cold urticaria was made: development of hives even in areas not directly exposed to cold and a negative response to the cold stimulation test, are the characteristic features of this rare form of cold urticaria. CONCLUSION: Atypical cold urticaria should be suspected in all cases of anaphylaxis related to cold exposure (i.e. contact with water) with a negative cold stimulation test.
Keywords: Anaphylaxis; Child; Cold Temperature; Humans; Male; Swimming; Urticaria

Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1

Cervical-length measurement in mid-gestation to predict spontaneous preterm birth in asymptomatic triplet pregnancy. - Fichera, A; Pagani, G; Stagnati, V; Cascella, S; Faiola, S; Gaini, C; Lanna, M; Pasquini, L; Raffaelli, R; Stampalija, T; Tommasini, A; Prefumo, F (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: To assess the predictive value of sonographic cervical-length (CL) measurement in mid-gestation for spontaneous preterm birth (PTB) in asymptomatic triplet pregnancy. METHODS: This was a retrospective study of asymptomatic triplet pregnancies followed at five Italian tertiary referral centers, between 2002 and 2015. CL was measured transvaginally between 18 and 24 weeks' gestation. Pregnancies with medically indicated PTB were excluded. Demographic and pregnancy characteristics of pregnancies complicated by PTB were analyzed and the distributions of CL measurements in these patients were calculated. Logistic regression analysis was performed to assess the association between CL and PTB, adjusted for confounders. Performance of CL measurement in prediction of PTB < 28, < 30 and < 32 weeks of gestation was assessed. RESULTS: A total of 120 triplet pregnancies were included in the final analysis. Median CL was 35 (interquartile range (IQR), 29-40) mm measured at a median gestational age of 20 + 2 (IQR, 20 + 0 to 23 + 4) weeks. Overall, 23 (19.2%), 17 (14.2%) and eight (6.7%) patients had a CL < 25, < 20 and < 15 mm, respectively. Spontaneous PTB < 32 weeks occurred in 41 (34.2%) cases, < 30 weeks in 23 (19.2%) and < 28 weeks in 12 (10%) cases. CL < 15 mm was significantly more frequent in the group of patients who delivered < 28 (P = 0.03) and < 30 (P = 0.01) weeks' gestation, compared with those who delivered after 28 and after 30 weeks, respectively, while CL < 20 mm was more common in triplet pregnancies with delivery < 32 weeks compared with those delivered ≥ 32 weeks (P = 0.03). Logistic regression analysis was possible only for PTB < 32 weeks due to the small number of cases that delivered < 30 and < 28 weeks. After adjustment for confounders, CL was not significantly associated with PTB < 32 weeks (adjusted odds ratio, 0.97; 95% CI, 0.94-1.01). CL measurement had an area under the receiver-operating characteristics curve of 0.41 (95% CI, 0.20-0.62), 0.41 (95% CI, 0.26-0.56) and 0.42 (95% CI, 0.31-0.54) for the prediction of spontaneous PTB < 28, < 30 and < 32 weeks, respectively. CONCLUSION: CL assessed in mid-gestation is a poor predictor of PTB < 28, < 30 and < 32 weeks' gestation in asymptomatic triplet pregnancy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cervical Length Measurement; Female; Gestational Age; Humans; Infant, Newborn; Logistic Models; Predictive Value of Tests; Pregnancy; Pregnancy, Triplet; Premature Birth; Retrospective Studies

Characterization of multi-locus imprinting disturbances and underlying genetic defects in patients with chromosome 11p15.5 related imprinting disorders. - Fontana, L; Bedeschi, M F; Maitz, S; Cereda, A; Faré, C; Motta, S; Seresini, A; D'Ursi, P; Orro, A; Pecile, V; Calvello, M; Selicorni, A; et al. (Epigenetics, 2018)
The identification of multilocus imprinting disturbances (MLID) appears fundamental to uncover molecular pathways underlying imprinting disorders (IDs) and to complete clinical diagnosis of patients. However, MLID genetic associated mechanisms remain largely unknown. To characterize MLID in Beckwith-Wiedemann (BWS) and Silver-Russell (SRS) syndromes, we profiled by MassARRAY the methylation of 12 imprinted differentially methylated regions (iDMRs) in 21 BWS and 7 SRS patients with chromosome 11p15.5 epimutations. MLID was identified in 50% of BWS and 29% of SRS patients as a maternal hypomethylation syndrome. By next-generation sequencing, we searched for putative MLID-causative mutations in genes involved in methylation establishment/maintenance and found two novel missense mutations possibly causative of MLID: one in NLRP2, affecting ADP binding and protein activity, and one in ZFP42, likely leading to loss of DNA binding specificity. Both variants were paternally inherited. In silico protein modelling allowed to define the functional effect of these mutations. We found that MLID is very frequent in BWS/SRS. In addition, since MLID-BWS patients in our cohort show a peculiar pattern of BWS-associated clinical signs, MLID test could be important for a comprehensive clinical assessment. Finally, we highlighted the possible involvement of ZFP42 variants in MLID development and confirmed NLRP2 as causative locus in BWS-MLID.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Beckwith-Wiedemann Syndrome; Child; Child, Preschool; Chromosomes, Human, Pair 15; DNA Methylation; Female; Genomic Imprinting; Humans; Infant; Kruppel-Like Transcription Factors; Male; Mutation, Missense; Silver-Russell Syndrome; Young Adult

Complete Remission of a Refractory Acute Myeloid Leukemia with Myelodysplastic- and Monosomy 7-Related Changes after a Combined Conditioning Regimen of Plerixafor, Cytarabine and Melphalan in a 4-Year-Old Boy: A Case Report and Review of Literature. - Grasso, Antonio G; Granzotto, Marilena; Zanon, Davide; Maestro, Alessandra; Loiacono, Stefano; Maximova, Natalia (Cancers (Basel), 2018)
Acute myeloid leukemia with myelodysplastic changes and monosomy 7 is a rare form of pediatric leukemia associated with very poor disease-free survival. The refractoriness of the disease is due to the protection offered by the bone marrow niche, making leukemic stem cells impervious to whatever chemotherapy or myeloablative regimen is chosen. Using a mobilizing agent for haematopoietic stem cells, Plerixafor, could sensitise leukemic cells to the myeloablative therapy. This approach was not previously used in a pediatric population, and in adult populations, was used in combination with busulphan with no difference in overall survival. We describe the case of a 4-year-old boy affected by refractory acute myeloid leukemia with myelodysplastic changes and monosomy 7. The child had never achieved a remission. We proposed a combined time-scheduled scheme of therapy with plerixafor and melphalan. Combining pharmacokinetics of plerixafor with pharmacokinetics and rapid and elevated myeloablative potential of melphalan in high dosage (200 mg/m²), we succeeded in mobilizing more than 85% of stem blasts immediately before infusion of Melphalan. The count of residual blasts after 8 h from melphalan infusion was only 1.3 cells/μL. The child achieved an engraftment at day +32 with full donor chimerism. Sixteen months after haematopoietic stem cell transplantation (HSCT), he is well and in complete remission. Our case suggests that the use of plerixafor before a conditioning therapy with melphalan could induce remission in acute myeloid leukemia refractory to the usual conditioning therapy in pediatric patients. This work adds strength to the body of knowledge regarding the "personalized" conditioning regimen for high-risk leukemic patients.

Cooking influence in tolerance acquisition in egg-induced acute food protein enterocolitis syndrome. - Miceli Sopo, S; Romano, A; Bersani, G; Fantacci, C; Badina, L; Longo, G; Monti, G; Viola, S; Tripodi, S; Barilaro, G; Iacono, I D; Caffarelli, C; et al. (Allergol Immunopathol (Madr), 2018)
BACKGROUND: Few studies on the age of resolution of Food Protein Induced Enterocolitis Syndrome (FPIES) induced by solid foods are available. In particular, for FPIES induced by egg, the mean age of tolerance acquisition reported in the literature ranges from 42 to 63 months. OBJECTIVE: We have assessed whether the age of tolerance acquisition in acute egg FPIES varies depending on whether the egg is cooked or raw. METHODS: We conducted a retrospective and multicentric study of children with diagnosis of acute egg FPIES seen in 10 Italian allergy units between July 2003 and October 2017. The collected data regarded sex, presence of other allergic diseases, age of onset of symptoms, kind and severity of symptoms, cooking technique of the ingested egg, outcome of the allergy test, age of tolerance acquisition. RESULTS: Sixty-one children with acute egg FPIES were enrolled, 34 (56%) males and 27 (44%) females. Tolerance to cooked egg has been demonstrated by 47/61 (77%) children at a mean age of 30.2 months. For 32 of them, tolerance to raw egg has been demonstrated at a mean age of 43.9 months. No episodes of severe adverse reaction after baked egg ingestion have been recorded. CONCLUSIONS: It is possible to perform an OFC with baked egg, to verify the possible acquisition of tolerance, at about 30 months of life in children with acute egg FPIES.

Effectiveness of the facility-based maternal near-miss case reviews in improving maternal and newborn quality of care in low-income and middle-income countries: a systematic review. - Lazzerini, Marzia; Richardson, Sonia; Ciardelli, Valentina; Erenbourg, Anna (BMJ Open, 2018)
OBJECTIVES: The maternal near-miss case review (NMCR) has been promoted by WHO as an approach to improve quality of care (QoC) at facility level. This systematic review synthesises evidence on the effectiveness of the NMCR on QoC and maternal and perinatal health outcomes in low-income and middle-income countries (LMICs). METHODS: Studies were searched for in six electronic databases (MEDLINE, Index Medicus, Web of Science, the Cochrane library, Embase, LILACS), with no language restrictions. Two authors independently screened papers and selected them for inclusion and independently extracted data. Maternal mortality was the primary outcome. Secondary outcomes included any outcome informing on any of the six dimensions of QoC: efficacy, safety, efficiency, equity, accessibility and timely care, acceptability and patient-centred care. RESULTS: Out of 24 822 papers retrieved, 17 studies from 11 countries were included. Maternal mortality measured before and after the implementation of the NMCR cycle significantly decreased (OR 0.77, 95% CI 0.61 to 0.98, eight studies, 55 573 043 women; I=39%). A statistically significant reduction in the incidence of uterine rupture, postpartum haemorrhage and maternal sepsis was observed in three out of six studies. Ten studies reporting on maternal care process all showed some significant improvement when measured against predefined standards. All studies reported that the NMCR resulted in some amelioration of the facility structure (physical structure, staffing, equipment, training, organisation of care). Newborn outcomes were overall poorly reported; four studies showed no significant difference in perinatal mortality. Patient satisfaction and equity were also poorly reported. CONCLUSIONS: Policy makers may consider implementing the maternal NMCR cycle approach among strategies aiming at improving QoC and reducing maternal mortality and morbidity in LMIC. Future studies should better document the effectiveness of the NMCR cycle particularly on outcomes reflecting patient-centred care and cost-effectiveness.
Keywords: Developing Countries; Female; Humans; Infant, Newborn; Maternal Mortality; Near Miss, Healthcare; Parturition; Patient Satisfaction; Perinatal Mortality; Postpartum Hemorrhage; Poverty; Pregnancy; Quality of Health Care; Uterine Rupture

Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Emergency extracorporeal shockwave lithotripsy as opposed to delayed shockwave lithotripsy for the treatment of acute renal colic due to obstructive ureteral stone: a prospective randomized trial. - Bucci, Stefano; Umari, Paolo; Rizzo, Michele; Pavan, Nicola; Liguori, Giovanni; Barbone, Fabio; Trombetta, Carlo (Minerva Urol Nefrol, 2018)
BACKGROUND: The aim of this study was to assess the efficacy of emergency extracorporeal shockwave lithotripsy (eSWL) as first-line treatment in patients with acute colic due to obstructive ureteral stone. METHODS: Seventy-four patients were randomized to emergency SWL within 12 hours (eSWL group) and deferred SWL later than 3 days (dSWL group). Follow-up included ultrasound, KUB (kidney-ureter-bladder) radiography and CT (computed tomography) scan at 24 hours, 7 days, 1 and 3 months from the treatment. When necessary, repeated SWL (re-SWL) or ureteroscopy (auxiliary-URS) was performed. Preoperative and postoperative data were compared and stone free rates (SFR) and efficiency quotients (EQ) were evaluated. Analyses were performed using SAS software. RESULTS: Complete data of 70 patients were collected. 36 underwent eSWL and 34 dSWL. The mean patient age was 48.7. Mean stone size was 9.8 mm (CI 95%: 8.9-10.8). 25 (35.7%) were proximal and 45 (64.3%) distal. Mean SWL energy was 19.2 kV (CI 95%: 18.5-19.9) and mean number of shocks was 2657 (CI 95%: 2513-2802). eSWL patients needs less auxiliary-URS than dSWL patients (13.9% vs. 44.1%, P=0.039) and less re-SWL sessions (8.3% vs. 32.4%, P=0.093). SFR at 24 hours was 52.8% and 11.8% (P<0.001) and the EQ at 3 months was 79.1% and 57.5% in the eSWL and dSWL group respectively. Patients from the dSWL group spent more time in the hospital (2.21 vs. 1.36 days, P=0.046) and complication rates between the two groups were similar. CONCLUSIONS: eSWL is a safe procedure and delivers high SFR even within 24 hours especially for <10 mm stones. It is able to reduce the number of auxiliary procedures and hospitalization.
Keywords: Aged; Calculi; Emergency Medical Services; Female; Humans; Length of Stay; Lithotripsy; Male; Middle Aged; Prospective Studies; Renal Colic; Time-to-Treatment; Tomography, X-Ray Computed; Ureteral Obstruction

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Facilitators and barriers to the effective implementation of the individual maternal near-miss case reviews in low/middle-income countries: a systematic review of qualitative studies. - Lazzerini, Marzia; Ciuch, Margherita; Rusconi, Silvia; Covi, Benedetta (BMJ Open, 2018)
BACKGROUND: The maternal near-miss cases review (NMCR), a type of clinical audit, proved to be effective in improving quality of care and decreasing maternal mortality in low/middle-income countries (LMICs). However, challenges in its implementation have been described. OBJECTIVES: Synthesising the evidence on facilitators and barriers to the effective implementation of NMCR in LMICs. DESIGN: Systematic review of qualitative studies. DATA SOURCES: MEDLINE, LILACS, Global Health Library, SCI-EXPANDED, SSCI, Cochrane library and Embase were searched in December 2017. ELIGIBILITY CRITERIA FOR SELECTING STUDIES: Qualitative studies exploring facilitators and/or barriers of implementing NMCR in LMIC were included. DATA EXTRACTION AND SYNTHESIS: Two independent reviewers extracted data, performed thematic analysis and assessed risk of bias. RESULTS: Out of 25 361 papers retrieved, 9 studies from Benin, Brazil, Burkina Faso, Cote D'Ivoire, Ghana, Malawi, Morocco, Tanzania, Uganda could be included in the review. The most frequently reported barriers to NMCR implementation were the following: absence of national guidelines and local protocols; insufficient training on how to perform the audit; lack of leadership, coordination, monitoring and supervision; lack of resources and work overload; fear of blame and punishment; poor knowledge of evidenced-based medicine; hierarchical differences among staff and poor understating of the benefits of the NMCR. Major facilitators to NMCR implementation included: good leadership and coordination; training of all key staff; a good cultural environment; clear staff's perception on the benefits of conducting audit; patient empowerment and the availability of external support. CONCLUSIONS: In planning the NMCR implementation in LMICs, policy-makers should consider actions to prevent and mitigate common challenges to successful NMCR implementation. Future studies should aim at documenting facilitators and barriers to NMCR outside the African Region.

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

A Giant Ovarian Cyst in an Adolescent. - Corrias, Francesca; Pederiva, Federica; Cozzi, Giorgio; Ammar, Lydie; Cattaruzzi, Elisabetta; Lembo, Maria Antonietta; Barbi, Egidio (J Pediatr, 2018)
Keywords: Child; Cystadenoma, Serous; Female; Humans; Ovarian Neoplasms

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

In vivo microbiome and associated immune markers: New insights into the pathogenesis of vaginal dysbiosis. - Campisciano, Giuseppina; Zanotta, Nunzia; Licastro, Danilo; De Seta, Francesco; Comar, Manola (Sci Rep, 2018)
The microbiota fulfils a key role in the training and function of the immune system, which contributes to the symbiosis between the host and complex microbial communities. In this study, we characterized the interplay between vaginal bacteria and local immune mediators during dysbiosis in selected women of reproductive age who were grouped according to Nugent's criteria. The abundance of Gardnerella vaginalis and Bifidobacterium breve was increased in the intermediate dysbiotic status, while the presence of a plethora of non-resident bacteria characterized the group with overt vaginosis. In response to these increases, the anti-inflammatory IL1ra and pro-inflammatory IL2 increased, while the embryo trophic factors FGFβ and GMCSF decreased compared to the healthy milieu. A specific pattern, including IL1α, IL1β, IL8, MIG, MIP1α and RANTES, distinguished the intermediate group from the vaginosis group, while IL5 and IL13, which are secreted by Th2 cells, were significantly associated with the perturbation of the commensals Lactobacilli, Gardnerella and Ureaplasma. Summarizing, we postulate that although the dysbiotic condition triggers a pro-inflammatory process, the presence of a steady state level of Th2 may influence clinical manifestations. These results raise clinically relevant questions regarding the use of vaginal immunological markers as efficacious tools to monitor microbial alterations.
Keywords: Adult; Biomarkers; Cytokines; Dysbiosis; Female; Humans; Microbiota; Th2 Cells; Vagina

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

Low-dose sirolimus in two cousins with autoimmune lymphoproliferative syndrome-associated infection. - Nocerino, Agostino; Valencic, Erica; Loganes, Claudia; Pelos, Giorgio; Tommasini, Alberto (Pediatr Int, 2018)
Keywords: Anti-Bacterial Agents; Autoimmune Lymphoproliferative Syndrome; Child; Child, Preschool; Dose-Response Relationship, Drug; Female; Humans; Immunosuppressive Agents; Infant; Male; Otitis Media; Pneumonia, Bacterial; Sirolimus

MKRN3 levels in girls with central precocious puberty and correlation with sexual hormone levels: a pilot study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Capristo, Carlo; Tornese, Gianluca; Marzuillo, Pierluigi; Luongo, Caterina; Rosaria Umano, Giuseppina; Festa, Adalgisa; Coppola, Ruggero; Miraglia Del Giudice, Emanuele; Perrone, Laura (Endocrine, 2018)
PURPOSE: Recently, mutations of makorin RING-finger protein 3 (MKRN3) have been described in familial central precocious puberty. Serum levels of this protein decline before the pubertal onset in healthy girls and boys. The aim of the study is to investigate MKRN3 circulating levels in patients with central precocious puberty. METHODS: We performed an observational cross-sectional study. We enrolled 17 patients with central precocious puberty aged 7 years (range: 2-8 years) and breast development onset <8 years; 17 prepubertal control age-matched patients aged 6.3 years (2-8.2); and 10 pubertal stage-matched control patients aged 11.4 years (9-14). Serum values of MKRN3, gonadotropins, (17)estradiol and Anti-Müllerian Hormone were evaluated and the MKRN3 genotyped in central precocious puberty patients. RESULTS: No MKRN3 mutation was found among central precocious puberty patients. MKRN3 levels were lower in patients with central precocious puberty compared to prepubertal age-matched ones (p: 0.0004) and comparable to those matched for pubertal stage. MKRN3 levels were inversely correlated to Body Mass Index Standard Deviations (r:-0.35; p:0.02), Luteinizing Hormone (r:-0.35; p:0.03), FSH (r:-0.37; p:0.02), and (17)estradiol (r: -0.36; p:0.02). CONCLUSIONS: We showed that girls with central precocious puberty had lower peripheral levels of MKRN3 compared to age-matched pairs and that they negatively correlated to gonadotropins, estrogen, and BMI. Our findings support the MKRN3 involvement in central precocious puberty also in absence of deleterious mutations, although our sample size is small. In addition our data suggest the role of MKRN3 in the complex mechanism controlling puberty onset and its interaction with other factors affecting puberty such as nutrition.
Keywords: Adolescent; Adolescent Nutritional Physiological Phenomena; Anti-Mullerian Hormone; Case-Control Studies; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Cross-Sectional Studies; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Pilot Projects; Puberty, Precocious; Ribonucleoproteins; Sexual Maturation

MKRN3 Levels in Girls with Central Precocious Puberty during GnRHa Treatment: A Longitudinal Study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Tornese, Gianluca; Luongo, Caterina; Festa, Adalgisa; Marzuillo, Pierluigi; Miraglia Del Giudice, Emanuele (Horm Res Paediatr, 2018)
BACKGROUND: Recently, mutations of makorin RING finger protein 3 (MKRN3) have been identified in familial central precocious puberty (CPP). Serum levels of this protein decline before the pubertal onset in healthy girls and boys and are lower in patients with CPP compared to prepubertal matched pairs. The aim of our study was to investigate longitudinal changes in circulating MKRN3 levels in patients with CPP before and during GnRH analogs (GnRHa) treatment. METHODS: We performed a longitudinal prospective study. We enrolled 15 patients with CPP aged 7.2 years (range: 2-8) with age at breast development onset < 8 years and 12 control girls matched for the time from puberty onset (mean age 11.8 ± 1.2 years). Serum values of MKRN3, gonadotropins, and 17β-estradiol were evaluated before and during treatment with GnRHa (at 6 and 12 months). The MKRN3 gene was genotyped in CPP patients. In the girls from the control group, only basal levels were analyzed. RESULTS: No MKRN3 mutations were found among CPP patients. MKRN3 levels declined significantly from baseline to 6 months of GnRHa treatment (p = 0.0007) and from 6 to 12 months of treatment (p = 0.003); MKRN3 levels at 6 months were significantly lower than in the control girls (p < 0.0001). CONCLUSIONS: We showed that girls with CPP had a decline in peripheral levels of MKRN3 during GnRHa treatment. Our data suggest a suppression of MKRN3 by continuous pharmacological administration of GnRHa.
Keywords: Brain Diseases; Case-Control Studies; Child; Child, Preschool; Female; Follicle Stimulating Hormone; Genotype; Gonadotropin-Releasing Hormone; Humans; Longitudinal Studies; Luteinizing Hormone; Male; Puberty, Precocious; Ribonucleoproteins

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Non-invasive biomarkers of fetal brain development reflecting prenatal stress: An integrative multi-scale multi-species perspective on data collection and analysis. - Frasch, Martin G; Lobmaier, Silvia M; Stampalija, Tamara; Desplats, Paula; Pallarés, María Eugenia; Pastor, Verónica; Brocco, Marcela A; Wu, Hau-Tieng; Schulkin, Jay; Herry, Christophe L; Seely, Andrew J E; Metz, Gerlinde A S; et al. (Neurosci Biobehav Rev, 2018)
Prenatal stress (PS) impacts early postnatal behavioural and cognitive development. This process of 'fetal programming' is mediated by the effects of the prenatal experience on the developing hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). We derive a multi-scale multi-species approach to devising preclinical and clinical studies to identify early non-invasively available pre- and postnatal biomarkers of PS. The multiple scales include brain epigenome, metabolome, microbiome and the ANS activity gauged via an array of advanced non-invasively obtainable properties of fetal heart rate fluctuations. The proposed framework has the potential to reveal mechanistic links between maternal stress during pregnancy and changes across these physiological scales. Such biomarkers may hence be useful as early and non-invasive predictors of neurodevelopmental trajectories influenced by the PS as well as follow-up indicators of success of therapeutic interventions to correct such altered neurodevelopmental trajectories. PS studies must be conducted on multiple scales derived from concerted observations in multiple animal models and human cohorts performed in an interactive and iterative manner and deploying machine learning for data synthesis, identification and validation of the best non-invasive detection and follow-up biomarkers, a prerequisite for designing effective therapeutic interventions.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.

Pharmacogenetics of treatments for inflammatory bowel disease. - Lucafò, Marianna; Franca, Raffaella; Selvestrel, Davide; Curci, Debora; Pugnetti, Letizia; Decorti, Giuliana; Stocco, Gabriele (Expert Opin Drug Metab Toxicol, 2018)
INTRODUCTION: Inflammatory bowel disease is a chronic inflammation of the gut whose pathogenesis is still unclear. Although no curative therapy is currently available, a number of drugs are used in induction and maintenance therapy; however, for most of these drugs, a high inter-individual variability in response is observed. Among the factors of this variability, genetics plays an important role. Areas covered: This review summarizes the results of pharmacogenetic studies, considering the most important drugs used and in particular aminosalycilates, glucocorticoids, thiopurines, monoclonal antibodies and thalidomide. Most studies used a candidate gene approach, even if significant breakthroughs have been obtained recently from applying genome-wide studies. When available, also investigations considering epigenetics and pharmacogenetic dosing guidelines have been included. Expert opinion: Only for thiopurines, genetic markers identified as predictors of efficacy or adverse events have allowed the development of dosing guidelines. For the other drugs, encouraging results are available and great expectations rely on the study of epigenetics and integration with pharmacokinetic information, especially useful for biologics. However, to improve therapy of IBD patients with these drugs, for implementation in the clinics of pharmacogenetics, informatic clinical decision support systems and training about pharmacogenetics of health providers are needed.
Keywords: Dose-Response Relationship, Drug; Epigenesis, Genetic; Gastrointestinal Agents; Genetic Markers; Genetic Predisposition to Disease; Humans; Inflammatory Bowel Diseases; Pharmacogenetics

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Predictive value of the number of adverse reaction episodes for the IgE-mediated food allergy diagnosis. - Miceli Sopo, S; Gurnari, G; Monaco, S; Romano, A; Liotti, L; Cuomo, B; Dello Iacono, I; Badina, L; Longo, G; Calvani, M; Giannone, A; Calabrò, C; et al. (Allergol Immunopathol (Madr), 2018)
INTRODUCTION AND OBJECTIVES: The reproducibility of the adverse reaction increases the suggestiveness of a history of food allergy. However, the positive predictive value (PPV) of multiple adverse reaction episodes for the diagnosis of IgE-mediated food allergy is not known. This evaluation was the objective of our study. PATIENTS AND METHODS: We retrospectively studied 180 children with a history of non-anaphylactic adverse reactions after the ingestion of a food. All children had the prick test positive for the offending food and performed the oral food challenge (OFC) within 12 months after the last adverse reaction episode (ARE). We have evaluated whether increasing the number of ARE increased the probability that the OFC would be positive (failed). RESULTS: 93 patients (52%) presented one ARE, 49 (27%) presented two ARE, 24 (13%) presented three ARE, 14 (8%) patients presented≥four ARE. The OFC was positive in 94/180 (52%). The outcome of the OFC was found to be positively correlated with the number of ARE (OR=1.56; 95% CI=1.16-2.09; p=0.003). A PPV=100% was observed with a number of ARE≥five. CONCLUSIONS: The number of ARE is an important predictor of the diagnosis of food allergy, although less than we would have imagined. The number of ARE could be used to increase the predictability of the diagnostic tests currently in use, to define clinical prediction rules alternative to OFC and easy to use in clinical practice.

Quality of care for children with acute malnutrition at health center level in Uganda: a cross sectional study in West Nile region during the refugee crisis. - Wanzira, Humphrey; Muyinda, Richard; Lochoro, Peter; Putoto, Giovanni; Segafredo, Giulia; Wamani, Henry; Lazzerini, Marzia (BMC Health Serv Res, 2018)
BACKGROUND: Arua district, in Uganda, hosts some of the largest refugee camps in the country. The estimated prevalence of moderate and severe acute malnutrition in children is higher than the national estimates (10.4 and 5.6% respectively, compared to 3.6 and 1.3%). This study aimed at assessing the quality of care provided to children with acute malnutrition at out-patient level in such a setting. METHODS: Six facilities with the highest number of children with malnutrition were selected. The main tool used was the National Nutrition Service Delivery Assessment Tool, assessing 10 key areas of service delivery and assigned a score as either poor, fair, good or excellent. Health outcomes, quality of case management and data quality were assessed from the health management information system and from the official nutrition registers. RESULTS: All facilities except two scored either poor or fair under all the 10 assessment areas. Overall, 33/60 (55%) areas scored as poor, 25/60 (41%) as fair, 2/60 (3.3%) as good, and none as excellent. Main gaps identified included: lack of trained staff; disorganised patient flow; poor case management; stock out of essential supplies including ready-to-use therapeutic foods; weak community linkage. A sample coverage of 45.4% (1020/2248) of total children admitted in the district during the 2016 financial year were included. The overall mean cure rate was 52.9% while the default rate was 38.3%. There was great heterogeneity across health facilities in health outcomes, quality of case management, and data quality. CONCLUSION: This study suggests that quality of care provided to children with malnutrition at health center level is substandard with unacceptable low cure rates. It is essential to identify effective approaches to enhance adherence to national guidelines, provision of essential nutritional commodities, regular monitoring of services and better linkage with the community through village health teams.
Keywords: Child Nutrition Disorders; Child, Preschool; Cross-Sectional Studies; Health Facilities; Humans; Nutrition Assessment; Nutritional Status; Prevalence; Quality of Health Care; Refugee Camps; Refugees; Uganda

Repositioning of Tak-475 In Mevalonate Kinase Disease: Translating Theory Into Practice. - Marcuzzi, Annalisa; Loganes, Claudia; Celeghini, Claudio; Kleiner, Giulio (Curr Med Chem, 2018)
BACKGROUND: Mevalonate Kinase Deficiency (MKD, OMIM #610377) is a rare autosomal recessive metabolic and inflammatory disease. In MKD, defective function of the enzyme mevalonate kinase, due to a mutation in the MVK gene, leads to the shortage of mevalonate- derived intermediates, which results in unbalanced prenylation of proteins and altered metabolism of sterols. These defects lead to a complex multisystem inflammatory and metabolic syndrome. OBJECTIVE: Although biologic therapies aimed at blocking the inflammatory cytokine interleukin- 1 can significantly reduce inflammation, they cannot completely control the clinical symptoms that affect the nervous system. For this reason, MKD can still be considered an orphan drug disease. The availability of MKD models reproducing the MKD-systematic inflammation, is crucial to improve the knowledge on its pathogenesis, which is still unknown. New therapies are also required in order to improve pateints' conditions and their quality of life. METHODS: MKD-cellular models can be obtained by biochemical inhibition of mevalonatederived isoprenoids. Of note, these cells present an exaggerated response to inflammatory stimuli that can be reduced by treatment with zaragozic acid, an inhibitor of squalene synthase, thus increasing the availability of isoprenoids intermediates upstream the enzymatic block. RESULTS: A similar action might be obtained by lapaquistat acetate (TAK-475, Takeda), a drug that underwent extensive clinical trials as a cholesterol lowering agent 10 years ago, with a good safety profile. CONCLUSIONS: Here we describe the preclinical evidence supporting the possible repositioning of TAK-475 from its originally intended use to the treatment of MKD and discuss its potential to modulate the mevalonate pathway in inflammatory diseases.
Keywords: Acyl Coenzyme A; Cholesterol; Drug Repositioning; Farnesyl-Diphosphate Farnesyltransferase; Humans; Hypercholesterolemia; Mevalonate Kinase Deficiency; Oxazepines; Phosphotransferases (Alcohol Group Acceptor); Piperidines

The Role of Oxidative Stress and Membrane Transport Systems during Endometriosis: A Fresh Look at a Busy Corner. - Vitale, Salvatore Giovanni; Capriglione, Stella; Peterlunger, Isabel; La Rosa, Valentina Lucia; Vitagliano, Amerigo; Noventa, Marco; Valenti, Gaetano; Sapia, Fabrizio; Angioli, Roberto; Lopez, Salvatore; Sarpietro, Giuseppe; Rossetti, Diego; et al. (Oxid Med Cell Longev, 2018)
Endometriosis is a condition characterized by the presence of endometrial tissue outside the uterine cavity, leading to a chronic inflammatory reaction. It is one of the most widespread gynecological diseases with a 10-15% prevalence in the general female population, rising up to 30-45% in patients with infertility. Although it was first described in 1860, its etiology and pathogenesis are still unclear. It is now accepted that inflammation plays a central role in the development and progression of endometriosis. In particular, it is marked by an inflammatory process associated with the overproduction of an array of inflammatory mediators such as prostaglandins, metalloproteinases, cytokines, and chemokines. In addition, the growth and adhesion of endometrial cells in the peritoneal cavity due to reactive oxygen species (ROS) and free radicals lead to disease onset, its ensuing symptoms-among which pain and infertility. The aim of our review is to evaluate the role of oxidative stress and ROS in the pathogenesis of endometriosis and the efficacy of antioxidant therapy in the treatment and mitigation of its symptoms.
Keywords: Endometriosis; Female; Humans; Oxidative Stress

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Rothmund-Thomson Syndrome: Insights from New Patients on the Genetic Variability Underpinning Clinical Presentation and Cancer Outcome. - Colombo, Elisa A; Locatelli, Andrea; Cubells Sánchez, Laura; Romeo, Sara; Elcioglu, Nursel H; Maystadt, Isabelle; Esteve Martínez, Altea; Sironi, Alessandra; Fontana, Laura; Finelli, Palma; Gervasini, Cristina; Pecile, Vanna; et al. (Int J Mol Sci, 2018)
Biallelic mutations in gene, a caretaker of the genome, cause Rothmund-Thomson type-II syndrome (RTS-II) and confer increased cancer risk if they damage the helicase domain. We describe five families exemplifying clinical and allelic heterogeneity of RTS-II, and report the effect of pathogenic variants by predictions and transcripts analyses. Complete phenotype of patients #39 and #42 whose affected siblings developed osteosarcoma correlates with their c.[1048_1049del], c.[1878+32_1878+55del] and c.[1568G>C;1573delT], c.[3021_3022del] variants which damage the helicase domain. Literature survey highlights enrichment of these variants affecting the helicase domain in patients with cancer outcome raising the issue of strict oncological surveillance. Conversely, patients #29 and #19 have a mild phenotype and carry, respectively, the unreported homozygous c.3265G>T and c.3054A>G variants, both sparing the helicase domain. Finally, despite matching several criteria for RTS clinical diagnosis, patient #38 is heterozygous for c.2412_2414del; no pathogenic CNVs out of those evidenced by high-resolution CGH-array, emerged as contributors to her phenotype.
Keywords: Adolescent; Adult; Cell Line, Tumor; Child; Female; Homozygote; Humans; Male; Mutation; Pedigree; Phenotype; RecQ Helicases; Rothmund-Thomson Syndrome

Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Serum Stem Cell Growth Factor Beta for the Prediction of Therapy Response in Hepatocellular Carcinoma. - Sukowati, Caecilia H C; Patti, Riccardo; Pascut, Devis; Ladju, Rusdina B; Tarchi, Paola; Zanotta, Nunzia; Comar, Manola; Tiribelli, Claudio; Crocè, Lory S (Biomed Res Int, 2018)
Introduction: Chronic inflammatory response is one of major contributors in the development of hepatocellular carcinoma (HCC). Inflammatory molecules, such as cytokines and growth factors in the circulation, can be useful in the diagnosis and prognosis of the patients. The stem cell growth factor beta (SCGF), a newly found protein, is a secreted sulfated glycoprotein and it functions as a growth factor for primitive hematopoietic progenitor cells. The level of SCGF had been reported to be elevated in several cancer types. However, there is very few or even no information on this protein in the study of HCC, even more in clinical studies. Methods: A multiplex immunoassay panel of 48 cytokines and growth factors were utilized to screen 68 sera from 29 HCC patients at pretreatment (T0), 1 month (T1), and 6 months (T6) after treatment by either radiofrequency ablation (RF) or transarterial chemoembolization (TACE). Treatment response was evaluated according to mRECIST criteria. Results: Immunoassay screening showed that the levels of IL-17, CTACK, TNF, IL-2R, IL-8, and SCGF were different in Complete Responders (CR) and Nonresponders (NR) groups. At T0 and T1, the SCGF level was significantly the highest in NR (23.8 and 40.7 ng/mL, respectively), followed by early recurrence (25.4 and 25.0 ng/mL), and CR (6.7 and 5.3 ng/mL), independently from HCV, stages, and treatment type. Low basal SCGF level was associated with longer disease-free survival compared to high SCGF. Conclusion: In this study, for the first time, we demonstrate that the high level of serum SCGF at pre- and posttreatment is associated with HCC nonresponsiveness.
Keywords: Aged; Carcinoma, Hepatocellular; Chemoembolization, Therapeutic; Female; Hematopoietic Cell Growth Factors; Humans; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Retrospective Studies; Stem Cells; Treatment Outcome

Theophylline as a precision therapy in a young girl with PIK3R1 immunodeficiency. - Valencic, Erica; Grasso, Antonio Giacomo; Conversano, Ester; Lucafò, Marianna; Piscianz, Elisa; Gregori, Massimo; Conti, Francesca; Cancrini, Caterina; Tommasini, Alberto (J Allergy Clin Immunol Pract, 2018)

What is the quality of the maternal near-miss case reviews in WHO European Region? Cross-sectional study in Armenia, Georgia, Latvia, Republic of Moldova and Uzbekistan. - Bacci, Alberta; Hodorogea, Stelian; Khachatryan, Henrik; Babojonova, Shohida; Irsa, Signe; Jansone, Maira; Dondiuc, Iurie; Matarazde, George; Lazdane, Gunta; Lazzerini, Marzia (BMJ Open, 2018)
OBJECTIVES: The maternal near-miss case review (NMCR) cycle is a type of clinical audit aiming at improving quality of maternal healthcare by discussing near-miss cases. In several countries this approach has been introduced and supported by WHO and partners since 2004, but information on the quality of its implementation is missing. This study aimed at evaluating the quality of the NMCR implementation in selected countries within WHO European Region. DESIGN: Cross-sectional study. SETTINGS: Twenty-three maternity units in Armenia, Georgia, Latvia, Moldova and Uzbekistan. ASSESSMENT TOOLS: A predefined checklist including 50 items, according to WHO methodology. Quality in the NMCR implementation was defined by summary scores ranging from 0 (totally inappropriate) to 3 (appropriate). RESULTS: Quality of the NMCR implementation was heterogeneous among different countries, and within the same country. Overall, the first part of the audit cycle (from case identification to case analysis) was fairly well performed (mean score 2.00, 95% CI 1.94 to 2.06), with the exception of the 'inclusion of users' views' (mean score 0.66, 95% CI 0.11 to 1.22), while the second part (developing recommendations, implementing them and ensuring quality) was poorly performed (mean score 0.66, 95% CI 0.11 to 1.22). Each country had at least one champion facility, where quality of the NMCR cycle was acceptable. Quality of the implementation was not associated with its duration. Gaps in implementation were of technical, organisational and attitudinal nature. CONCLUSIONS: Ensuring quality in the NMCR may be difficult but achievable. The high heterogeneity in results within the same country suggests that quality of the NMCR implementation depends, to a large extent, from hospital factors, including staff's commitment, managerial support and local coordination. Efforts should be put in preventing and mitigating common barriers that hamper successful NMCR implementation.
Keywords: Armenia; Checklist; Cross-Sectional Studies; Female; Georgia; Humans; Latvia; Maternal Mortality; Medical Audit; Moldova; Near Miss, Healthcare; Pregnancy; Pregnancy Complications; Quality Improvement; Uzbekistan

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Climate change, emerging infections and blood donations. - Cegolon, L; Heymann, W C; Lange, J H (J Travel Med, 2017)
Keywords: Blood Transfusion; Climate Change; Communicable Diseases, Emerging; Global Health; Humans; Travel

Combined use of AFM and soft X-ray microscopy to reveal fibres' internalization in mesothelial cells. - Gianoncelli, Alessandra; Kourousias, George; Cammisuli, Francesca; Cassese, Damiano; Rizzardi, Clara; Radillo, Oriano; Lazzarino, Marco; Pascolo, Lorella (Analyst, 2017)
Nanotoxicology and nanomedicine investigations often require the probing of nano-objects such as fibres and particles in biological samples and cells, whilst internalization and intracellular destiny are the main issues for in vitro cellular studies. Various high resolution microscopy techniques are well suited for providing this highly sought-after information. However, sample preparation, nanomaterial composition and sectioning challenges make it often difficult to establish whether the fibres or particles have been internalized or they are simply overlaying or underlying the biological matter. In this paper we suggest a novel suitable combination of two different microscopic techniques to reveal in intact cells the uptake of asbestos fibres by mesothelial cells. After exposure to asbestos fibres and fixation, cells were first analysed under the AFM instrument and then imaged under the TwinMic soft X-ray microscope at Elettra Sincrotrone. The suggested approach combines standard soft X-ray microscopy imaging and AFM microscopy, with a common non-invasive sample preparation protocol which drastically reduces the experimental uncertainty and provides a quick and definitive answer to the nanoparticle cellular and tissue uptake.
Keywords: Asbestos; Cell Line; Epithelial Cells; Epithelium; Humans; Microscopy, Atomic Force; X-Rays

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

Cubosomes for in vivo fluorescence lifetime imaging. - Biffi, Stefania; Andolfi, Laura; Caltagirone, Claudia; Garrovo, Chiara; Falchi, Angela M; Lippolis, Vito; Lorenzon, Andrea; Macor, Paolo; Meli, Valeria; Monduzzi, Maura; Obiols-Rabasa, Marc; Petrizza, Luca; et al. (Nanotechnology, 2017)
Herein we provided the first proof of principle for in vivo fluorescence optical imaging application using monoolein-based cubosomes in a healthy mouse animal model. This formulation, administered at a non-cytotoxic concentration, was capable of providing both exogenous contrast for NIR fluorescence imaging with very high efficiency and chemospecific information upon lifetime analysis. Time-resolved measurements of fluorescence after the intravenous injection of cubosomes revealed that the dye rapidly accumulated mainly in the liver, while lifetimes profiles obtained in vivo allowed for discriminating between free dye or dye embedded within the cubosome nanostructure after injection.
Keywords: Animals; Carbocyanines; Cell Survival; Drug Compounding; Erythrocytes; Female; Fluorescent Dyes; Glycerides; Humans; Injections, Intravenous; Liposomes; Liver; Mice; Mice, Inbred BALB C; Nanoparticles; NIH 3T3 Cells; Optical Imaging; Particle Size; Spectroscopy, Near-Infrared; Time-Lapse Imaging

Curcumin Anti-Apoptotic Action in a Model of Intestinal Epithelial Inflammatory Damage. - Loganes, Claudia; Lega, Sara; Bramuzzo, Matteo; Vecchi Brumatti, Liza; Piscianz, Elisa; Valencic, Erica; Tommasini, Alberto; Marcuzzi, Annalisa (Nutrients, 2017)
The purpose of this study is to determine if a preventive treatment with curcumin can protect intestinal epithelial cells from inflammatory damage induced by IFNγ. To achieve this goal we have used a human intestinal epithelial cell line (HT29) treated with IFNγ to undergo apoptotic changes that can reproduce the damage of intestinal epithelia exposed to inflammatory cytokines. In this model, we measured the effect of curcumin (curcuminoid from ) added as a pre-treatment at different time intervals before stimulation with IFNγ. Curcumin administration to HT29 culture before the inflammatory stimulus IFNγ reduced the cell apoptosis rate. This effect gradually declined with the reduction of the curcumin pre-incubation time. This anti-apoptotic action by curcumin pre-treatment was paralleled by a reduction of secreted IL7 in the HT29 culture media, while there was no relevant change in the other cytokine levels. Even though curcumin pre-administration did not impact the activation of the NF-κB pathway, a slight effect on the phosphorylation of proteins in this inflammatory signaling pathway was observed. In conclusion, curcumin pre-treatment can protect intestinal cells from inflammatory damage. These results can be the basis for studying the preventive role of curcumin in inflammatory bowel diseases.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Apoptosis; Cell Survival; Curcuma; Curcumin; Cytokines; Epithelial Cells; HT29 Cells; Humans; Inflammation; Interferon-gamma; Interleukin-7; Intestinal Mucosa; NF-kappa B; Phosphorylation; Signal Transduction

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

Describing Kawasaki shock syndrome: results from a retrospective study and literature review. - Taddio, Andrea; Rossi, Eleonora Dei; Monasta, Lorenzo; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Bronzetti, Gabriele; Marrani, Edoardo; Mottolese, Biancamaria D'Agata; Simonini, Gabriele; Cimaz, Rolando; Ventura, Alessandro (Clin Rheumatol, 2017)
Kawasaki shock syndrome (KSS) is a rare manifestation of Kawasaki disease (KD) characterized by systolic hypotension or clinical signs of poor perfusion. The objectives of the study are to describe the main clinical presentation, echocardiographic, and laboratory findings, as well as the treatment options and clinical outcomes of KSS patients when compared with KD patients. This is a retrospective study. All children referred to two pediatric rheumatology units from January 1, 2012, to December 31, 2014, were enrolled. Patients were divided into patients with or without KSS. We compared the two groups according to the following variables: sex, age, type of KD (classic, with less frequent manifestations, or incomplete), clinical manifestations, cardiac involvement, laboratory findings, therapy administered, response to treatment, and outcome. Eighty-four patients with KD were enrolled. Of these, five (6 %) met the criteria for KSS. Patients with KSS had higher values of C-reactive protein (p = 0.005), lower hemoglobin levels (p = 0.003); more frequent hyponatremia (p = 0.004), hypoalbuminemia (p = 0.004), and coagulopathy (p = 0.003); and increase in cardiac troponins (p = 0.000). Among the KSS patients, three had a coronary artery involvement, but none developed a permanent aneurysm. Intravenous immunoglobulin resistance was more frequent in the KSS group, although not significantly so (3/5, 60 % vs. 23/79, 30 %, P = NS). None of the five cases was fatal, and all recovered without sequelae. KSS patients are more likely to have higher rates of cardiac involvement. However, most cardiovascular abnormalities resolved promptly with therapy.
Keywords: C-Reactive Protein; Child; Child, Preschool; Echocardiography; Female; Heart Failure; Hemoglobins; Humans; Immunoglobulins, Intravenous; Male; Mucocutaneous Lymph Node Syndrome; Retrospective Studies; Shock; Syndrome

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Essure Permanent Birth Control, Effectiveness and Safety: An Italian 11-Year Survey. - Franchini, Mario; Zizolfi, Brunella; Coppola, Carmela; Bergamini, Valentino; Bonin, Cecilia; Borsellino, Giovanni; Busato, Enrico; Calabrese, Stefania; Calzolari, Stefano; Fantin, Gian Piero; Giarrè, Giovanna; Litta, Piero; et al. (J Minim Invasive Gynecol, 2017)
STUDY OBJECTIVE: To describe safety, tolerability, and effectiveness results through a minimum 2-year follow-up of patients who underwent permanent sterilization with the Essure insert. DESIGN: A retrospective multicenter study (Canadian Task Force classification II2). SETTING: Seven general hospitals and 4 clinical teaching centers in Italy. PATIENTS: A total of 1968 women, mean age 39.5 years (range, 23-48 years) who underwent office hysteroscopic sterilization using the Essure insert between April 1, 2003, and December 30, 2014. INTERVENTION: The women underwent office hysteroscopic bilateral Essure insert placement, with satisfactory device location and tube occlusion based on hysterosalpingography or hysterosalpingo-contrast sonography (HyCoSy). MEASUREMENTS AND MAIN RESULTS: Placement rate, successful bilateral tubal occlusion, perioperative adverse events, early postoperative (during the first 3 months of follow-up), and late complications were evaluated. Satisfactory insertion was accomplished in 97.2% of women and, in 4, perforation and 1 expulsion were detected during hysterosalpingography. Three unintended pregnancies occurred before the 3-month confirmation test. Two pregnancies were reported among women relying on the Essure inserts. Postprocedure pain was minimal and brief; in 9 women, pelvic pain became intractable, necessitating removal of the devices via laparoscopy. On telephone interviews, overall satisfaction was rated as "very satisfied" by the majority of women (97.6%), and no long-term adverse events were reported. CONCLUSION: The findings from this extended Italian survey further support the effectiveness, tolerability, and satisfaction of Essure hysteroscopic sterilization when motivated women are selected and well informed of the potential risks of the device. Moreover, the results do not demonstrate an increased incidence of complications and pregnancies associated with long-term Essure use. Patients with a known hypersensitivity to nickel may be less suitable candidates for the Essure insert.
Keywords: Adult; Fallopian Tubes; Female; Follow-Up Studies; Humans; Hypersensitivity; Hysterosalpingography; Hysteroscopy; Italy; Laparoscopy; Middle Aged; Nickel; Pain; Pregnancy; Pregnancy, Unplanned; Retrospective Studies; Sterilization, Reproductive; Sterilization, Tubal; Surveys and Questionnaires; Young Adult

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Histoproteomic Characterization of Localized Cutaneous Amyloidosis in X-Linked Reticulate Pigmentary Disorder. - L'Imperio, Vincenzo; Bruno, Irene; Rabach, Ingrid; Smith, Andrew; Chinello, Clizia; Stella, Martina; Magni, Fulvio; Pagni, Fabio (Skin Pharmacol Physiol, 2017)
Keywords: Amyloidosis; Genetic Diseases, X-Linked; Humans; Pigmentation Disorders; Proteomics; Skin Diseases

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Identification of proteins with different abundance associated with cell migration and proliferation in leiomyoma interstitial fluid by proteomics. - Ura, Blendi; Scrimin, Federica; Franchin, Cinzia; Arrigoni, Giorgio; Licastro, Danilo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2017)
Uterine leiomyoma is the most common female reproductive tract benign tumor. Little is known about protein composition and changes in the leiomyoma interstitial fluid (IF). The present study focused on changes in protein abundance in the IF of leiomyoma. Leiomyoma IFs and adjacent myometrial IFs were obtained and analyzed by two-dimensional electrophoresis (2-DE) coupled with mass spectrometry and western blotting for 2-DE data validation. A total of 25 unique proteins were observed to change significantly (P<0.05). Of these proteins with different abundance, 22 had not been previously identified in leiomyoma IF. analysis predicted that three of these proteins were secreted via classical mechanisms, while 22 were secreted via non-classical mechanisms. Ingenuity Pathway Analysis identified 17 proteins associated with cellular migration and proliferation. Among these, phosphoglycerate mutase 1 had not been previously associated with leiomyoma. The abundance of seven proteins was further validated by western blotting. A comparative proteomic approach identified a number of proteins associated with cellular migration and proliferation, with changes in abundance in IF likely to be involved in tumor development. Further studies will be required to investigate the role of these proteins in leiomyoma IF and their possible association with tumor development and growth.

Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Clinical and Hypoxemic Childhood Pneumonia over Three Years in Central Malawi: An Observational Study. - McCollum, Eric D; Nambiar, Bejoy; Deula, Rashid; Zadutsa, Beatiwel; Bondo, Austin; King, Carina; Beard, James; Liyaya, Harry; Mankhambo, Limangeni; Lazzerini, Marzia; Makwenda, Charles; Masache, Gibson; et al. (PLoS One, 2017)
BACKGROUND: The pneumococcal conjugate vaccine's (PCV) impact on childhood pneumonia during programmatic conditions in Africa is poorly understood. Following PCV13 introduction in Malawi in November 2011, we evaluated the case burden and rates of childhood pneumonia. METHODS AND FINDINGS: Between January 1, 2012-June 30, 2014 we conducted active pneumonia surveillance in children <5 years at seven hospitals, 18 health centres, and with 38 community health workers in two districts, central Malawi. Eligible children had clinical pneumonia per Malawi guidelines, defined as fast breathing only, chest indrawing +/- fast breathing, or, ≥1 clinical danger sign. Since pulse oximetry was not in the Malawi guidelines, oxygenation <90% defined hypoxemic pneumonia, a distinct category from clinical pneumonia. We quantified the pneumonia case burden and rates in two ways. We compared the period immediately following vaccine introduction (early) to the period with >75% three-dose PCV13 coverage (post). We also used multivariable time-series regression, adjusting for autocorrelation and exploring seasonal variation and alternative model specifications in sensitivity analyses. The early versus post analysis showed an increase in cases and rates of total, fast breathing, and indrawing pneumonia and a decrease in danger sign and hypoxemic pneumonia, and pneumonia mortality. At 76% three-dose PCV13 coverage, versus 0%, the time-series model showed a non-significant increase in total cases (+47%, 95% CI: -13%, +149%, p = 0.154); fast breathing cases increased 135% (+39%, +297%, p = 0.001), however, hypoxemia fell 47% (-5%, -70%, p = 0.031) and hospital deaths decreased 36% (-1%, -58%, p = 0.047) in children <5 years. We observed a shift towards disease without danger signs, as the proportion of cases with danger signs decreased by 65% (-46%, -77%, p<0.0001). These results were generally robust to plausible alternative model specifications. CONCLUSIONS: Thirty months after PCV13 introduction in Malawi, the health system burden and rates of the severest forms of childhood pneumonia, including hypoxemia and death, have markedly decreased.
Keywords: Child; Child Mortality; Cost of Illness; Dose-Response Relationship, Immunologic; Geography; Humans; Hypoxia; Malawi; Pneumococcal Vaccines; Pneumonia, Pneumococcal; Time Factors; Vaccines, Conjugate

Impaired fasting glucose and impaired glucose tolerance in children and adolescents with overweight/obesity. - Di Bonito, P; Pacifico, L; Chiesa, C; Valerio, G; Miraglia Del Giudice, E; Maffeis, C; Morandi, A; Invitti, C; Licenziati, M R; Loche, S; Tornese, G; Franco, F; et al. (J Endocrinol Invest, 2017)
OBJECTIVE: To investigate in a large sample of overweight/obese (OW/OB) children and adolescents the prevalence of prediabetic phenotypes such as impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and to assess their association with cardiometabolic risk (CMR) factors including hepatic steatosis (HS). METHODS: Population data were obtained from the CARdiometabolic risk factors in children and adolescents in ITALY study. Between 2003 and 2013, 3088 youths (972 children and 2116 adolescents) received oral glucose tolerance test (OGTT) and were included in the study. In 798 individuals, abdominal ultrasound for identification of HS was available. RESULTS: The prevalence of IFG (3.2 vs. 3.3%) and IGT (4.6 vs. 5.0%) was similar between children and adolescents. Children with isolated IGT had a 2-11 fold increased risk of high LDL-C, non-HDL-C, Tg/HDL-C ratio, and low insulin sensitivity, when compared to those with normal glucose tolerance (NGT). No significant association of IFG with any CMR factor was found in children. Among adolescents, IGT subjects, and to a lesser extent those with IFG, showed a worse CMR profile compared to NGT subgroup. In the overall sample, IGT phenotype showed a twofold increased risk of HS compared to NGT subgroup. CONCLUSIONS: Our study shows an unexpected similar prevalence of IFG and IGT between children and adolescents with overweight/obesity. The IGT phenotype was associated with a worse CMR profile in both children and adolescents. Phenotyping prediabetes conditions by OGTT should be done as part of prediction and prevention of cardiometabolic diseases in OW/OB youth since early childhood.
Keywords: Adolescent; Blood Glucose; Case-Control Studies; Child; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin; Insulin Resistance; Italy; Male; Obesity; Overweight; Prediabetic State; Prevalence

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

Intranasal Dexmedetomidine Sedation as Adjuvant Therapy in Acute Asthma Exacerbation With Marked Anxiety and Agitation. - Cozzi, Giorgio; Lega, Sara; Giorgi, Rita; Barbi, Egidio (Ann Emerg Med, 2017)
We describe 2 patients with acute asthma exacerbation who were admitted to the emergency department (ED) with severe agitation and restlessness as a prominent finding, for which bedside asthma treatment sedation with intranasal dexmedetomidine was performed. In both cases, dexmedetomidine allowed the patients to rest and improved tolerance to treatment. Dexmedetomidine is a unique sedative with an excellent safety profile and minimal effect on respiratory function. These properties render it particularly promising for the management of severe agitation in children admitted to the ED with acute asthma exacerbation.
Keywords: Acute Disease; Administration, Intranasal; Anxiety; Asthma; Child, Preschool; Dexmedetomidine; Emergency Service, Hospital; Female; Humans; Hypnotics and Sedatives; Infant; Psychomotor Agitation

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

The Italian Society for Pediatric Nephrology (SINePe) consensus document on the management of nephrotic syndrome in children: Part I - Diagnosis and treatment of the first episode and the first relapse. - Pasini, Andrea; Benetti, Elisa; Conti, Giovanni; Ghio, Luciana; Lepore, Marta; Massella, Laura; Molino, Daniela; Peruzzi, Licia; Emma, Francesco; Fede, Carmelo; Trivelli, Antonella; Maringhini, Silvio; et al. (Ital J Pediatr, 2017)
This consensus document is aimed at providing an updated, multidisciplinary overview on the diagnosis and treatment of pediatric nephrotic syndrome (NS) at first presentation. It is the first consensus document of its kind to be produced by all the pediatric nephrology centres in Italy, in line with what is already present in other countries such as France, Germany and the USA. It is based on the current knowledge surrounding the symptomatic and steroid treatment of NS, with a view to providing the basis for a separate consensus document on the treatment of relapses. NS is one of the most common pediatric glomerular diseases, with an incidence of around 2-7 cases per 100000 children per year. Corticosteroids are the mainstay of treatment, but the optimal therapeutic regimen for managing childhood idiopathic NS is still under debate. In Italy, shared treatment guidelines were lacking and, consequently, the choice of steroid regimen was based on the clinical expertise of each individual unit. On the basis of the 2015 Cochrane systematic review, KDIGO Guidelines and more recent data from the literature, this working group, with the contribution of all the pediatric nephrology centres in Italy and on the behalf of the Italian Society of Pediatric Nephrology, has produced a shared steroid protocol that will be useful for National Health System hospitals and pediatricians. Investigations at initial presentation and the principal causes of NS to be screened are suggested. In the early phase of the disease, symptomatic treatment is also important as many severe complications can occur which are either directly related to the pathophysiology of the underlying NS or to the steroid treatment itself. To date, very few studies have been published on the prophylaxis and treatment of these early complications, while recommendations are either lacking or conflicting. This consensus provides indications for the prevention, early recognition and treatment of these complications (management of edema and hypovolemia, therapy and prophylaxis of infections and thromboembolic events). Finally, recommendations about the clinical definition of steroid resistance and its initial diagnostic management, as well as indications for renal biopsy are provided.
Keywords: Adrenal Cortex Hormones; Child; Child, Preschool; Consensus; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Humans; Italy; Male; Nephrotic Syndrome; Practice Guidelines as Topic; Prognosis; Recurrence; Retreatment; Societies, Medical; Survival Rate; Treatment Outcome

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

Long-Term Survival After Hematopoietic Stem Cell Transplantation for Complete STAT1 Deficiency. - Naviglio, Samuele; Soncini, Elena; Vairo, Donatella; Lanfranchi, Arnalda; Badolato, Raffaele; Porta, Fulvio (J Clin Immunol, 2017)
PURPOSE: Complete signal transducer and activator of transcription 1 (STAT1) deficiency is a rare autosomal recessive condition characterized by impairment of intracellular signaling from both type I and type II interferons (IFN). Affected patients are prone to early severe mycobacterial and viral infections, which usually result in death before 18 months of age. We previously reported a patient affected by complete STAT1 deficiency who underwent hematopoietic stem cell transplantation (HSCT). Here, we describe the transplantation procedures and long-term outcomes. METHODS: The patient, who had suffered multiple life-threatening mycobacterial and viral infections in the first years of life, underwent HSCT at 4 years of age from a partially matched (HLA compatibility 8/10) unrelated donor after a myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and anti-thymocyte globulin. RESULTS: Hematological reconstitution was detected at d+15, with full donor engraftment demonstrated by molecular analysis of leukocytes. Several complications occurred in the post-transplantation phase, including acute graft versus host disease, posterior reversible encephalopathy, thrombotic thrombocytopenic purpura, bilateral keratoconjunctivitis with complete loss of vision, and chronic lower limb lymphedema. Analysis of STAT1 in CD3 cells at 90 and 120 days after HSCT by flow cytometry showed normal STAT1 phosphorylation levels in response to IFN-α. CONCLUSIONS: Notably, no severe infections occurred after discharge (day + 90) during a 9-year follow-up, suggesting that normal response to IFNs in hematopoietic cells is sufficient to provide protection in humans.
Keywords: Child, Preschool; Hematopoietic Stem Cell Transplantation; Humans; Immunologic Deficiency Syndromes; Male; STAT1 Transcription Factor; Treatment Outcome

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Is middle cerebral artery Doppler related to neonatal and 2-year infant outcome in early fetal growth restriction? - Stampalija, Tamara; Arabin, Birgit; Wolf, Hans; Bilardo, Caterina M; Lees, Christoph (Am J Obstet Gynecol, 2017)
BACKGROUND: Reduced fetal middle cerebral artery Doppler impedance is associated with hypoxemia in fetal growth restriction. It remains unclear as to whether this finding could be useful in timing delivery, especially in the third trimester. In this regard there is a paucity of evidence from prospective studies. OBJECTIVES: The aim of this study was to determine whether there is an association between middle cerebral artery Doppler impedance and its ratio with the umbilical artery in relation to neonatal and 2 year infant outcome in early fetal growth restriction (26-31 weeks of gestation). Additionally we sought to explore which ratio is more informative for clinical use. STUDY DESIGN: This is a secondary analysis from the Trial of Randomized Umbilical and Fetal Flow in Europe, a prospective, multicenter, randomized management study on different antenatal monitoring strategies (ductus venosus Doppler changes and computerized cardiotocography short-term variation) in fetal growth restriction diagnosed between 26 and 31 weeks. We analyzed women with middle cerebral artery Doppler measurement at study entry and within 1 week before delivery and with complete postnatal follow-up (374 of 503). The primary outcome was survival without neurodevelopmental impairment at 2 years corrected for prematurity. Neonatal outcome was defined as survival until first discharge home without severe neonatal morbidity. Z-scores were calculated for middle cerebral artery pulsatility index and both umbilicocerebral and cerebroplacental ratios. Odds ratios of Doppler parameter Z-scores for neonatal and 2 year infant outcome were calculated by multivariable logistic regression analysis adjusted for gestational age and birthweight p50 ratio. RESULTS: Higher middle cerebral artery pulsatility index at inclusion but not within 1 week before delivery was associated with neonatal survival without severe morbidity (odds ratio, 1.24; 95% confidence interval, 1.02-1.52). Middle cerebral artery pulsatility index Z-score and umbilicocerebral ratio Z-score at inclusion were associated with 2 year survival with normal neurodevelopmental outcome (odds ratio, 1.33; 95% confidence interval, 1.03-1.72, and odds ratio, 0.88; 95% confidence interval, 0.78-0.99, respectively) as were gestation at delivery and birthweight p50 ratio (odds ratio, 1.41; 95% confidence interval, 1.20-1.66, and odds ratio, 1.86; 95% confidence interval, 1.33-2.60, respectively). When comparing cerebroplacental ratio against umbilicocerebral ratio, the incremental range of the cerebroplacental ratio tended toward zero, whereas the umbilicocerebral ratio tended toward infinity as the values became more abnormal. CONCLUSION: In a monitoring protocol based on ductus venosus and cardiotocography in early fetal growth restriction (26-31 weeks of gestation), the impact of middle cerebral artery Doppler and its ratios on outcome is modest and less marked than birthweight and delivery gestation. It is unlikely that middle cerebral artery Doppler and its ratios are informative in optimizing the timing of delivery in fetal growth restriction before 32 weeks of gestation. The umbilicocerebral ratio allows for a better differentiation in the abnormal range than the cerebroplacental ratio.
Keywords: Birth Weight; Child Development; Child, Preschool; Delivery, Obstetric; Female; Fetal Growth Retardation; Gestational Age; Humans; Middle Cerebral Artery; Pregnancy; Prospective Studies; Pulsatile Flow; Ultrasonography, Doppler; Ultrasonography, Prenatal; Umbilical Arteries

Neuroimaging Changes in Menkes Disease, Part 1. - Manara, R; D'Agata, L; Rocco, M C; Cusmai, R; Freri, E; Pinelli, L; Darra, F; Procopio, E; Mardari, R; Zanus, C; Di Rosa, G; Soddu, C; et al. (AJNR Am J Neuroradiol, 2017)
Menkes disease is a rare multisystem X-linked disorder of copper metabolism. Despite an early, severe, and progressive neurologic involvement, our knowledge of brain involvement remains unsatisfactory. The first part of this retrospective and review MR imaging study aims to define the frequency rate, timing, imaging features, and evolution of intracranial vascular and white matter changes. According to our analysis, striking but also poorly evolutive vascular abnormalities characterize the very early phases of disease. After the first months, myelination delay becomes evident, often in association with protean focal white matter lesions, some of which reveal an age-specific brain vulnerability. In later phases of the disease, concomitant progressive neurodegeneration might hinder the myelination progression. The currently enriched knowledge of neuroradiologic finding evolution provides valuable clues for early diagnosis, identifies possible MR imaging biomarkers of new treatment efficacy, and improves our comprehension of possible mechanisms of brain injury in Menkes disease.
Keywords: Brain; Disease Progression; Female; Humans; Magnetic Resonance Imaging; Male; Menkes Kinky Hair Syndrome; Neuroimaging; Retrospective Studies; White Matter

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

A Novel Panel of Serum Biomarkers for MPM Diagnosis. - Bonotti, A; Foddis, R; Landi, S; Melaiu, O; De Santi, C; Giusti, L; Donadio, E; Ciregia, F; Mazzoni, M R; Lucacchini, A; Bovenzi, M; Comar, M; et al. (Dis Markers, 2017)
Exposure to asbestos is the main cause of malignant pleural mesothelioma (MPM), a highly aggressive cancer of the pleura. Since the only tools for early detection are based on radiological tests, some authors focused on serum markers (i.e., mesothelin). The aim of this study was the evaluation of new serum biomarkers to be used individually or in combination, in order to improve the outcome of patients whose disease would be diagnosed at an earlier stage. Serum and plasma were available from 43 subjects previously exposed to asbestos and 27 MPM patients, all being epithelioid type. All the new markers found differentially expressed in MPM and healthy subjects, by proteomic and genomic approaches, have been validated in the serum by the use of specific ELISA. The combined approach, using tools of genomics and proteomics, is found to be highly innovative for this type of disease and led to the identification of new serum markers in the diagnosis of MPM. These results, if confirmed in a larger series, may have a strong impact in this area, because early detection of this cancer in people at high risk could significantly improve the course of the disease and the clinical approach to an individualized therapy.
Keywords: Aged; Biomarkers, Tumor; Blood Proteins; Case-Control Studies; Female; Humans; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Proteome

Polymorphisms in key bone modulator cytokines genes influence bisphosphonates therapy in postmenopausal women. - Lima, C A D; Javorski, N R; Souza, A P O; Barbosa, A D; Valença, A P M C; Crovella, S; Souza, P R E; de Azevêdo Silva, J; Sandrin-Garcia, P (Inflammopharmacology, 2017)
Osteoporosis is a multifactorial and debilitating disease resulting from decreased bone mineral density (BMD) and loss of tissue microarchitecture. Ineffective therapies may lead to bone fractures and subsequent death. Single nucleotide polymorphisms (SNPs) in key immune regulator genes have been associated with therapeutic response to bisphosphonates, which are the first therapeutic line of choice for osteoporosis. However, cytokine pathways and their relation with therapeutic adhesion remain to be fully elucidated. Aimed at better understanding these processes, we investigated the response to bisphosphonate therapy in postmenopausal women and four SNPs in key proinflammatory cytokines genes: IL23R +2284 (C>A) (rs10889677), IL17A +672 (G>A) (rs7747909), IL12B +1188 (T>G) (rs3212227) and INF-γ -1616 (G>A) (rs2069705). A total of 69 patients treated with bisphosphonate were followed for a period of 1 up to 4 years, genotyped and compared according to their changes in bone mineral density (BMD) and level of biochemical markers during their treatment. The INF-γ -1616 G/G associated with increased BMD values in femoral neck (GG/AA, p = 0.016) and decreased BMD values in total hip (GG/GA, p = 0.019; GG/AA, p = 0.011). In relation to biochemical markers, INF-γ -1616 SNP associated with increased alkaline phosphatase (GG/AA; p < 0.0001) and parathyroid hormone levels (AA/GA; p = 0.017). Vitamin D values changes were related to IL17A +672 (GG/GA, p = 0.034) and to IL12B +1188 (TT/TG, p = 0.046) SNPs. Besides, significant differences in changes of calcium levels correlated with IL23R +2284 (CC/CA, p = 0.016) genotypes. Altogether, we suggest that these polymorphisms may play an important role for therapeutic decisions in osteoporosis treatment.
Keywords: Aged; Bone Density; Bone Remodeling; Cytokines; Diphosphonates; Female; Humans; Middle Aged; Osteoporosis, Postmenopausal; Polymorphism, Single Nucleotide; Postmenopause

Pregnant with HIV before age 25: data from a large national study in Italy, 2001-2016. - Floridia, M; Masuelli, G; Tamburrini, E; Cetin, I; Liuzzi, G; Martinelli, P; Guaraldi, G; Spinillo, A; Vimercati, A; Maso, G; Pinnetti, C; Frisina, V; et al. (Epidemiol Infect, 2017)
Young pregnant women with HIV may be at significant risk of unplanned pregnancy, lower treatment coverage, and other adverse pregnancy outcomes. In a large cohort of pregnant women with HIV in Italy, among 2979 pregnancies followed in 2001-2016, 9·0% were in women <25 years, with a significant increase over time (2001-2005: 7·0%; 2006-2010: 9·1%; 2011-2016: 12·2%, P < 0·001). Younger women had a lower rate of planned pregnancy (23·2% vs. 37·7%, odds ratio (OR) 0·50, 95% confidence interval (CI) 0·36-0·69), were more frequently diagnosed with HIV in pregnancy (46·5% vs. 20·9%, OR 3·29, 95% CI 2·54-4·25), and, if already diagnosed with HIV before pregnancy, were less frequently on antiretroviral treatment at conception (<25 years: 56·3%; ⩾25 years: 69·0%, OR 0·58, 95% CI 0·41-0·81). During pregnancy, treatment coverage was almost universal in both age groups (98·5% vs. 99·3%), with no differences in rate of HIV viral suppression at third trimester and adverse pregnancy outcomes. The data show that young women represent a growing proportion of pregnant women with HIV, and are significantly more likely to have unplanned pregnancy, undiagnosed HIV infection, and lower treatment coverage at conception. During pregnancy, antiretroviral treatment, HIV suppression, and pregnancy outcomes are similar compared with older women. Earlier intervention strategies may provide additional benefits in the quality of care for women with HIV.
Keywords: Adolescent; Cohort Studies; Female; HIV Infections; Humans; Italy; Odds Ratio; Pregnancy; Young Adult

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rate, correlates and outcomes of repeat pregnancy in HIV-infected women. - Floridia, M; Tamburrini, E; Masuelli, G; Martinelli, P; Spinillo, A; Liuzzi, G; Vimercati, A; Alberico, S; Maccabruni, A; Pinnetti, C; Frisina, V; Dalzero, S; et al. (HIV Med, 2017)
OBJECTIVES: The aim of the study was to assess the rate, determinants, and outcomes of repeat pregnancies in women with HIV infection. METHODS: Data from a national study of pregnant women with HIV infection were used. Main outcomes were preterm delivery, low birth weight, CD4 cell count and HIV plasma viral load. RESULTS: The rate of repeat pregnancy among 3007 women was 16.2%. Women with a repeat pregnancy were on average younger than those with a single pregnancy (median age 30 vs. 33 years, respectively), more recently diagnosed with HIV infection (median time since diagnosis 25 vs. 51 months, respectively), and more frequently of foreign origin [odds ratio (OR) 1.36; 95% confidence interval (CI) 1.10-1.68], diagnosed with HIV infection in the current pregnancy (OR: 1.69; 95% CI: 1.35-2.11), and at their first pregnancy (OR: 1.33; 95% CI: 1.06-1.66). In women with sequential pregnancies, compared with the first pregnancy, several outcomes showed a significant improvement in the second pregnancy, with a higher rate of antiretroviral treatment at conception (39.0 vs. 65.4%, respectively), better median maternal weight at the start of pregnancy (60 vs. 61 kg, respectively), a higher rate of end-of-pregnancy undetectable HIV RNA (60.7 vs. 71.6%, respectively), a higher median birth weight (2815 vs. 2885 g, respectively), lower rates of preterm delivery (23.0 vs. 17.7%, respectively) and of low birth weight (23.4 vs. 15.4%, respectively), and a higher median CD4 cell count (+47 cells/μL), with almost no clinical progression to Centers for Disease Control and Prevention stage C (CDC-C) HIV disease (0.3%). The second pregnancy was significantly more likely to end in voluntary termination than the first pregnancy (11.4 vs. 6.1%, respectively). CONCLUSIONS: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Emigrants and Immigrants; Female; HIV Infections; HIV-1; Humans; Infant, Low Birth Weight; Pregnancy; Premature Birth; Viral Load

Surgery for distal hypospadias: what about the catheter? - Scarpa, Maria-Grazia; Perin, Giordano; Di Grazia, Massimo; Codrich, Daniela; Pederiva, Federica; Guida, Edoardo; Lembo, Maria Antonietta; Giannotta, Antonio; Schleef, Jurgen (Pediatr Med Chir, 2017)
No agreed recommendations exist for timing of urethral stent removal, after distal hypospadias surgery. We compared our preliminary case series with outcomes from literature: 18/44 patients were treated with catheter and 26/44 without it. The surgical outcome was comparable in the two groups. After hypospadias surgery, the main advantage of the immediate postoperative catheter removal was the shorter hospital stay without negatively affecting the care and home management.
Keywords: Child; Child, Preschool; Device Removal; Humans; Hypospadias; Infant; Length of Stay; Male; Retrospective Studies; Stents; Treatment Outcome; Urinary Catheterization

Synthesis of Lipophilic Core-Shell FeO@SiO@Au Nanoparticles and Polymeric Entrapment into Nanomicelles: A Novel Nanosystem for in Vivo Active Targeting and Magnetic Resonance-Photoacoustic Dual Imaging. - Monaco, Ilaria; Arena, Francesca; Biffi, Stefania; Locatelli, Erica; Bortot, Barbara; La Cava, Francesca; Marini, Giada Maria; Severini, Giovanni Maria; Terreno, Enzo; Comes Franchini, Mauro (Bioconjug Chem, 2017)
In this work, iron/silica/gold core-shell nanoparticles (FeO@SiO@Au NPs) characterized by magnetic and optical properties have been synthesized to obtain a promising theranostic platform. To improve their biocompatibility, the obtained multilayer nanoparticles have been entrapped in polymeric micelles, decorated with folic acid moieties, and tested in vivo for photoacoustic and magnetic resonance imaging detection of ovarian cancer.
Keywords: Animals; Cell Proliferation; Female; Ferric Compounds; Folic Acid; Gold; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Magnetite Nanoparticles; Mice; Mice, Inbred BALB C; Mice, Nude; Micelles; Multimodal Imaging; Ovarian Neoplasms; Photoacoustic Techniques; Polymers; Silicon Dioxide; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

Targeted sequencing identifies novel variants involved in autosomal recessive hereditary hearing loss in Qatari families. - Alkowari, Moza K; Vozzi, Diego; Bhagat, Shruti; Krishnamoorthy, Navaneethakrishnan; Morgan, Anna; Hayder, Yousra; Logendra, Barathy; Najjar, Nehal; Gandin, Ilaria; Gasparini, Paolo; Badii, Ramin; Girotto, Giorgia; et al. (Mutat Res, 2017)
Hereditary hearing loss is characterized by a very high genetic heterogeneity. In the Qatari population the role of GJB2, the worldwide HHL major player, seems to be quite limited compared to Caucasian populations. In this study we analysed 18 Qatari families affected by non-syndromic hearing loss using a targeted sequencing approach that allowed us to analyse 81 genes simultaneously. Thanks to this approach, 50% of these families (9 out of 18) resulted positive for the presence of likely causative alleles in 6 different genes: CDH23, MYO6, GJB6, OTOF, TMC1 and OTOA. In particular, 4 novel alleles were detected while the remaining ones were already described to be associated to HHL in other ethnic groups. Molecular modelling has been used to further investigate the role of novel alleles identified in CDH23 and TMC1 genes demonstrating their crucial role in Ca2+ binding and therefore possible functional role in proteins. Present study showed that an accurate molecular diagnosis based on next generation sequencing technologies might largely improve molecular diagnostics outcome leading to benefits for both genetic counseling and definition of recurrence risk.
Keywords: Adolescent; Alleles; Cadherins; Child; Child, Preschool; Connexins; Female; GPI-Linked Proteins; Hearing Loss, Sensorineural; Humans; Infant; Male; Membrane Proteins; Models, Molecular; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Qatar; Sequence Analysis, DNA

Thrombogenesis in Thrombophilic Pregnancy: Evaluation of Low-Molecular-Weight Heparin Prophylaxis. - Simeone, Roberto; Giacomello, Roberta; Bruno, Germano; Parco, Sergio; Maximova, Natalia; Martinelli, Monica; Zito, Gabriella; Luppi, Stefania; Cervi, Gina; Ricci, Giuseppe (Acta Haematol, 2017)
The aim of this study is to investigate thrombogenesis and the hypercoagulable changes in pregnant women affected by thrombophilia who received low-molecular-weight heparin (LWMH) prophylaxis. We included 21 pregnant women affected by thrombophilia treated with LWMH and 20 nontreated normal pregnant women as the control group. The sample group of thrombophilic pregnant women included different conditions (factor V Leiden mutation, protein C deficiency, protein S deficiency, antiphospholipid antibodies syndrome, and combined defects). Three blood samples were collected during pregnancy (i.e., at 16, 20, and 24 weeks) and tested for activated partial thromboplastin time and prothrombin fragment F1 + 2 (F1 + 2); anti-FXa activity was tested only in treated thrombophilic pregnant women. F1 + 2 levels progressively increased during pregnancy in both study groups. However, the F1 + 2 increase in women exposed to heparin prophylaxis was significantly lower than that in normal pregnant women in all 3 measurements carried out during gestation (p < 0.05); a statistically significant inverse correlation between F1 + 2 levels and anti-Xa activity (R = -0.8575, p < 0.05) was observed in treated women during pregnancy. Our findings suggest that F1 + 2 in addition to anti-Xa measurement could be used to adjust LWMH prophylaxis, at least in high-risk pregnant women.
Keywords: Adult; Anticoagulants; Case-Control Studies; Factor Xa Inhibitors; Female; Heparin, Low-Molecular-Weight; Humans; Nadroparin; Partial Thromboplastin Time; Peptide Fragments; Pilot Projects; Pregnancy; Pregnancy Complications, Hematologic; Prothrombin; Thrombophilia; Thrombosis

Towards measles elimination in Italy: Virological surveillance and genotypes trend (2013-2015). - Magurano, Fabio; Baggieri, Melissa; Filia, Antonietta; Del Manso, Martina; Lazzarotto, Tiziana; Amendola, Antonella; D'Agaro, Pierlanfranco; Chironna, Maria; Ansaldi, Filippo; Iannazzo, Stefania; Bucci, Paola; Marchi, Antonella; et al. (Virus Res, 2017)
In accordance with the goal of the World Health Organization Regional Office for Europe, the Italian National Measles and Rubella Elimination Plan aimed to interrupt indigenous measles transmission in Italy by the end of 2015. However, from 2013 to 2015, Italy experienced high measles burden with 4902 measles cases (49.3% laboratory-confirmed) reported to the enhanced measles surveillance system (cumulative incidence in the triennium reference period: 2.4/100,000 population). The measles elimination goal was not reached. Laboratory surveillance of measles circulating genotypes is performed by the Measles and Rubella National Reference Laboratory (NRL) at the Italian National Institute of Health (Istituto Superiore di Sanità - ISS), in Rome. Samples received from 1 January 2013-31 December 2015 were analysed. Those positive for measles genome by molecular tests were sequenced and phylogenetically analysed. Phylogenetic analysis performed by NRL identified that genotypes D4 and D8 were endemic and co-circulated in 2011-2013: study results show that genotype D4 disappeared during 2013. Sporadic cases were associated to genotype B3 during 2011-2013, which became endemic in Italy during 2014 and co-circulated with D8 until 2015. Sporadic cases were found belonging to genotypes D9 and H1 all over the period in exam. Similar trend has been observed in European WHO Region.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Disease Outbreaks; Female; Genotype; Humans; Infant; Italy; Male; Measles; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny; RNA, Viral; Sentinel Surveillance; Young Adult

Training in Occupational Medicine: Jurisprudential Malfunctions in the Italian System and European Perspectives. - Cegolon, L; Heymann, W C; Xodo, C; Lange, J H (Ann Ig, 2017)
BACKGROUND: To practice occupational health in Europe, a medical doctor must qualify in occupational medicine. This requires a period of postgraduate specialist medical training lasting a minimum of four years, in conformity with European regulations, to obtain a certificate of completion of training which is then mutually recognized within the entire European Union. DISCUSSION: In 2002 an Italian law allowed doctors specialized in public health medicine and legal/forensic medicine to also practice as consultants in occupational medicine in the country. However a subsequent law in 2008 determined that only physicians specialized in occupational medicine could freely practice as consultants in this discipline. The other two categories (consultants in public health medicine and consultants in legal/forensic medicine) were required to undertake additional training (a Master course) to qualify as consultants in occupational medicine. CONCLUSIONS: Doctors who entered postgraduate training in public health or legal/forensic medicine before 2008, with the option to practice also as consultants in occupational medicine upon completion of their training, suffered an unprecedented and legally questionable retroactive application of this new law which stripped them of previously acquired rights. Moreover, even after qualifying by undertaking this extra training in occupational medicine, the latter two categories of doctors do not have their training recognized in other member states of the European Union. To disallow the rights of doctors qualified in occupational medicine to work as consultants in the latter medical discipline elsewhere within the European Union seems a clear violation of professional rights and, as such, legal action could be taken to submit this issue to European attention.
Keywords: Certification; European Union; Italy; Occupational Medicine

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Action of methotrexate and tofacitinib on directly stimulated and bystander-activated lymphocytes. - Piscianz, Elisa; Candilera, Vanessa; Valencic, Erica; Loganes, Claudia; Paron, Greta; De Iudicibus, Sara; Decorti, Giuliana; Tommasini, Alberto (Mol Med Rep, 2016)
Chronic inflammation associated with autoimmune activation is characteristic of rheumatic diseases from childhood to adulthood. In recent decades, significant improvements in the treatment of these types of disease have been achieved using disease modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) and, more recently, using biologic inhibitors. The recent introduction of kinase inhibitors (for example, tofacitinib; Tofa) further increases the available ARDs. However, there are patients that do not respond to any treatment strategies, for whom combination therapies are proposed. The data regarding the combined action of different drugs is lacking and the knowledge of the mechanisms of ARDs and their actions upon pathogenic lymphocytes, which are hypothesized to sustain disease, is poor. An in vitro model of inflammation was developed in the current study, in which stimulated and unstimulated lymphocytes were cultured together, but tracked separately, to investigate the action of MTX and Tofa on the two populations. By analysing lymphocyte proliferation and activation, and cytokine secretion in the culture supernatants, it was established that, due to the presence of activated cells, unstimulated cells underwent a bystander activation that was modulated by the ARDs. Additionally, varying administration schedules were demonstrated to affect lymphocytes differently in vitro, either directly or via bystander activation. Furthermore, MTX and Tofa exerted different effects; while MTX showed an antiproliferative effect, Tofa marginally effected activation, although only a slight antiproliferative action, which could be potentiated by sequential treatment with MTX. Thus, it was hypothesized that these differences may be exploited in sequential therapeutic strategies, to maximize the anti‑rheumatic effect. These findings are notable and must be accounted for, as bystander‑activated cells in vivo could contribute to the spread of autoimmune activation and disease progression.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

Association between p21 Ser31Arg polymorphism and the development of cervical lesion in women infected with high risk HPV. - Lima, Géssica; Santos, Erinaldo; Angelo, Hildson; Oliveira, Micheline; Heráclio, Sandra; Leite, Fernanda; de Melo, Celso; Crovella, Sergio; Maia, Maria; Souza, Paulo (Tumour Biol, 2016)
Infection by high-risk human papillomavirus (HR-HPV) and single nucleotide polymorphism (SNP) in genes involved in cell cycle control, as p21 and p27, are important factors in the development of different types of human cancers. This study aims at investigating whether both the p21 Ser31Arg and p27 V109G polymorphisms are associated with susceptibility to the development of cervical lesions in women HR-HPV positive. We analyzed 132 women HPV positive and with cervical lesions or CC and 154 healthy control (HPV negative and without cervical lesions). p21 Ser31Arg and p27 V109G polymorphisms were analyzed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and sequencing. The p21 31Arg allele was associated with susceptibility for the development of cervical lesions (P* = 0.0009), while p27 V109G polymorphism showed no significant differences for this association (P* = 0.89). However, the combined effect of the polymorphisms showed that the presence of the CC genotype (SNP p21 Ser31Arg) conferred protection for the development of cervical lesions (OR = 0.39). p21 Ser31Arg and p27 V109G polymorphisms were not associated with the grade of cervical lesions (CINI, CINII, and CINIII) or CC (P* > 0.05). The HR-HPV more frequent in this study were of 16 (57.6 %) and 18 (37.1 %) types; however, no association was observed when both polymorphisms and risk factors analyzed were compared (P* > 0.05). Our findings suggest a possible association between p21 Ser31tabArg polymorphism and susceptibility to the development of cervical lesions in women from Pernambuco. Brazil.

Association of the HLA-G 3'UTR polymorphisms with colorectal cancer in Italy: a first insight. - Garziera, M; Catamo, E; Crovella, S; Montico, M; Cecchin, E; Lonardi, S; Mini, E; Nobili, S; Romanato, L; Toffoli, G (Int J Immunogenet, 2016)
This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA-G 3'UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three-hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14-bp INDEL, +3196 C>G SNPs and UTR-2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR-4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA-G 3'UTR and colorectal cancer susceptibility.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

Carbamazepine-induced thrombocytopenic purpura in a child: Insights from a genomic analysis. - Abate, Maria Valentina; Stocco, Gabriele; Devescovi, Raffaella; Carrozzi, Marco; Pierobon, Chiara; Valencic, Erica; Lucafò, Marianna; Di Silvestre, Alessia; d'Adamo, Pio; Tommasini, Alberto; Decorti, Giuliana; Ventura, Alessandro (Blood Cells Mol Dis, 2016)

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

Clinical Characteristics of Patients Carrying the Q703K Variant of the NLRP3 Gene: A 10-year Multicentric National Study. - Naselli, Aldo; Penco, Federica; Cantarini, Luca; Insalaco, Antonella; Alessio, Mariolina; Tommasini, Alberto; Maggio, Cristina; Obici, Laura; Gallizi, Romina; Cimmino, Marco; Signa, Sara; Lucherini, Orso Maria; et al. (J Rheumatol, 2016)
OBJECTIVE: The aim of our study was to analyze the clinical and functional effect of the p.Q703K (p. Q705K, c. 2107C>A) variant of the NLRP3 gene in a population of patients screened for suspected cryopyrin-associated periodic syndrome (CAPS). METHODS: Since 2002, 580 patients underwent molecular analysis for NLRP3. Data on clinical presentation, response to treatment, and longterm followup were collected using a uniform questionnaire. The pattern of cytokine secretion after lipopolysaccharide stimulation from isolated monocytes was analyzed in 3 patients carrying the p.Q703K variant and 1 patient with a chronic infantile neurologic, cutaneous, articular syndrome phenotype carrying both the p.M406I and p.Q703K, and compared with 7 patients with CAPS with sure pathogenic variants and 6 healthy controls. RESULTS: The p.Q703K variant was found in 57 screened patients with an overall allelic frequency of 5%. The frequency in normal controls was 5.5%. Clinical data at the moment of molecular analysis and at followup were available in 36 patients. Two patients displayed additional mutations of NLRP3. The mean followup was 2.5 years. Thirteen patients (39%) had a final diagnosis different from the original suspicion of CAPS. The remaining 21 patients displayed a mild phenotype mainly characterized by recurrent episodes of urticarial rash and arthralgia. Only 8 patients were treated with anti-interleukin (IL)-1 treatment, with a complete response in 5 patients. The pattern of secretion of IL-1β and other cytokines (IL-6 and IL-1 receptor antagonist) in patients did not display the aberrancies observed in patients with CAPS and was similar to that observed in healthy controls. CONCLUSION: The present study confirms the weak clinical and functional effect of the p.Q703K variant.

Clinical Spectrum of PRKAG2 Syndrome. - Porto, Andrea Giuseppe; Brun, Francesca; Severini, Giovanni Maria; Losurdo, Pasquale; Fabris, Enrico; Taylor, Matthew R G; Mestroni, Luisa; Sinagra, Gianfranco (Circ Arrhythm Electrophysiol, 2016)
Keywords: AMP-Activated Protein Kinases; DNA; Heart Conduction System; Humans; Mutation; Wolff-Parkinson-White Syndrome

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

Decline in Lung Function in Childhood Asthma. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (N Engl J Med, 2016)
Keywords: Anti-Inflammatory Agents; Asthma; Female; Humans; Lung; Male

Differential expression of GAS5 in rapamycin-induced reversion of glucocorticoid resistance. - Lucafò, Marianna; Bravin, Vanessa; Tommasini, Alberto; Martelossi, Stefano; Rabach, Ingrid; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Clin Exp Pharmacol Physiol, 2016)
This study evaluates the association between the long noncoding RNA GAS5 levels and the anti-proliferative effect of the glucocorticoid (GC) methylprednisolone (MP) alone and in combination with rapamycin in peripheral blood mononuclear cells (PBMCs) obtained from healthy donors. The effect of MP, rapamycin, and MP plus rapamycin was determined in 17 healthy donors by labelling metabolically active cells with [methyl-3H] thymidine and the expression levels of GAS5 gene were evaluated by real-time RT-PCR TaqMan analysis. We confirmed a role for GAS5 in modulating GC response: poor responders presented higher levels of GAS5 in comparison with good responders. Interestingly, when PBMCs were treated with the combination of rapamycin plus MP, the high levels of GAS5 observed for each drug in the MP poor responders group decreased in comparison with rapamycin (P value = 0.0134) or MP alone (P value = 0.0193). GAS5 is involved in GC resistance and co-treatment of rapamycin with GCs restores GC effectiveness in poor responders through the downregulation of the long noncoding RNA. GAS5 could be considered a biomarker to personalize therapy and a novel therapeutic target useful for the development of new pharmacological approaches to restore GC sensitivity.

Dyslipidemia, Diet, and Physical Exercise in Children on Treatment with Anti-Retroviral Medication in El Salvador: A Cross-Sectional Study. - Sonego, Michela; Sagrado, Maria José; Escobar, Gustavo; Lazzerini, Marzia; Rivas, Estefanie; Martín-Cañavate, Rocio; de López, Elsy Pérez; Ayala, Sandra; Castaneda, Luis; Aparicio, Pilar; Custodio, Estefanía (Pediatr Infect Dis J, 2016)
BACKGROUND: Dyslipidemias are common in HIV-infected children, especially if treated with protease-inhibitors, but there are few data on how to treat dyslipidemias in this population. We estimated the dislypidemia prevalence and its association with treatment, diet, and physical exercise in children on anti-retroviral treatment at the El Salvador reference center for pediatric HIV care (CENID). METHODS: Information was gathered regarding socio-demographic characteristics, treatment, diet, and physical activity of 173 children aged 5-18 years and receiving anti-retroviral therapy.Triglycerides, total cholesterol, low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), viral load, and CD4 T-lymphocytes were measured. Abnormal concentrations were defined as triglycerides ≥130 mg/dl in 10- to 18-year-olds and ≥100 mg/dl in <10 year-olds; total cholesterol ≥200 mg/dl; LDL-C ≥130 mg/dl; and HDL-C ≤35 mg/dl.We adjusted four different multivariate models to assess the independent association of each type of dyslipidemia with protease-inhibitors, diet, and physical exercise. RESULTS: Of the 173 children, 83 (48%) had hypertriglyceridemia and 25 (14.5%) hypercholesterolemia. High LDL-C concentrations were observed in 17 children (9.8%) and low HDL-C in 38 (22%). Treatment with protease-inhibitors was significantly associated with hypertriglyceridemia (Prevalence Ratio (PR) 2.8; 95%CI 2.0-3.8) and hypercholesterolemia (PR 9.0; 95%CI 3.6-22.2).Higher adherence to a "high fat/sugar diet" was associated with hypercholesterolemia (PR 1.6; 95%CI 1.1-2.3) and high LDL-C (PR 1.7; 95%CI 1.0-2.9).Compared with those exercising <3 times/week, children exercising ≥7 times were less likely to have low HDL-C (PR=0.4; 95%CI 0.2-0.7). CONCLUSIONS: These results suggest that a healthy diet and exercise habits can contribute to controlling some aspects of the lipid profile in this population.

Efficacy of ketamine in refractory convulsive status epilepticus in children: a protocol for a sequential design, multicentre, randomised, controlled, open-label, non-profit trial (KETASER01). - Rosati, Anna; Ilvento, Lucrezia; L'Erario, Manuela; De Masi, Salvatore; Biggeri, Annibale; Fabbro, Giancarlo; Bianchi, Roberto; Stoppa, Francesca; Fusco, Lucia; Pulitanò, Silvia; Battaglia, Domenica; Pettenazzo, Andrea; et al. (BMJ Open, 2016)
INTRODUCTION: Status epilepticus (SE) is a life-threatening neurological emergency. SE lasting longer than 120 min and not responding to first-line and second-line antiepileptic drugs is defined as 'refractory' (RCSE) and requires intensive care unit treatment. There is currently neither evidence nor consensus to guide either the optimal choice of therapy or treatment goals for RCSE, which is generally treated with coma induction using conventional anaesthetics (high dose midazolam, thiopental and/or propofol). Increasing evidence indicates that ketamine (KE), a strong N-methyl-d-aspartate glutamate receptor antagonist, may be effective in treating RCSE. We hypothesised that intravenous KE is more efficacious and safer than conventional anaesthetics in treating RCSE. METHODS AND ANALYSIS: A multicentre, randomised, controlled, open-label, non-profit, sequentially designed study will be conducted to assess the efficacy of KE compared with conventional anaesthetics in the treatment of RCSE in children. 10 Italian centres/hospitals are involved in enrolling 57 patients aged 1 month to 18 years with RCSE. Primary outcome is the resolution of SE up to 24 hours after withdrawal of therapy and is updated for each patient treated according to the sequential method. ETHICS AND DISSEMINATION: The study received ethical approval from the Tuscan Paediatric Ethics Committee (12/2015). The results of this study will be published in peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NCT02431663; Pre-results.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

Hand-held computers can help to distract children undergoing painful venipuncture procedures. - Crevatin, Franca; Cozzi, Giorgio; Braido, Elena; Bertossa, Gabriella; Rizzitelli, Patrizia; Lionetti, Daniela; Matassi, Daniela; Calusa, Dorotea; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2016)
AIM: Needle-related procedures can be painful for children, and distraction provides ideal pain relief in blood-drawing centres. This study assessed the effectiveness of playing a computer game during venipuncture, compared with low-tech distraction by a nurse. METHODS: We conducted this prospective, randomised controlled trial at the blood-drawing centre of a tertiary-level children's hospital in Italy. Half of the 200 children played Angry Birds on a hand-held computer while the other half were distracted by a second, specifically trained nurse who sang to them, read a book, blew bubbles or played with puppets. Pain was measured using a faces pain scale for children aged 4-7 years and a numeric scale for children aged 8-13 years. RESULTS: The 200 children had a median age of eight years. Children reported significant pain in 16 cases (16%) in the hand-held computer distraction group and in 15 cases (15%) in the nurse-led low-tech distraction group (p = 0.85). The procedural success rate at the first attempt was not different in the two groups. CONCLUSION: Playing a game on a hand-held computer meant that only one in six children reported pain during venipuncture, but it was not superior to being distracted by nurses.

Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.

Improving regional universal newborn hearing screening programmes in Italy. - Molini, E; Cristi, M C; Lapenna, R; Calzolaro, L; Muzzi, E; Ciciriello, E; Della Volpe, A; Orzan, E; Ricci, G (Acta Otorhinolaryngol Ital, 2016)
The Universal Newborn Hearing Screening (UNHS) programme aims at achieving early detection of hearing impairment. Subsequent diagnosis and intervention should follow promptly. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for early Identification, Intervention and Care of Hearing Impaired Children", the limitations and strengths of current UNHS programs in Italy have been analysed by a group of professionals working in tertiary centres involved in regional UNHS programmes, using SWOT analysis and a subsequent TOWS matrix. Coverage and lost-to-follow up rates are issues related to UNHS programmes. Recommendations to improve the effectiveness of the UNHS programme have been identified. The need for homogeneous policies, high-quality information and dissemination of knowledge for operators and families of hearing-impaired children emerged from the discussion.

Mortality and its risk factors in Malawian children admitted to hospital with clinical pneumonia, 2001-12: a retrospective observational study. - Lazzerini, Marzia; Seward, Nadine; Lufesi, Norman; Banda, Rosina; Sinyeka, Sophie; Masache, Gibson; Nambiar, Bejoy; Makwenda, Charles; Costello, Anthony; McCollum, Eric D; Colbourn, Tim (Lancet Glob Health, 2016)
BACKGROUND: Few studies have reported long-term data on mortality rates for children admitted to hospital with pneumonia in Africa. We examined trends in case fatality rates for all-cause clinical pneumonia and its risk factors in Malawian children between 2001 and 2012. METHODS: Individual patient data for children (<5 years) with clinical pneumonia who were admitted to hospitals participating in Malawi's Child Lung Health Programme between 2001 and 2012 were recorded prospectively on a standardised medical form. We analysed trends in pneumonia mortality and children's clinical characteristics, and we estimated the association of risk factors with case fatality for children younger than 2 months, 2-11 months of age, and 12-59 months of age using separate multivariable mixed effects logistic regression models. FINDINGS: Between November, 2012, and May, 2013, we retrospectively collected all available hard copies of yellow forms from 40 of 41 participating hospitals. We examined 113 154 pneumonia cases, 104 932 (92·7%) of whom had mortality data and 6903 of whom died, and calculated an overall case fatality rate of 6·6% (95% CI 6·4-6·7). The case fatality rate significantly decreased between 2001 (15·2% [13·4-17·1]) and 2012 (4·5% [4·1-4·9]; ptrend<0·0001). Univariable analyses indicated that the decrease in case fatality rate was consistent across most subgroups. In multivariable analyses, the risk factors significantly associated with increased odds of mortality were female sex, young age, very severe pneumonia, clinically suspected Pneumocystis jirovecii infection, moderate or severe underweight, severe acute malnutrition, disease duration of more than 21 days, and referral from a health centre. Increasing year between 2001 and 2012 and increasing age (in months) were associated with reduced odds of mortality. Fast breathing was associated with reduced odds of mortality in children 2-11 months of age. However, case fatality rate in 2012 remained high for children with very severe pneumonia (11·8%), severe undernutrition (15·4%), severe acute malnutrition (34·8%), and symptom duration of more than 21 days (9·0%). INTERPRETATION: Pneumonia mortality and its risk factors have steadily improved in the past decade in Malawi; however, mortality remains high in specific subgroups. Improvements in hospital care may have reduced case fatality rates though a lack of sufficient data on quality of care indicators and the potential of socioeconomic and other improvements outside the hospital precludes adequate assessment of why case-fatality rates fell. Results from this study emphasise the importance of effective national systems for data collection. Further work combining this with data on trends in the incidence of pneumonia in the community are needed to estimate trends in the overall risk of mortality from pneumonia in children in Malawi. FUNDING: Bill & Melinda Gates Foundation.

A multi-method approach to the molecular diagnosis of overt and borderline 11p15.5 defects underlying Silver-Russell and Beckwith-Wiedemann syndromes. - Russo, Silvia; Calzari, Luciano; Mussa, Alessandro; Mainini, Ester; Cassina, Matteo; Di Candia, Stefania; Clementi, Maurizio; Guzzetti, Sara; Tabano, Silvia; Miozzo, Monica; Sirchia, Silvia; Finelli, Palma; et al. (Clin Epigenetics, 2016)
BACKGROUND: Multiple (epi)genetic defects affecting the expression of the imprinted genes within the 11p15.5 chromosomal region underlie Silver-Russell (SRS) and Beckwith-Wiedemann (BWS) syndromes. The molecular diagnosis of these opposite growth disorders requires a multi-approach flowchart to disclose known primary and secondary (epi)genetic alterations; however, up to 20 and 30 % of clinically diagnosed BWS and SRS cases remain without molecular diagnosis. The complex structure of the 11p15 region with variable CpG methylation and low-rate mosaicism may account for missed diagnoses. Here, we demonstrate the relevance of complementary techniques for the assessment of different CpGs and the importance of testing multiple tissues to increase the SRS and BWS detection rate. RESULTS: Molecular testing of 147 and 450 clinically diagnosed SRS and BWS cases provided diagnosis in 34 SRS and 185 BWS patients, with 9 SRS and 21 BWS cases remaining undiagnosed and herein referred to as "borderline." A flowchart including complementary techniques and, when applicable, the analysis of buccal swabs, allowed confirmation of the molecular diagnosis in all borderline cases. Comparison of methylation levels by methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in borderline and control cases defined an interval of H19/IGF2:IG-DMR loss of methylation that was distinct between "easy to diagnose" and "borderline" cases, which were characterized by values ≤mean -3 standard deviations (SDs) compared to controls. Values ≥mean +1 SD at H19/IGF2: IG-DMR were assigned to borderline hypermethylated BWS cases and those ≤mean -2 SD at KCNQ1OT1: TSS-DMR to hypomethylated BWS cases; these were supported by quantitative pyrosequencing or Southern blot analysis. Six BWS cases suspected to carry mosaic paternal uniparental disomy of chromosome 11 were confirmed by SNP array, which detected mosaicism till 10 %. Regarding the clinical presentation, borderline SRS were representative of the syndromic phenotype, with exception of one patient, whereas BWS cases showed low frequency of the most common features except hemihyperplasia. CONCLUSIONS: A conclusive molecular diagnosis was reached in borderline methylation cases, increasing the detection rate by 6 % for SRS and 5 % for BWS cases. The introduction of complementary techniques and additional tissue analyses into routine diagnostic work-up should facilitate the identification of cases undiagnosed because of mosaicism, a distinctive feature of epigenetic disorders.
Keywords: Beckwith-Wiedemann Syndrome; Blotting, Southern; Child; Child, Preschool; Chromosomes, Human, Pair 11; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Humans; Infant; Male; Mosaicism; Multiplex Polymerase Chain Reaction; Oligonucleotide Array Sequence Analysis; Silver-Russell Syndrome

The one-step synthesis and surface functionalization of dumbbell-like gold-iron oxide nanoparticles: a chitosan-based nanotheranostic system. - Kostevsek, Nina; Locatelli, Erica; Garrovo, Chiara; Arena, Francesca; Monaco, Ilaria; Nikolov, Ivaylo Petrov; Sturm, Saso; Zuzek Rozman, Kristina; Lorusso, Vito; Giustetto, Pierangela; Bardini, Paola; Biffi, Stefania; et al. (Chem Commun (Camb), 2016)
The first one-step synthesis of dumbbell-like gold-iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool.

Oral zinc provision in acute diarrhea. - Lazzerini, Marzia (Curr Opin Clin Nutr Metab Care, 2016)
PURPOSE OF REVIEW: The clinical management of acute diarrhea is based on the use of oral rehydration salts and appropriate nutrition. In addition, the WHO and The United Nations Children's Fund recommend zinc supplementation for diarrhea in children below 5 years. This article aims at reviewing recent literature on the effects of oral zinc for treating acute diarrhea in children. RECENT FINDINGS: Recent studies confirm that zinc supplementation has a benefit in children below 5 years with acute diarrhea in countries at medium or high risk of zinc deficiency. A few small trials have reported a benefit of zinc in children at low risk of zinc deficiency, with heterogeneity in results. No recent study has explored the effects of zinc in children younger than 6 months, and in this age group previous research refuted any benefit from zinc. SUMMARY: Current literature supports the use of oral zinc in treating diarrhea in children older than 6 months, especially if at risk of zinc deficiency, such as children with poor diets exposed to recurrent gastrointestinal infections. More research is needed to confirm findings in children at low risk of zinc deficiency. Currently there is no evidence that zinc benefits children younger than 6 months.

Pharmacogenetics driving personalized medicine: analysis of genetic polymorphisms related to breast cancer medications in Italian isolated populations. - Cocca, Massimiliano; Bedognetti, Davide; La Bianca, Martina; Gasparini, Paolo; Girotto, Giorgia (J Transl Med, 2016)
BACKGROUND: Breast cancer is the most common cancer in women characterized by a high variable clinical outcome among individuals treated with equivalent regimens and novel targeted therapies. In this study, we performed a population based approach intersecting high-throughput genotype data from Friuli Venezia Giulia (FVG) isolated populations with publically available pharmacogenomics information to estimate the frequency of genotypes correlated with responsiveness to breast cancer treatment thus improving the clinical management of this disease in an efficient and cost effective way. METHODS: A list of 80 variants reported to be related to the efficacy or toxicity of breast cancer drugs was obtained from PharmGKB database. Fourty-one were present in FVG, 1000G European (EUR) and ExAC (Non Finnish European) databases. Their frequency was extracted using PLINK software and the differences tested by Fisher's exact test. RESULTS: Statistical analyses revealed that 13 out of the 41 (32 %) variants were significantly different in frequency in our sample as compared to the EUR/ExAC cohorts. For nine variants the available level of evidence (LOE) included polymorphisms related to cyclophosphamide, tamoxifen, doxorubicin, fluorpyrimidine and paclitaxel. In particular, for trastuzumab two variants were detected: (1) rs1801274-G within FCGR2A and associated with decreased efficacy (LOE 2B); (2) rs1136201-G located within ERBB2 and associated with increased toxicity (LOE 3). Both these two variants were underrepresented in the FVG population compared to EUR/ExAC population thus suggesting a high therapeutic index of this drug in our population. Moreover, as regards fluoropyrimidines, the frequency of two polymorphisms within the DPYD gene associated with drug toxicity (e.g., rs2297595-C allele and rs3918290-T allele, LOE 2A and 1, respectively) was extremely low in FVG population thus suggesting that a larger number of FVG patients could benefit from full dosage of fluoropyrimidine therapy. CONCLUSIONS: All these findings increase the overall knowledge on the prevalence of specific variants related with breast cancer treatment responsiveness in FVG population and highlight the importance of assessing gene polymorphisms related with cancer medications in isolated communities.

Pitfalls and promises in FTIR spectromicroscopy analyses to monitor iron-mediated DNA damage in sperm. - Pascolo, Lorella; Bedolla, Diana E; Vaccari, Lisa; Venturin, Irene; Cammisuli, Francesca; Gianoncelli, Alessandra; Mitri, Elisa; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Zweyer, Marina; Ricci, Giuseppe (Reprod Toxicol, 2016)
Many drugs, chemicals, and environmental factors can impair sperm functionality by inducing DNA damage, one of the important causes of reduced fertility potential. The use of vibrational spectromicroscopy represents a promising approach for monitoring DNA integrity in sperm, although some limitations exist, depending from the experimental conditions. Here, we report that when using FTIR spectromicroscopy to reveal oxidative stress mediated by Fenton's reaction on hydrated sperm samples, DNA damage interpretation is partially compromised by unexpected cell surface precipitates. The precipitates give a broad band in the 1150-1000cm(-1) infrared region, which partially covers one of the signatures of DNA (phosphate stretching bands), and are detected as iron and oxygen containing material when using XRF spectroscopy. On the other hand, the analyses further support the potential of FTIR spectromicroscopy to reveal cellular oxidative damage events such as lipid peroxidation, protein misfolding and aggregations, as well as DNA strain breaks.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children's anxiety and pain levels in emergency department. - Felluga, Margherita; Rabach, Ingrid; Minute, Marta; Montico, Marcella; Giorgi, Rita; Lonciari, Isabella; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2016)
UNLABELLED: The aim of the study is to investigate if the presence of medical clowns during painful procedures in the emergency department (ED) affects children's anxiety and pain. Forty children (4-11 years) admitted to the ED with the need of painful procedures were prospectively enrolled. They were randomly assigned to the clown group, where children interacted with clowns or to the control group in which they were entertained by parents and ED nurses. The children's anxiety was assessed by the Children's Anxiety and Pain Scales; pain was evaluated with the Numerical Rating Scale and Wong-Backer Scale, according to the children's age. Staff and clown's opinions were evaluated by means of dedicated questionnaires. Children's anxiety levels in the clown group were significantly lower than those compared with the control group, while children's pain levels did not change between the two groups. CONCLUSION: The presence of clowns in the ED before and during painful procedures was effective in reducing children's anxiety. WHAT IS KNOWN: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Role of inflammasome genetics in susceptibility to HPV infection and cervical cancer development. - Pontillo, A; Bricher, P; Leal, V N C; Lima, S; Souza, P R E; Crovella, S (J Med Virol, 2016)
PROBLEM: Only a small proportion of HPV+ women develop virus-associated lesions and cervical cancer, suggesting that other factors are involved in HPV+ keratinocyte transformation. Immune response plays an important role in clearing HPV infection, and host genetic variants resulting in defective immune response have been associated with virus persistence and/or cervical cancer. Considering that genetic variations in inflammasome genes were previously associated with viral infection and cancer development, the present study investigates selected single nucleotide polymorphisms (SNPs) in inflammasome genes as a possible risk factor for HPV infection susceptibility and/or for progression to cervical cancer. PATIENTS AND METHODS: 12 SNPs in seven inflammasome-related genes (NLRP1, NLRP3, NLRP6, CARD8, IL1B, IL18, TNFAIP3) were genotyped in a Brazilian HPV+ case/control cohort (n = 246/310). Multivariate analysis was performed in case/control as well as in HPV+ women stratified by the presence or severity of histologic lesion, HPV persistence, and type of virus. RESULTS: IL1B rs1143643 was associated with protection against HPV infection in case/control analysis. NLRP1 rs11651270 plays a protection role against HPV persistence and/or oncogenesis. NLRP3 rs10754558 and IL18 rs1834481 exert a beneficial role against HPV persistence. NLRP3 rs10754558 variant resulted significantly associated with a lower risk to be infected with a high-risk HPV. CONCLUSION: Our findings for the first time demonstrated that inflammasome genetics could affect HPV/host interaction in terms of virus susceptibility as well as of virus/persistence and cervical cancer progression. J. Med. Virol. 88:1646-1651, 2016. © 2016 Wiley Periodicals, Inc.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

Thalidomide for inflammatory bowel disease: Systematic review. - Bramuzzo, Matteo; Ventura, Alessandro; Martelossi, Stefano; Lazzerini, Marzia (Medicine (Baltimore), 2016)
BACKGROUND: Thalidomide is an immunomodulatory drug used in the experimental treatment of refractory Crohn disease and ulcerative colitis. We aimed to review the existing evidence on the efficacy and safety of thalidomide in the treatment of inflammatory bowel diseases. METHODS: CENTRAL, MEDLINE, LILACS, POPLINE, CINHAL, and Web of Science were searched in March 2016. Manual search included conference and reference lists. All types of studies, except single case reports, were included. Outcomes evaluated were: induction of remission; maintenance of remission; steroid reduction; effect on penetrating Crohn disease; endoscopic remission; adverse events. RESULTS: The research strategies retrieved 722 papers. Two randomized controlled trials and 29 uncontrolled studies for a total of 489 patients matched the inclusion criteria. Thalidomide induced a clinical response in 296/427 (69.3%) patients. Clinical remission was achieved in 220/427 (51.5%) cases. Maintenance of remission was reported in 128/160 (80.0%) patients at 6 months and in 96/133 (72.2%) at 12 months. Reduction in steroid dosage was reported in 109/152 (71.7%) patients. Fistulas improved in 49/81 (60.5%) cases and closed in 28/81 (34.6%). Endoscopic improvement was observed in 46/66 (69.7%) and complete mucosal healing in 35/66 (53.0%) patients. Cumulative incidence of total adverse events and of those leading to drug suspension was 75.6 and 19.7/1000 patient-months, respectively. Neurological disturbances accounted for 341/530 (64.3%) adverse events and were the most frequent cause of drug withdrawal. CONCLUSION: Existing evidence suggests that thalidomide may be a valid treatment option for patients with inflammatory bowel diseases refractory to other first- and second-line treatments.

Thiopurine Biotransformation and Pharmacological Effects: Contribution of Oxidative Stress. - Pelin, Marco; De Iudicibus, Sara; Londero, Margherita; Spizzo, Riccardo; Dei Rossi, Sveva; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Curr Drug Metab, 2016)
BACKGROUND: Thiopurine antimetabolites are important agents for the treatment of severe diseases, such as acute lymphoblastic leukemia and inflammatory bowel disease. Their pharmacological actions depend on biotransformation into active thioguanine-nucleotides; intracellular metabolism is mediated by enzymes of the salvage pathway of nucleotide synthesis and relies on polymorphic enzymes involved in thiopurines' catabolism such as thiopurine-S-methyl transferase. Given the enzymes involved in thiopurines' metabolism, it is reasonable to hypothesize that these drugs are able to induce significant oxidative stress conditions, possibly altering their pharmacological activity. METHODS: A systemic search of peer-reviewed scientific literature in bibliographic databases has been carried out. Both clinical and preclinical studies as well as mechanistic studies have been included to shed light on the role of oxidative stress in thiopurines' pharmacological effects. RESULTS: Sixty-nine papers were included in our review, allowing us to review the contribution of oxidative stress in the pharmacological action of thiopurines. Thiopurines are catabolized in the liver by xanthine oxidase, with potential production of reactive oxidative species and azathioprine is converted into mercaptopurine by a reaction with reduced glutathione, that, in some tissues, may be facilitated by glutathione- S-transferase (GST). A clear role of GSTM1 in modulating azathioprine cytotoxicity, with a close dependency on superoxide anion production, has been recently demonstrated. Interestingly, recent genome-wide association studies have shown that, for both azathioprine in inflammatory bowel disease and mercaptopurine in acute lymphoblastic leukemia, treatment effects on patients' white blood cells are related to variants of a gene, NUDT15, involved in biotransformation of oxidated nucleotides. CONCLUSIONS: Basing on previous evidences published in literature, oxidative stress may contribute to thiopurine effects in significant ways that, however, are still not completely elucidated.

TRIM32 ubiquitin E3 ligase, one enzyme for several pathologies: From muscular dystrophy to tumours. - Lazzari, Elisa; Meroni, Germana (Int J Biochem Cell Biol, 2016)
TRIM32 is a member of the TRIpartite Motif family characterised by the presence of an N-terminal three-domain-module that includes a RING domain, which confers E3 ubiquitin ligase activity, one or two B-box domains and a Coiled-Coil region that mediates oligomerisation. Several TRIM32 substrates were identified including muscular proteins and proteins involved in cell cycle regulation and cell motility. As ubiquitination is a versatile post-translational modification that can affect target turnover, sub-cellular localisation or activity, it is likely that diverse substrates may be differentially affected by TRIM32-mediated ubiquitination, reflecting its multi-faceted roles in muscle physiology, cancer and immunity. With particular relevance for muscle physiology, mutations in TRIM32 are associated with autosomal recessive Limb-Girdle Muscular Dystrophy 2H, a muscle-wasting disease with variable clinical spectrum ranging from almost asymptomatic to wheelchair-bound patients. In this review, we will focus on the ability of TRIM32 to mark specific substrates for proteasomal degradation discussing how the TRIM32-proteasome axis may (i) be important for muscle homeostasis and for the pathogenesis of muscular dystrophy; and (ii) define either an oncogenic or tumour suppressive role for TRIM32 in the context of different types of cancer.

Understanding the role of personality and alexithymia in food preferences and PROP taste perception. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; La Bianca, Martina; Gasparini, Paolo; Carlino, Davide; Tepper, Beverly J (Physiol Behav, 2016)
Taste perception and food preferences are influenced by a variety of factors, including personality characteristics. The aims of this study were to examine the role of personality characteristics, such as alexithymia (a personality construct characterized by inability to identify, describe, and work with one's own feelings), in: 1) taste responses to the bitter genetic taste-marker PROP and 2) food liking. We studied 649 healthy subjects residing in six genetically-isolated villages of Northeast Italy. Data on PROP taste responsiveness, food liking, personality characteristics and TAS2R28 genotypes were collected. Results showed that PROP non-tasters had higher alexithymia scores than PROP tasters. Moreover, the presence of alexithymia in heterozygous individuals for the rs1726886 polymorphism of the TAS2R38 gene was associated with a reduction in the perceived intensity of PROP. Finally, higher alexithymia scores were associated with liking of alcohol, sweets and fats/meats whereas lower alexithymia scores were related to liking of vegetables, condiments and strong cheeses, Measures of temperament, character, anxiety and depression were also related to food liking. Our findings suggest that: 1) alexithymia, in addition to the TAS2R38 polymorphism, may play a role in responsiveness to the aversive and bitter taste of PROP; and 2) alexithymia, in combination with other personality traits, may provide important insights for better understanding food liking.

When a lymphatic malformation determines a bowel volvulus: Are clinical status and images always reliable? - Guida, Edoardo; Di Grazia, Massimo; Cattaruzzi, Elisabetta; Bussani, Rossana; Rigamonti, Waifro; Lembo, Maria Antonietta (Int J Surg Case Rep, 2016)
INTRODUCTION: An acute abdomen in the form of small-bowel volvulus could be a presentation of a lymphatic malformation in childhood. CASE PRESENTATION: A 5year old male was admitted to our Institute for an acute abdomen. Clinical aspects and radiological images were not specific for a certain diagnosis. Laparotomy revealed a big soft mass, with a milky content, completely involving about 50cm of ileus with a partial volvulus of the intestinal loop. A complete mass excision and also a bowel involved resection were performed. After a histological examination, a lymphatic malformation was diagnosed. DISCUSSION: The diagnosis of a mesenteric lymphatic malformation could be intraoperative and a complete resection should be the treatment of choice. Sometimes it could be necessary to perform an involved bowel tract resection in the case of volvolus with ischemia. CONCLUSIONS: Paediatricians and surgeons should bare in mind that an intrabdominal lymphatic malformation may present as a nonspecific an acute abdomen caused by a bowel volvolus and diagnosis may not be so simple preoperatively.

5-Aminoimidazole-4-carboxamide ribonucleotide-transformylase and inosine-triphosphate-pyrophosphatase genes variants predict remission rate during methotrexate therapy in patients with juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Moressa, Valentina; Zandonà, Luigi; Favretto, Diego; Malusà, Noelia; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Rheumatol Int, 2015)
For children with juvenile idiopathic arthritis (JIA) who fail to respond to methotrexate, the delay in identifying the optimal treatment at an early stage of disease can lead to long-term joint damage. Recent studies indicate that relevant variants to predict methotrexate response in JIA are those in 5-aminoimidazole-4-carboxamide ribonucleotide-transformylase (ATIC), inosine-triphosphate-pyrophosphatase (ITPA) and solute-liquid-carrier-19A1 genes. The purpose of the study was, therefore, to explore the role of these candidate genetic factors on methotrexate response in an Italian cohort of children with JIA. Clinical response to methotrexate was evaluated as clinical remission stable for a 6-month period, as ACRPed score and as change in Juvenile Arthritis Disease score. The most relevant SNPs for each gene considered were assayed on patients' DNA. ITPA activity was measured in patients' erythrocytes. Sixty-nine patients with JIA were analyzed: 52.2 % responded to therapy (ACRPed70 score), while 37.7 % reached clinical remission stable for 6 months. ATIC rs2372536 GG genotype was associated with improved clinical remission (adjusted p value = 0.0090). For ITPA, rs1127354 A variant was associated with reduced clinical remission: (adjusted p value = 0.028); this association was present even for patients with wild-type ITPA and low ITPA activity. These preliminary results indicate that genotyping of ATIC rs2372536 and ITPA rs1127354 variants or measuring ITPA activity could be useful to predict methotrexate response in children with JIA after validation by further prospective studies on a larger patient cohort.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Analysis of functional variants reveals new candidate genes associated with alexithymia. - Mezzavilla, Massimo; Ulivi, Sheila; Bianca, Martina La; Carlino, Davide; Gasparini, Paolo; Robino, Antonietta (Psychiatry Res, 2015)
In this study we explored the possible association between 36,915 functional variants and alexithymia, a personality trait characterized by the inability to identify and describe emotions and feelings. From our analysis, variants in the genes ABCB4, TP53AIP1, ARHGAP32 and TMEM88B were identified linked to the alexithymia phenotype.
Keywords: Adolescent; Adult; Affective Symptoms; Aged; Case-Control Studies; DNA-Binding Proteins; Emotions; Female; Humans; Male; Membrane Proteins; Middle Aged; P-Glycoproteins; Personality Inventory; Phenotype; Tumor Suppressor Proteins; Young Adult

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

Characterization of 14 novel deletions underlying Rubinstein-Taybi syndrome: an update of the CREBBP deletion repertoire. - Rusconi, Daniela; Negri, Gloria; Colapietro, Patrizia; Picinelli, Chiara; Milani, Donatella; Spena, Silvia; Magnani, Cinzia; Silengo, Margherita Cirillo; Sorasio, Lorena; Curtisova, Vaclava; Cavaliere, Maria Luigia; Prontera, Paolo; et al. (Hum Genet, 2015)
Rubinstein-Taybi syndrome (RSTS) is a rare, clinically heterogeneous disorder characterized by cognitive impairment and several multiple congenital anomalies. The syndrome is caused by almost private point mutations in the CREBBP (~55% of cases) and EP300 (~8%) genes. The CREBBP mutational spectrum is variegated and characterized by point mutations (30-50 %) and deletions (~10%). The latter are diverse in size and genomic position and remove either the whole CREBBP gene and its flanking regions or only an intragenic portion. Here, we report 14 novel CREBBP deletions ranging from single exons to the whole gene and flanking regions which were identified by applying complementary cytomolecular techniques: fluorescence in situ hybridization, multiplex ligation-dependent probe amplification and array comparative genome hybridization, to a large cohort of RSTS patients. Deletions involving CREBBP account for 23% of our detected CREBBP mutations, making an important contribution to the mutational spectrum. Genotype-phenotype correlations revealed that patients with CREBBP deletions extending beyond this gene did not always have a more severe phenotype than patients harboring CREBBP point mutations, suggesting that neighboring genes play only a limited role in the etiopathogenesis of CREBBP-centerd contiguous gene syndrome. Accordingly, the extent of the deletion is not predictive of the severity of the clinical phenotype.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Cohort Studies; CREB-Binding Protein; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Point Mutation; Rubinstein-Taybi Syndrome; Sequence Deletion

Delayed reactivation of chronic infantile neurologic, cutaneous, articular syndrome (CINCA) in a patient with somatic mosaicism of CIAS1/NLRP3 gene after withdrawal of anti-IL-1 beta therapy. - Paloni, Giulia; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Taddio, Andrea (Clin Exp Rheumatol, 2015)
Keywords: Antibodies, Monoclonal; Carrier Proteins; Cryopyrin-Associated Periodic Syndromes; Drug Administration Schedule; Female; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Mosaicism; Phenotype; Recurrence; Remission Induction; Time Factors; Treatment Outcome; Young Adult

The diagnostic challenge of very early-onset enterocolitis in an infant with XIAP deficiency. - Girardelli, Martina; Arrigo, Serena; Barabino, Arrigo; Loganes, Claudia; Morreale, Giuseppe; Crovella, Sergio; Tommasini, Alberto; Bianco, Anna Monica (BMC Pediatr, 2015)
BACKGROUND: Aggressive course and resistance to treatments usually characterize very early onset inflammatory bowel disease (VEO-IBD). Some VEO-IBD cases are due to monogenic immune defects and can benefit from hematopoietic stem cell transplantation (HSCT). CASE PRESENTATION: We describe a Caucasian male baby who presented in the first months of life macrophage activation syndrome, followed by intractable colitis, recurrent episodes of fever and mild splenomegaly. After several immunological, genetic and clinical investigations, subsequently a therapeutic attempt with colectomy, analysis of VEO-IBD-associated genes, revealed a causative mutation in XIAP. The genetic diagnosis of a primary immune deficiency allowed curing the boy with hematopoietic stem cell transplantation. CONCLUSION: Our report, together with novel findings from recent literature, should contribute to increase awareness of monogenic immune defects as a cause of VEO-IBD. Comprehensive genetic analysis can allow a prompt diagnosis, resulting in the choice of effective treatments and sparing useless and damaging procedures.

Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Dysplastic bone marrow changes during maintenance therapy for acute leukemia. - Chinello, Matteo; Naviglio, Samuele; Shardlow, Alison; Severino, Alessandro; Ventura, Alessandro; Locasciulli, Anna (J Pediatr Hematol Oncol, 2015)
We describe the case of an 8-year-old girl with common precursor B-cell acute lymphoblastic leukemia who presented with severe pancytopenia during maintenance therapy with methotrexate and 6-mercaptopurine. The bone marrow smear showed moderate hypocellularity and trilinear dysplastic changes consistent with a diagnosis of drug toxicity, with no evidence of lymphoblasts. Flow cytometric immunophenotyping was negative for leukemic cells. Blood cell counts normalized after treatment with folinic acid. Maintenance therapy was gradually restarted and she remained well at follow-up visits. Myelotoxicity from methotrexate and 6-mercaptopurine may represent an unpredictable incident during an otherwise uneventful maintenance therapy, and may occur independently of other organ toxicities.
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Bone Marrow Diseases; Child; Disease Management; Female; Follow-Up Studies; Humans; Methotrexate; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Prognosis

Early onset bilateral anterior uveitis preceding a late manifestation of juvenile idiopathic arthritis: a case report. - Parentin, Fulvio; Matarazzo, Lorenza; Lepore, Loredana; Pensiero, Stefano; Ventura, Alessandro (Ocul Immunol Inflamm, 2015)
Keywords: Adolescent; Arthritis, Juvenile; Female; Humans; Time Factors; Tomography, Optical Coherence; Uveitis, Anterior

Effect of seminal leukocytes on in vitro fertilization and intracytoplasmic sperm injection outcomes. - Ricci, Giuseppe; Granzotto, Marilena; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Zito, Gabriella; Borelli, Massimo (Fertil Steril, 2015)
OBJECTIVE: To investigate the influence of seminal leukocytes on conventional IVF and intracytoplasmic sperm injection (ICSI) outcomes, using a flow cytometry method. DESIGN: Prospective study. SETTING: Tertiary infertility center and research institute. PATIENT(S): One hundred sixty-four couples undergoing conventional IVF or ICSI. INTERVENTION(S): Seminal leukocytes were counted by flow cytometry. MAIN OUTCOME MEASURE(S): Correlation between seminal leukocytes concentration and reproductive outcomes in IVF and ICSI cycles. RESULT(S): The median number of oocytes retrieved, the fertilization and cleavage rate, the median number and grade of embryos transferred, the median number of good-quality embryos transferred, and the median percentage of good-quality embryos from total embryos transferred, in leukocytospermic and non-leukocytospermic patients were not statistically different after either IVF or ICSI. Similarly, there were no significant differences between the two groups for implantation rate and clinical pregnancy rate. Multivariate logistic regression analysis showed that the reproductive outcomes were not influenced by adjustment for female age, infertility diagnosis, number of previous attempts, treatment protocol (GnRH agonist or antagonist), assisted reproduction procedure (IVF or ICSI), and leukocytospermia. By profiling the proper Poisson regression models, no leukocytospermia cut-off value was able to identify the subjects at risk for oocyte fertilization or embryo cleavage failure. CONCLUSION(S): Using a flow cytometry method, we demonstrated that leukocytospermia does not significantly influence IVF or ICSI outcomes. The same results were obtained by using lower or higher cut-off values for leukocytospermia (from 0.2 to 2 × 10(6)/mL).
Keywords: Adult; Female; Fertilization in Vitro; Flow Cytometry; Humans; Leukocytes; Male; Pregnancy; Pregnancy Rate; Prospective Studies; Semen; Sperm Injections, Intracytoplasmic

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Efficacy of intravenous immunoglobulin therapy in giant cell hepatitis with autoimmune hemolytic anemia: A multicenter study. - Marsalli, Giulia; Nastasio, Silvia; Sciveres, Marco; Calvo, Pier Luigi; Ramenghi, Ugo; Gatti, Simona; Albano, Veronica; Lega, Sara; Ventura, Alessandro; Maggiore, Giuseppe (Clin Res Hepatol Gastroenterol, 2015)
BACKGROUND AND OBJECTIVE: Giant cell hepatitis with autoimmune hemolytic anemia (GCH-AHA) is a rare disease of infancy, of possible autoimmune mechanism with poor prognosis due to its scarce response to immunosuppressive drugs. The aim of this retrospective multicenter study was to evaluate the efficacy and safety of intravenous immunoglobulin (IVIg) treatment in inducing and maintaining remission of the liver disease, in patients with GCH-AHA. METHODS: Seven children with GCH-AHA, four newly diagnosed, and three in relapse, being treated with different therapies, received one to three IVIg infusions (0.5 to 2g/kg) in association with other immunosuppressive drugs. Subsequently five of them received monthly sequential IVIg infusions (mean 13.4, range 7-24). RESULTS: IVIg infusions as first-line therapy associated with prednisone and other immunosuppressive drugs significantly (P=0.04) reduced the aminotransferase activity in all patients and normalized prothombin activity in the only patient with severe liver dysfunction. Sequential monthly IVIg infusions determined a steroid-sparing effect and allowed a complete or partial remission in all patients, although with temporary efficacy, since relapse of the hemolytic anemia and/or of liver disease occurred in all patients. IVIg infusions were associated with mild side effects in two patients. CONCLUSIONS: IVIg infusion can be safely and effectively administered in patients with severe GCH-AHA at diagnosis, or in case of relapse, in association with other immunosuppressive drugs. Repeated IVIg infusions may help maintain remission, however, due to their temporary efficacy, they should not be routinely employed.

Food protein-induced enterocolitis syndrome caused by fish and/or shellfish in Italy. - Miceli Sopo, Stefano; Monaco, Serena; Badina, Laura; Barni, Simona; Longo, Giorgio; Novembre, Elio; Viola, Serena; Monti, Giovanna (Pediatr Allergy Immunol, 2015)
BACKGROUND: The study describes the demographic features, culprit foods, clinical features and outcomes for children presenting with acute fish and/or shellfish food protein-induced enterocolitis syndrome (FPIES) in four Italian paediatric allergy centres. METHODS: A retrospective/prospective study was undertaken. All children diagnosed with fish or shellfish FPIES were enrolled. The diagnosis of FPIES was based on Sicherer's or Miceli Sopo clinical criteria. Skin prick tests (SPT) were performed in all patients, at the time of diagnosis and prior to OFC. RESULTS: Seventy children were enrolled. Mean age at first episode was 14 months (range 6-46 months); mean age at diagnosis was 34 months (range 6-164 months). Sole and cod were the fish most commonly implicated. Fifty-seven of 70 (81%) children had FPIES exclusively to fish, 37 of 57 (65%) children had single-fish FPIES, 20 of 57 (35%) multiple-fish FPIES, nine of 70 (13%) presented adverse reactions exclusively to shellfish, and four of 70 (6%) presented adverse reactions to both fish and shellfish. Only four (5.7%) children presented episodes of acute FPIES with different foods (2 to cow's milk, 1 to egg, 1 to beef); in all cases, onset was prior to that of fish or shellfish FPIES. Fifteen of 70 (21%) children tolerated fish other than the offending fish. Twenty-four of 70 (34%) children achieved tolerance (age range 24-102 months). CONCLUSIONS: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Glucocorticoid pharmacogenetics in pediatric idiopathic nephrotic syndrome. - Cuzzoni, Eva; De Iudicibus, Sara; Franca, Raffaella; Stocco, Gabriele; Lucafò, Marianna; Pelin, Marco; Favretto, Diego; Pasini, Andrea; Montini, Giovanni; Decorti, Giuliana (Pharmacogenomics, 2015)
Idiopathic nephrotic syndrome represents the most common type of primary glomerular disease in children: glucocorticoids (GCs) are the first-line therapy, even if considerable interindividual differences in thepir efficacy and side effects have been reported. Immunosuppressive and anti-inflammatory effects of these drugs are mainly due to the GC-mediated transcription regulation of pro- and anti-inflammatory genes. This mechanism of action is the result of a complex multistep pathway that involves the glucocorticoid receptor and several other proteins, encoded by polymorphic genes. Aim of this review is to highlight the current knowledge on genetic variants that could affect GC response, particularly focusing on children with idiopathic nephrotic syndrome.

Hypoxaemia as a Mortality Risk Factor in Acute Lower Respiratory Infections in Children in Low and Middle-Income Countries: Systematic Review and Meta-Analysis. - Lazzerini, Marzia; Sonego, Michela; Pellegrin, Maria Chiara (PLoS One, 2015)
OBJECTIVE: To evaluate the association between hypoxaemia and mortality from acute lower respiratory infections (ALRI) in children in low- and middle-income countries (LMIC). DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on the association between hypoxaemia and death from ALRI in children below five years in LMIC. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to February 2015. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 11,627 papers retrieved, 18 studies from 13 countries on 20,224 children met the inclusion criteria. Twelve (66.6%) studies had either low or moderate risk of bias. Hypoxaemia defined as oxygen saturation rate (SpO2) <90% associated with significantly increased odds of death from ALRI (OR 5.47, 95% CI 3.93 to 7.63) in 12 studies on 13,936 children. An Sp02 <92% associated with a similar increased risk of mortality (OR 3.66, 95% CI 1.42 to 9.47) in 3 studies on 673 children. Sensitivity analyses (excluding studies with high risk of bias and using adjusted OR) and subgroup analyses (by: altitude, definition of ALRI, country income, HIV prevalence) did not affect results. Only one study was performed on children living at high altitude. CONCLUSIONS: The results of this review support the routine evaluation of SpO2 for identifying children with ALRI at increased risk of death. Both a Sp02 value of 92% and 90% equally identify children at increased risk of mortality. More research is needed on children living at high altitude. Policy makers in LMIC should aim at improving the regular use of pulse oximetry and the availability of oxygen in order to decrease mortality from ALRI.

Immunologic evidence of a strong association between non-Hodgkin lymphoma and simian virus 40. - Tognon, Mauro; Luppi, Mario; Corallini, Alfredo; Taronna, Angelo; Barozzi, Patrizia; Rotondo, John Charles; Comar, Manola; Casali, Maria Vittoria; Bovenzi, Massimo; D'Agostino, Antonio; Vinante, Fabrizio; Rigo, Antonella; et al. (Cancer, 2015)
BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed to detect specific antibodies against SV40. Serum samples were taken from 2 distinct cohorts of NHL-affected patients (NHL1 [n = 89] and NHL2 [n = 61]) along with controls represented by oncologic patients affected by breast cancer (BC; n = 78) and undifferentiated nasopharyngeal carcinoma (UNPC; n = 64) and 3 different cohorts of healthy subjects (HSs; HS1 [n = 130], HS2 [n = 83], and HS3 [n = 87]). RESULTS: Immunologic data indicated that in serum samples from NHL patients, antibodies against SV40 mimotopes were detectable with a prevalence of 40% in NHL1 patients and with a prevalence of 43% in NHL2 patients. In HSs of the same median age as NHL patients, the prevalence was 16% for the HS1 group (57 years) and 14% for the HS2 group (65 years). The difference was statistically significant (P < .0001 and P < .001). Interestingly, the difference between NHL1/NHL2 patients and BC patients (40%/43% vs 15%, P < .001) and between NHL1/NHL2 patients and UNPC patients (40%/43% vs 25%, P < .05) was significant. CONCLUSIONS: Our data indicate a strong association between NHL and SV40 and thus a need for innovative therapeutic approaches for this hematologic malignancy.
Keywords: Adult; Aged; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lymphoma, Non-Hodgkin; Male; Middle Aged; Polyomavirus Infections; Seroepidemiologic Studies; Simian virus 40; Tumor Virus Infections

Interleukin-18, interleukin-12B and interferon-γ gene polymorphisms in Brazilian patients with rheumatoid arthritis: a pilot study. - Angelo, H D; Gomes Silva, I I F; Oliveira, R D R; Louzada-Júnior, P; Donadi, E A; Crovella, S; Maia, M M D; de Souza, P R E; Sandrin-Garcia, P (Tissue Antigens, 2015)
Polymorphisms in interleukin (IL)-18, IL-12 and interferon (IFN)-γ genes are associated with different levels of cytokines expression and have been associated with rheumatoid arthritis (RA). IL-18 +105 A/C, IL-12B +1188 A/C and IFN-γ +874 T/A polymorphisms were analyzed by restriction fragment length polymorphism-polymerase chain reaction (PCR) and amplification refractory mutation system PCR from 90 RA patients and 186 healthy individuals. There were significant differences to IL-18 +105 A/C polymorphism between the RA and control groups (odds ratio = 3.77; P < 0.0001). Individual carriers of the variant allele C had a 3.77-fold increased risk of for RA (P = 0.0032). No association was observed for IL-12B and IFN-γ polymorphisms. Our finds suggest a possible role for IL-18 polymorphism in the RA susceptibility in studied population.

Kinetic Profiles of Inflammatory Mediators in the Conjunctival Sac Fluid of Patients upon Photorefractive Keratectomy. - Tisato, Veronica; Perri, Paolo; Rimondi, Erika; Melloni, Elisabetta; Lamberti, Giuseppe; Milani, Daniela; Secchiero, Paola; Zauli, Giorgio (Mediators Inflamm, 2015)
Photorefractive keratectomy (PRK) represents a therapeutic option to remodel corneal stroma and to compensate refractive errors, which involves inflammatory and/or regenerative processes. In this context, the modulation of cytokines/chemokines in the conjunctival sac fluid and their role in the maintenance of the corneal microenvironment during the healing process upon refractive procedures has not been deeply investigated. In this study, serial samples of conjunctival sac fluid of patients (n = 25) undergoing PRK were harvested before and at different time points after surgery. The levels of 29 cytokines/chemokines/growth factors involved in inflammatory/immune processes were measured with a multiplex array system. The results have firstly highlighted the different pattern of cytokine expression between the microenvironment at the anterior surface of the eye and the systemic circulation. More importantly, the kinetic of modulation of cytokines/chemokines at the conjunctival level following PRK revealed that while the majority of cytokines/chemokines showed a significant decrease, MCP-1 emerged in light of its pronounced and significant increase soon after PRK and during the follow-up. This methodological approach has highlighted the role of MCP-1 in the healing process following PRK and has shown a potential for the identification of expression/modulation of soluble factors for biomarker profiling in ocular surface diseases.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Long noncoding RNA GAS5: a novel marker involved in glucocorticoid response. - Lucafo, M; De Iudicibus, S; Di Silvestre, A; Pelin, M; Candussio, L; Martelossi, S; Tommasini, A; Piscianz, E; Ventura, A; Decorti, G (Curr Mol Med, 2015)
Glucocorticoids (GCs) exert their effects through regulation of gene expression after activation in the cytoplasm of the glucocorticoid receptor (GR) encoded by NR3C1 gene. A negative feedback mechanism resulting in GR autoregulation has been demonstrated through the binding of the activated receptor to intragenic sequences called GRE-like elements, contained in GR gene. The long noncoding RNA growth arrest-specific transcript 5 (GAS5) interacts with the activated GR suppressing its transcriptional activity. The aim of this study was to evaluate the possible role of GAS5 and NR3C1 gene expression in the antiproliferative effect of methylprednisolone in peripheral blood mononuclear cells and to correlate the expression with individual sensitivity to GCs. Subjects being poor responders to GCs presented higher levels of GAS5 and NR3C1 in comparison with good responders. We suggest that abnormal levels of GAS5 may alter GC effectiveness, probably interfering with the mechanism of GR autoregulation.
Keywords: Adult; Cell Proliferation; Female; Gene Expression Regulation; Glucocorticoids; Humans; Leukocytes, Mononuclear; Male; Methylprednisolone; Middle Aged; Receptors, Glucocorticoid; RNA, Long Noncoding; Transcription, Genetic

MID2 can substitute for MID1 and control exocytosis of lytic granules in cytotoxic T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Levring, Trine B; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte M; Geisler, Carsten (APMIS, 2015)
We have recently shown that the E3 ubiquitin ligase midline 1 (MID1) is upregulated in murine cytotoxic lymphocytes (CTL), where it controls exocytosis of lytic granules and the killing capacity. Accordingly, CTL from MID1 knock-out (MID1(-/-)) mice have a 25-30% reduction in exocytosis of lytic granules and cytotoxicity compared to CTL from wild-type (WT) mice. We wondered why the MID1 gene knock-out did not affect exocytosis and cytotoxicity more severely and speculated whether MID2, a close homologue of MID1, might partially compensate for the loss of MID1 in MID1(-/-) CTL. Here, we showed that MID2, like MID1, is upregulated in activated murine T cells. Furthermore, MID1(-/-) CTL upregulated MID2 two-twenty-fold stronger than CTL from WT mice, suggesting that MID2 might compensate for MID1. In agreement, transfection of MID2 into MID1(-/-) CTL completely rescued exocytosis of lytic granules in MID1(-/-) CTL, and vice versa, knock-down of MID2 inhibited exocytosis of lytic granules in both WT and MID1(-/-) CTL, demonstrating that both MID1 and MID2 play a central role in the regulation of granule exocytosis and that functional redundancy exists between MID1 and MID2 in CTL.
Keywords: Animals; Cytoplasmic Granules; Exocytosis; Interferon-gamma; Mice; Mice, Inbred C57BL; Mice, Knockout; Microtubule-Associated Proteins; Proteins; T-Lymphocytes, Cytotoxic; Transcription Factors; Up-Regulation

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Music Training Increases Phonological Awareness and Reading Skills in Developmental Dyslexia: A Randomized Control Trial. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Montico, Marcella; Zoia, Stefania; Schön, Daniele (PLoS One, 2015)
There is some evidence for a role of music training in boosting phonological awareness, word segmentation, working memory, as well as reading abilities in children with typical development. Poor performance in tasks requiring temporal processing, rhythm perception and sensorimotor synchronization seems to be a crucial factor underlying dyslexia in children. Interestingly, children with dyslexia show deficits in temporal processing, both in language and in music. Within this framework, we test the hypothesis that music training, by improving temporal processing and rhythm abilities, improves phonological awareness and reading skills in children with dyslexia. The study is a prospective, multicenter, open randomized controlled trial, consisting of test, rehabilitation and re-test (ID NCT02316873). After rehabilitation, the music group (N = 24) performed better than the control group (N = 22) in tasks assessing rhythmic abilities, phonological awareness and reading skills. This is the first randomized control trial testing the effect of music training in enhancing phonological and reading abilities in children with dyslexia. The findings show that music training can modify reading and phonological abilities even when these skills are severely impaired. Through the enhancement of temporal processing and rhythmic skills, music might become an important tool in both remediation and early intervention programs.Trial Registration: ClinicalTrials.gov NCT02316873

A nationwide survey of PMM2-CDG in Italy: high frequency of a mild neurological variant associated with the L32R mutation. - Barone, Rita; Carrozzi, M; Parini, R; Battini, R; Martinelli, D; Elia, M; Spada, M; Lilliu, F; Ciana, G; Burlina, A; Leuzzi, V; Leoni, M; et al. (J Neurol, 2015)
PMM2-CDG (PMM2 gene mutations) is the most common congenital disorder of N-glycosylation. We conducted a nationwide survey to characterize the frequency, clinical features, glycosylation and genetic correlates in Italian patients with PMM2-CDG. Clinical information was obtained through a questionnaire filled in by the referral physicians including demographics, neurological and systemic features, neuroimaging data and genotype. Glycosylation analyses of serum transferrin were complemented by MALDI-Mass Spectrometry (MALDI-MS). Between 1996 and 2012, data on 37 Italian patients with PMM2-CDG were collected. All the patients with a severe phenotype were unable to walk unaided, 84 % had severe intellectual disability and 81 % microcephaly. Conversely, among 17 mildly affected patients 82 % had independent ambulation, 64 % had borderline to mild intellectual disability and 35 % microcephaly. Epilepsy and stroke-like events did not occur among patients with the mild phenotype. The rate and extent of systemic involvement were more pronounced in severely affected patients. The L32R misfolding mutation of the PMM2 gene occurred in 70 % of the patients with the mild phenotype and was associated with a less severe underglycosylation of serum Tf at MALDI-MS analyses. Despite their different disease severity, all patients had progressive (olivo)ponto-cerebellar atrophy that was the hallmark clinical feature for the diagnosis. A mild neurological phenotype of PMM2-CDG marked by preserved ambulatory ability and autonomy and associated with L32R mutation is particularly frequent in Italy. PMM2-CDG should be considered in patients with even mild developmental disability and/or unexplained progressive cerebellar atrophy.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Is "option B+" also being adopted in pregnant women in high-income countries? Temporal trends from a national study in Italy. - Floridia, Marco; Guaraldi, Giovanni; Ravizza, Marina; Tibaldi, Cecilia; Pinnetti, Carmela; Maccabruni, Anna; Molinari, Atim; Liuzzi, Giuseppina; Alberico, Salvatore; Meloni, Alessandra; Rizzi, Laura; Dalzero, Serena; et al. (Clin Infect Dis, 2015)
Keywords: Anti-Retroviral Agents; Antiretroviral Therapy, Highly Active; Developed Countries; Female; HIV Infections; Humans; Infant, Newborn; Italy; Patient Acceptance of Health Care; Pregnancy; Pregnancy Complications, Infectious

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

Persistent viremia and urine shedding of tick-borne encephalitis virus in an infected immunosuppressed patient from a new epidemic cluster in North-Eastern Italy. - Caracciolo, Ilaria; Bassetti, Matteo; Paladini, Giorgio; Luzzati, Roberto; Santon, Daniela; Merelli, Maria; Sabbata, Giovanni De; Carletti, Tea; Marcello, Alessandro; D'Agaro, Pierlanfranco (J Clin Virol, 2015)
A persistent tick-borne encephalitis virus infection in an immune-suppressed patient is presented. Such an unusual clinical case offers the unique chance of detecting persistent viremia associated to the erythrocyte fraction and shedding of the virus in the urine for more than six weeks. The infection occurred in a new area of the Friuli Venezia-Giulia region (North Eastern Italy) where two additional cases are also being reported.

Phenotypic and genetic characterization of a family carrying two Xq21.1-21.3 interstitial deletions associated with syndromic hearing loss. - Iossa, Sandra; Costa, Valerio; Corvino, Virginia; Auletta, Gennaro; Barruffo, Luigi; Cappellani, Stefania; Ceglia, Carlo; Cennamo, Giovanni; d'Adamo, Adamo Pio; D'Amico, Alessandra; Di Paolo, Nilde; Forte, Raimondo; et al. (Mol Cytogenet, 2015)
BACKGROUND: Sensorineural hearing impairment is a common pathological manifestation in patients affected by X-linked intellectual disability. A few cases of interstitial deletions at Xq21 with several different phenotypic characteristics have been described, but to date, a complete molecular characterization of the deletions harboring disease-causing genes is still missing. Thus, the aim of this study is to realize a detailed clinical and molecular analysis of a family affected by syndromic X-linked hearing loss with intellectual disability. RESULTS: Clinical analyses revealed a very complex phenotype that included inner ear malformations, vestibular problems, choroideremia and hypotonia with a peculiar pattern of phenotypic variability. Genomic analysis revealed, for the first time, the presence of two close interstitial deletions in the Xq21.1-21.3, harboring 11 protein coding, 9 non-coding genes and 19 pseudogenes. Among these, 3 protein coding genes have already been associated with X-linked hearing loss, intellectual disability and choroideremia. CONCLUSIONS: In this study we highlighted the presence of peculiar genotypic and phenotypic details in a family affected by syndromic X-linked hearing loss with intellectual disability. We identified two, previously unreported, Xq21.1-21.3 interstitial deletions. The two rearrangements, containing several genes, segregate with the clinical features, suggesting their role in the pathogenicity. However, not all the observed phenotypic features can be clearly associated with the known genes thus, further study is necessary to determine regions involved.

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

PRE- AND POSTNATAL MODIFICATIONS IN PARENTAL MENTAL REPRESENTATIONS IN THREE CASES OF FETAL GASTROSCHISIS DIAGNOSED DURING PREGNANCY. - Tripani, Antonella; Pellizzoni, Sandra; Giuliani, Rosella; Bembich, Stefano; Clarici, Andrea; Lonciari, Isabella; Ammaniti, Massimo (Infant Ment Health J, 2015)
The aim of this study was to identify possible effects of gastroschisis on parents' intrapsychic dynamics by applying an observational clinical approach. More specifically, we intend to (a) evaluate the representational style of parents informed about the diagnosis of fetal gastroschisis during pregnancy using the Interview of Maternal Representations During Pregnancy and the Interview of Paternal Representations During Pregnancy (M. Ammaniti, C. Candelori, M. Pola, & R. Tambelli, ) and (b) observe whether the baby's birth influences the parents' representational styles through the application of the same tools (the Interview of Maternal Representations After the Birth, M. Ammaniti & R. Tambelli, , and the Interview of Paternal Representations After the Birth, M. Ammaniti & R. Tambelli, ), adapted to the postnatal period. During the prenatal period, all parents showed a restricted/disinvested style. Three parents-one mother and two fathers-changed their styles from restricted/disinvested to integrated between pregnancy and Month 6 after the birth of their child. Clinical data from the interviews and observations are discussed in an attempt at better defining intrapsychic dynamics of parents after a diagnosis of gastroschisis.

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

Reply to Thalidomide Treatment of Pediatric Ulcerative Colitis: A New Use for an Old Drug. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2015)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Risk factors for mortality from acute lower respiratory infections (ALRI) in children under five years of age in low and middle-income countries: a systematic review and meta-analysis of observational studies. - Sonego, Michela; Pellegrin, Maria Chiara; Becker, Genevieve; Lazzerini, Marzia (PLoS One, 2015)
OBJECTIVE: To evaluate risk factors for death from acute lower respiratory infections (ALRI) in children in low- and middle-income countries. DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on risk factors for death from ALRI in children below five years in low- and middle income countries. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to January 2014. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 10,655 papers retrieved, 77 studies from 39 countries (198,359 children) met the inclusion criteria. Host and disease characteristics more strongly associated with ALRI mortality were: diagnosis of very severe pneumonia as per WHO definition (odds ratio 9.42, 95% confidence interval 6.37‒13.92); age below two months (5.22, 1.70‒16.03); diagnosis of Pneumocystis Carinii (4.79, 2.67‒8.61), chronic underlying diseases (4.76, 3.27‒6.93); HIV/AIDS (4.68, 3.72‒5.90); and severe malnutrition (OR 4.27, 3.47‒5.25). Socio-economic and environmental factors significantly associated with increased odds of death from ALRI were: young maternal age (1.84, 1.03‒3.31); low maternal education (1.43, 1.13‒1.82); low socio-economic status (1.62, 1.32‒2.00); second-hand smoke exposure (1.52, 1.20 to 1.93); indoor air pollution (3.02, 2.11‒4.31). Immunisation (0.46, 0.36‒0.58) and good antenatal practices (0.50, 0.31‒0.81) were associated with decreased odds of death. CONCLUSIONS: Host and disease characteristics as well as socio-economic and environmental determinants affect the risk of death from ALRI in children. Together with the prevention and treatment of chronic diseases, interventions to modify underlying risk factors such as poverty, lack of female education, and poor environmental conditions, should be considered among the strategies to reduce ALRI mortality in children in low- and middle-income countries.
Keywords: Child, Preschool; Developing Countries; Environmental Exposure; Humans; Infant; Infant, Newborn; Observational Studies as Topic; Poverty; Respiratory Tract Infections; Risk Factors; Survival Analysis

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Subcutaneous panniculitis-like T-cell lymphoma presenting with diffuse cutaneous edema in a 2-year-old child. - Chinello, Matteo; Naviglio, Samuele; Remotti, Daniele; Locasciulli, Anna; Ventura, Alessandro (J Pediatr Hematol Oncol, 2015)
Keywords: Child, Preschool; Edema; Humans; Lymphoma, T-Cell; Male; Panniculitis; Skin Diseases

Target sequencing approach intended to discover new mutations in non-syndromic intellectual disability. - Morgan, Anna; Gandin, Ilaria; Belcaro, Chiara; Palumbo, Pietro; Palumbo, Orazio; Biamino, Elisa; Dal Col, Valentina; Laurini, Erik; Pricl, Sabrina; Bosco, Paolo; Carella, Massimo; Ferrero, Giovanni Battista; et al. (Mutat Res, 2015)
The technological improvements over the last years made considerable progresses in the knowledge of the etiology of intellectual Disability (ID). However, at present very little is known about the genetic heterogeneity underlying the non-syndromic form of ID (NS-ID). To investigate the genetic basis of NS-ID we analyzed 43 trios and 22 isolated NS-ID patients using a targeted sequencing (TS) approach. 71 NS-ID genes have been selected and sequenced in all subjects. We found putative pathogenic mutations in 7 out of 65 patients. The pathogenic role of mutations was evaluated through sequence comparison and structural analysis was performed to predict the effect of alterations in a 3D computational model through molecular dynamics simulations. Additionally, a deep patient clinical re-evaluation has been performed after the molecular results. This approach allowed us to find novel pathogenic mutations with a detection rate close to 11% in our cohort of patients. This result supports the hypothesis that many NS-ID related genes still remain to be discovered and that NS-ID is a more complex phenotype compared to syndromic form, likely caused by a complex and broad interaction between genes alterations and environment factors.

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

TNF-related apoptosis inducing ligand in ocular cancers and ocular diabetic complications. - Perri, Paolo; Zauli, Giorgio; Gonelli, Arianna; Milani, Daniela; Celeghini, Claudio; Lamberti, Giuseppe; Secchiero, Paola (Biomed Res Int, 2015)
TNF-related apoptosis inducing ligand (TRAIL) is an intensively studied cytokine, in particular for its anticancer activity. The discovery that conjunctival sac fluid contains extremely high levels of soluble TRAIL as compared to other body fluids suggested important implications in the context of the immunological surveillance of the eye, in particular of the anterior surface. In this review, we discuss the potential physiopathologic and therapeutic role of the TRAIL/TRAIL receptor system in a variety of ocular cancers. Moreover, since an increasing amount of data has indicated the important biological activities of the TRAIL/TRAIL receptor systems also in a completely different pathologic context such as diabetes mellitus, in the second part of this review we summarize the currently available data on the involvement of TRAIL in the ocular complications of diabetes mellitus as modulator of the inflammatory and angiogenic response in the eye.
Keywords: Apoptosis; Diabetes Complications; Diabetes Mellitus; Eye Neoplasms; Humans; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

Treatment of asthma based on symptoms. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Asthma; Female; Humans; Male; Spirometry

Ultrastructural Morphology of Sperm from Human Globozoospermia. - Ricci, Giuseppe; Andolfi, Laura; Zabucchi, Giuliano; Luppi, Stefania; Boscolo, Rita; Martinelli, Monica; Zweyer, Marina; Trevisan, Elisa (Biomed Res Int, 2015)
Globozoospermia is a rare disorder characterized by the presence of sperm with round head, lacking acrosome. Coiling tail around the nucleus has been reported since early human studies, but no specific significance has conferred it. By contrast, studies on animal models suggest that coiling tail around the nucleus could represent a crucial step of defective spermatogenesis, resulting in round-headed sperm. No observations, so far, support the transfer of this hypothesis to human globozoospermia. The purpose of this work was to compare ultrastructural morphology of human and mouse model globozoospermic sperm. Sperm have been investigated by using scanning and transmission electron microscopy. The images that we obtained show significant similarities to those described in GOPC knockout mice, an animal model of globozoospermia. By using this model as reference, we were able to identify the probable steps of the tail coiling process in human globozoospermia. Although we have no evidence that there is the same pathophysiology in man and knocked-out mouse, the similarities between these ultrastructural observations in human and those in the experimental model are very suggestive. This is the first demonstration of the existence of relevant morphological homologies between the tail coiling in animal model and human globozoospermia.

Usher syndrome: an effective sequencing approach to establish a genetic and clinical diagnosis. - Lenarduzzi, S; Vozzi, D; Morgan, A; Rubinato, E; D'Eustacchio, A; Osland, T M; Rossi, C; Graziano, C; Castorina, P; Ambrosetti, U; Morgutti, M; Girotto, G (Hear Res, 2015)
Usher syndrome is an autosomal recessive disorder characterized by retinitis pigmentosa, sensorineural hearing loss and, in some cases, vestibular dysfunction. The disorder is clinically and genetically heterogeneous and, to date, mutations in 11 genes have been described. This finding makes difficult to get a precise molecular diagnosis and offer patients accurate genetic counselling. To overcome this problem and to increase our knowledge of the molecular basis of Usher syndrome, we designed a targeted resequencing custom panel. In a first validation step a series of 16 Italian patients with known molecular diagnosis were analysed and 31 out of 32 alleles were detected (97% of accuracy). After this step, 31 patients without a molecular diagnosis were enrolled in the study. Three out of them with an uncertain Usher diagnosis were excluded. One causative allele was detected in 24 out 28 patients (86%) while the presence of both causative alleles characterized 19 patients out 28 (68%). Sixteen novel and 27 known alleles were found in the following genes: USH2A (50%), MYO7A (7%), CDH23 (11%), PCDH15 (7%) and USH1G (2%). Overall, on the 44 patients the protocol was able to characterize 74 alleles out of 88 (84%). These results suggest that our panel is an effective approach for the genetic diagnosis of Usher syndrome leading to: 1) an accurate molecular diagnosis, 2) better genetic counselling, 3) more precise molecular epidemiology data fundamental for future interventional plans.
Keywords: Adult; Alleles; Cadherins; Extracellular Matrix Proteins; Female; Genetic Counseling; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; Myosins; Nerve Tissue Proteins; Usher Syndromes

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

Wharton's jelly derived mesenchymal stromal cells: Biological properties, induction of neuronal phenotype and current applications in neurodegeneration research. - Frausin, Stefano; Viventi, Serena; Verga Falzacappa, Lucia; Quattromani, Miriana Jlenia; Leanza, Giampiero; Tommasini, Alberto; Valencic, Erica (Acta Histochem, 2015)
Multipotent mesenchymal stromal cells, also known as mesenchymal stem cells (MSC), can be isolated from bone marrow or other tissues, including fat, muscle and umbilical cord. It has been shown that MSC behave in vitro as stem cells: they self-renew and are able to differentiate into mature cells typical of several mesenchymal tissues. Moreover, the differentiation toward non-mesenchymal cell lineages (e.g. neurons) has been reported as well. The clinical relevance of these cells is mainly related to their ability to spontaneously migrate to the site of inflammation/damage, to their safety profile thanks to their low immunogenicity and to their immunomodulation capacities. To date, MSCs isolated from the post-natal bone marrow have represented the most extensively studied population of adult MSCs, in view of their possible use in various therapeutical applications. However, the bone marrow-derived MSCs exhibit a series of limitations, mainly related to their problematic isolation, culturing and use. In recent years, umbilical cord (UC) matrix (i.e. Wharton's jelly, WJ) stromal cells have therefore emerged as a more suitable alternative source of MSCs, thanks to their primitive nature and the easy isolation without relevant ethical concerns. This review seeks to provide an overview of the main biological properties of WJ-derived MSCs. Moreover, the potential application of these cells for the treatment of some known dysfunctions in the central and peripheral nervous system will also be discussed.

A young soccer player with sudden pain after kicking the ball. - Lega, Sara; Rabach, Ingrid; Barbi, Egidio; Ventura, Alessandro (BMJ, 2015)
Keywords: Adolescent; Athletic Injuries; Emergency Medicine; Fractures, Bone; Humans; Ilium; Male; Soccer

Acute-onset pretibial swelling. - Lega, Sara; Rabusin, Marco; Pederiva, Federica (Indian Pediatr, 2014)
Keywords: Bone Marrow Diseases; Child, Preschool; Edema; Female; Granuloma Annulare; Humans; Leg; Tibia

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Association between orofacial granulomatosis and Crohn's disease in children: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Ventura, Alessandro (World J Gastroenterol, 2014)
AIM: To review pediatric cases of orofacial granulomatosis (OFG), report disease characteristics, and explore the association between OFG and Crohn's disease. METHODS: We conducted a systematic review according to the PRISMA guidelines. We searched Medline, LILACS, Virtual Health Library, and Web of Knowledge in September 2013 for cases of OFG in the pediatric age range (< 18 years), with no language limitations. All relevant articles were accessed in full text. The manual search included references of retrieved articles. We extracted data on patients' characteristics, disease characteristics, association with other diseases, and treatment. We analyzed the data and reported the results in tables and text. RESULTS: We retrieved 173 reports of OFG in children. Mean age at onset was 11.1 ± 3.8 years (range: 2.0-18 years). Prevalence in males was significant higher than in females (P < 0.001), with a male:female ratio of 2:1. Gastrointestinal signs or symptoms were present in 26.0% of children at the time of OFG diagnosis. Overall, 70/173 (40.4%) children received a concomitant diagnosis of Crohn's disease. In about half (51.4%) of the cases the onset of OFG anticipated the diagnosis of Crohn's disease, with a mean time between the two diagnoses of 13.1 ± 11.6 mo (range: 3-36 mo). Overall, 21/173 (12.1%) of the children with OFG had perianal disease, while 11/173 (6.4%) had a family history of Crohn's disease. Both perianal disease and a family history of Crohn's disease were significantly associated with a higher risk of Crohn's disease diagnosis in children with OFG [relative risk (RR) = 3.10, 95% confidence interval (CI): 2.46-3.90; RR = 2.74, 95%CI: 2.24-3.36, P < 0.0001 for both). Treatment of OFG included steroids (70.8% of children) and other immunosuppressive drugs (42.7%), such as azathioprine, thalidomide and infliximab. CONCLUSION: High prevalence of Crohn's disease in children with OFG suggests that OFG may be a subtype of Crohn's disease.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Crohn Disease; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Prevalence; Risk Factors; Steroids; Treatment Outcome

Autoimmune hematological diseases after allogeneic hematopoietic stem cell transplantation in children: an Italian multicenter experience. - Faraci, Maura; Zecca, Marco; Pillon, Marta; Rovelli, Attilio; Menconi, Maria Cristina; Ripaldi, Mimmo; Fagioli, Franca; Rabusin, Marco; Ziino, Ottavio; Lanino, Edoardo; Locatelli, Franco; Daikeler, Thomas; et al. (Biol Blood Marrow Transplant, 2014)
Autoimmune hematological diseases (AHDs) may occur after allogeneic hematopoietic stem cell transplantation (HSCT), but reports on these complications in large cohorts of pediatric patients are lacking. Between 1998 and 2011, 1574 consecutive children underwent allogeneic HSCT in 9 Italian centers. Thirty-three children (2.1%) developed AHDs: 15 autoimmune hemolytic anemia (45%), 10 immune thrombocytopenia (30%), 5 Evans' syndrome (15%), 2 pure red cell aplasia (6%), and 1 immune neutropenia (3%). The 10-year cumulative incidence of AHDs was 2.5% (95% confidence interval, 1.7 to 3.6). In a multivariate analysis, the use of alternative donor and nonmalignant disease was statistically associated with AHDs. Most patients with AHDs (64%) did not respond to steroids. Sustained complete remission was achieved in 87% of cases with the anti-CD20 monoclonal antibody (rituximab). Four patients (9%) (1 autoimmune hemolytic anemia, 1 Evans' syndrome, 2 immune thrombocytopenia) died at a median of 87 days after AHD diagnosis as a direct or indirect consequence of their disorder. Our data suggest that AHDs are a relatively rare complication occurring after HSCT that usually respond to treatment with rituximab.
Keywords: Child; Child, Preschool; Female; Hematologic Diseases; Hematopoietic Stem Cell Transplantation; Humans; Italy; Male; Remission Induction; Risk Factors; Transplantation Conditioning

C1q as a unique player in angiogenesis with therapeutic implication in wound healing. - Bossi, Fleur; Tripodo, Claudio; Rizzi, Lucia; Bulla, Roberta; Agostinis, Chiara; Guarnotta, Carla; Munaut, Carine; Baldassarre, Gustavo; Papa, Giovanni; Zorzet, Sonia; Ghebrehiwet, Berhane; Ling, Guang Sheng; et al. (Proc Natl Acad Sci U S A, 2014)
We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound healing we observed that vessel formation was defective in C1qa(-/-) mice and was restored to normal after local application of C1q. The mean vessel density of wound-healing tissue and the healed wound area were significantly increased in C1q-treated rats. On the basis of these results we suggest that C1q may represent a valuable therapeutic agent that can be used to treat chronic ulcers or other pathological conditions in which angiogenesis is impaired, such as myocardial ischemia.
Keywords: Animals; Cell Proliferation; Complement C1q; DNA Primers; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Human Umbilical Vein Endothelial Cells; Humans; Immunoblotting; Immunohistochemistry; In Situ Hybridization; Mice; Mice, Inbred C57BL; Mice, Knockout; Neovascularization, Physiologic; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Wound Healing

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

Cow's milk allergy in children, from avoidance to tolerance. - Calligaris, Lorenzo; Longo, Giorgio; Badina, Laura; Berti, Irene; Barbi, Egidio (Endocr Metab Immune Disord Drug Targets, 2014)
Food allergy is the primary cause of anaphylaxis in paediatric age affecting roughly 4% of children and their families worldwide, and requiring changes in dietary habits. The prognosis for food allergy in children has traditionally been regarded as good for the most frequent allergens, however the prognosis for cow's milk allergy in the pediatric age is currently considered to be worse than previously believed. There is now enough evidence that measures of avoidance for children at risk did not have any preventive effect whatsoever, but they still came to be counterproductive by avoiding the physiological interaction between food allergens and gastrointestinal mucosal immune system. Programs of specific oral tolerance induction (SOTI) have obtained interesting results in the treatment of food allergy supporting the idea that antigen exposure through gastrointestinal section is important to allow the development of tolerance. Nevertheless this approach is not yet considered "ready" for community recommendations. In this paper we describe our experience in the field of SOTI in children with cow's milk allergy.
Keywords: Animals; Cattle; Child; Child, Preschool; Desensitization, Immunologic; Humans; Immune Tolerance; Milk Hypersensitivity; Milk Substitutes; Retrospective Studies

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Effects of estroprogestins containing natural estrogen on vaginal flora. - De Seta, Francesco; Restaino, Stefano; Banco, Rubina; Conversano, Ester; De Leo, Rossella; Tonon, Maddalena; Maso, Gianpaolo; Barbati, Giulia; Lello, Stefano (Gynecol Endocrinol, 2014)
Estroprogestins with "natural oestrogen" has represented a new option in terms of combined hormonal contraception. So, the aim of this study is to investigate how estroprogestins with natural estrogen may modify the vaginal niche. In literature, very few studies focused on the interaction between hormonal contraception and vaginal milieu. This is a prospective comparative study. We enrolled 60 women from January 2013 to September 2013, 30 of them were administered estradiol valerate dienogest (E2V+DNG - Klaira®) in a quadriphasic regimen, while the other 30 women were administered 17-β estradiol with nomestrol acetate (EV+NOMAC - Zoely®) in a monophasic regimen. After a baseline study of vaginal milieu at recruitment of patients (Gram stain with Nugent score, vaginal pH, vaginal wet mount for the quantification of leukocytes, Lactobacilli and/or presence of Candida), we performed the same follow-up after six months of estroprogestin therapy. Our results showed that the women treated with E2V+DNG had a trend of an improvement of vaginal health in terms of increase of lactobacillar flora and reduction of vaginal pH in place of women treated with EV+NOMAC that showed a reduction of cervical mucus. Finally, our data about the effects on vaginal flora exerted by two estroprogestin pills (EPs) containing a natural estrogen suggest slight, but interesting differences in terms of vaginal ecology. These differences could be related to the type of estrogen, type of progestin, regimen of administration and, after all, to the net balance between estrogenic and progestin component of the EPs.
Keywords: Adolescent; Adult; Drug Combinations; Estradiol; Female; Humans; Megestrol; Middle Aged; Nandrolone; Norpregnadienes; Prospective Studies; Vagina; Young Adult

Expression and replication studies to identify new candidate genes involved in normal hearing function. - Girotto, Giorgia; Vuckovic, Dragana; Buniello, Annalisa; Lorente-Cánovas, Beatriz; Lewis, Morag; Gasparini, Paolo; Steel, Karen P (PLoS One, 2014)
Considerable progress has been made in identifying deafness genes, but still little is known about the genetic basis of normal variation in hearing function. We recently carried out a Genome Wide Association Study (GWAS) of quantitative hearing traits in southern European populations and found several SNPs with suggestive but none with significant association. In the current study, we followed up these SNPs to investigate which of them might show a genuine association with auditory function using alternative approaches. Firstly, we generated a shortlist of 19 genes from the published GWAS results. Secondly, we carried out immunocytochemistry to examine expression of these 19 genes in the mouse inner ear. Twelve of them showed distinctive cochlear expression patterns. Four showed expression restricted to sensory hair cells (Csmd1, Arsg, Slc16a6 and Gabrg3), one only in marginal cells of the stria vascularis (Dclk1) while the others (Ptprd, Grm8, GlyBP, Evi5, Rimbp2, Ank2, Cdh13) in multiple cochlear cell types. In the third step, we tested these 12 genes for replication of association in an independent set of samples from the Caucasus and Central Asia. Nine out of them showed nominally significant association (p<0.05). In particular, 4 were replicated at the same SNP and with the same effect direction while the remaining 5 showed a significant association in a gene-based test. Finally, to look for genotype-phenotype relationship, the audiometric profiles of the three genotypes of the most strongly associated gene variants were analyzed. Seven out of the 9 replicated genes (CDH13, GRM8, ANK2, SLC16A6, ARSG, RIMBP2 and DCLK1) showed an audiometric pattern with differences between different genotypes further supporting their role in hearing function. These data demonstrate the usefulness of this multistep approach in providing new insights into the molecular basis of hearing and may suggest new targets for treatment and prevention of hearing impairment.
Keywords: Adult; Animals; DNA Replication; Gene Expression Profiling; Genome-Wide Association Study; Genotype; Hair Cells, Auditory; Hearing; Humans; Mice; Phenotype; Polymorphism, Single Nucleotide; Stria Vascularis

The first trimester gravid serum regulates procalcitonin expression in human macrophages skewing their phenotype in vitro. - Rami, Damiano; La Bianca, Martina; Agostinis, Chiara; Zauli, Giorgio; Radillo, Oriano; Bulla, Roberta (Mediators Inflamm, 2014)
Procalcitonin (PCT) is one of the best diagnostic and prognostic markers in clinical practice, widely used to evaluate the evolution of bacterial infections. Although it is mainly produced by thyroid, during sepsis almost all the peripheral tissues are involved in PCT production. Parenchymal cells have been suggested as the main source of PCT expression; however the contribution of macrophages is not clear yet. In response to environmental cues, tissue macrophages acquire distinct functional phenotypes, ranging from proinflammatory (M1) to anti-inflammatory (M2) phenotype. Macrophages at the fetal-maternal interface show immunosuppressive M2-like activities required for the maintenance of immunological homeostasis during pregnancy. This study aims to clarify the ability to synthesise PCT of fully differentiated (M0), polarized (M1/M2) macrophages and those cultured either in the presence of first trimester gravid serum (GS) or pregnancy hormones. We found out that M1 macrophages upregulate PCT expression following LPS stimulation compared to M0 and M2. The GS downregulates PCT expression in macrophages, skewing them towards an M2-like phenotype. This effect seems only partially mediated by the hormonal milieu. Our findings strengthen the key role of macrophages in counteracting inflammatory stimuli during pregnancy, suggesting PCT as a possible new marker of M1-like macrophages.
Keywords: Biomarkers; Calcitonin; Cells, Cultured; Chorionic Gonadotropin; Estradiol; Female; Gene Expression Regulation; Homeostasis; Humans; Inflammation; Macrophages; Monocytes; Phenotype; Pregnancy; Pregnancy Trimester, First; Protein Precursors; Serum; Up-Regulation

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Influence of HLA-G polymorphisms in human immunodeficiency virus infection and hepatitis C virus co-infection in Brazilian and Italian individuals. - da Silva, G K; Vianna, Priscila; Veit, Tiago Degani; Crovella, Sergio; Catamo, Eulalia; Cordero, Elvira Alicia Aparicio; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Chies, José Artur Bogo (Infect Genet Evol, 2014)
OBJECTIVE: This study aimed to investigate the role of Human Leukocyte Antigen (HLA)-G in the susceptibility to HIV-1 infection through the analysis of the HLA-G 3' untranslated region (UTR) polymorphisms 14 bp insertion/deletion (rs66554220) and +3142C>G (rs1063320). DESIGN: We analyzed 582 HIV-1 infected patients and 626 uninfected individuals from Brazil and Italy in a case-control study. METHODS: HLA-G polymorphisms were genotyped using PCR, PCR-RFLP assays or direct sequencing. All analyses were stratified by ethnicity. Genotypic, allelic and diplotypic frequencies were compared between HIV-1 infected subjects and controls using Chi-square or Fischer exact tests. Also, haplotypic frequencies were estimated using MLocus software. RESULTS: African-derived HIV-infected individuals presented a higher frequency of the 14 bp insertion allele as compared to non-infected individuals (0.468 versus 0.373, respectively; p(Bonf) = 0.010). A higher frequency of the 14 bp insertion +3142G (insG) haplotype (0.456 versus 0.346, p<0.001) and the insG/insG diplotype (OR=1.88, 95%CI = 1.08-3.23, p=0.021) was observed among African-derived patients as compared to uninfected controls. Also, we observed a higher frequency of the ins/ins genotype among African-derived HIV patients co-infected with HCV (OR=2.78, 95%CI = 1.20-6.49, p = 0.008). CONCLUSIONS: Our data point out to an increased frequency of alleles and genotypes associated with low HLA-G expression among African-derived patients, suggesting a potential role for HLA-G in the susceptibility to HIV-1 infection and HCV co-infection in those individuals.
Keywords: 3' Untranslated Regions; Adolescent; Adult; African Continental Ancestry Group; Aged; Brazil; Coinfection; Gene Frequency; Genetic Variation; Haplotypes; Hepatitis C; HIV Infections; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

NLRP3 polymorphism is associated with protection against human T-lymphotropic virus 1 infection. - Kamada, Anselmo Jiro; Pontillo, Alessandra; Guimarães, Rafael Lima; Loureiro, Paula; Crovella, Sergio; Brandão, Lucas André Cavalcanti (Mem Inst Oswaldo Cruz, 2014)
Inter-individual heterogeneity in the response to human T-lymphotropic virus 1 (HTLV-1) infection has been partially attributed to host genetic background. The antiviral activity of the inflammasome cytoplasmic complex recognises viral molecular patterns and regulates immune responses via the activation of interleukin (IL)-1 family (IL-1, IL-18 and IL-33) members. The association between polymorphisms in the inflammasome receptors NLRP1 and NLRP3 and HTLV-1 infection was evaluated in a northeastern Brazilian population (84 HTLV-1 carriers and 155 healthy controls). NLRP3 rs10754558 G/G was associated with protection against HTLV-1 infection (p = 0.012; odds ratio = 0.37). rs10754558 affects NLRP3 mRNA stability; therefore, our results suggest that higher NLRP3 expression may augment first-line defences, leading to the effective protection against HTLV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Female; Genetic Predisposition to Disease; HTLV-I Infections; Human T-lymphotropic virus 1; Humans; Inflammasomes; Interleukin-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protective Factors

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities

A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Rhythm perception and production predict reading abilities in developmental dyslexia. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Front Hum Neurosci, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia-a learning disability that affects reading acquisition despite normal intelligence and adequate education-have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

Serum amyloid protein A concentration in cryopyrin-associated periodic syndromes patients treated with interleukin-1 beta antagonist. - Pastore, Serena; Paloni, Giulia; Caorsi, Roberta; Ronfani, Luca; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2014)
OBJECTIVES: Cryopyrin-associated periodic syndromes (CAPS) are a group of chronic, relapsing autoinflammatory disorders which may be complicated by systemic AA amyloidosis. The aim of our study was to evaluate serum amyloid protein A (SAA) level in CAPS patients treated with Interleukin-1beta (IL-1β) antagonist and to correlate its level with treatment response. METHODS: All patients of CAPS Italian Register treated with IL-1β inhibitor were enrolled. SAA levels before starting therapy, and at last visit were evaluated. Patients were then divided in complete responders and partial responders. RESULTS: Twenty-five patients were enrolled. SAA level before starting therapy was increased (median 118.5 mg/L, IQR 96.4-252.8; normal value <6.4 mg/L), while at last visit SAA was significantly reduced (median 4.3 mg/L, IQR 2.3-12.7) (p<0.001). However 12 patients still presented SAA levels beyond normal range, 10/25 patients (40%) showed a complete response to treatment. Conversely, 15 patients presented only a partial response, of which 12 for increased SAA value and 3 for increased CRP value. Patients with partial response had SAA values significantly higher than patients with complete response (median 12.6 mg/L; IQR 8.3-20.0 vs. 2.7 mg/L; IQR 1.6-4.1, p<0.001). CONCLUSIONS: Our results confirm the long term efficacy of anti IL-1β treatment in CAPS and the decrease of SAA levels; however 48% of patients still presented SAA elevation despite treatment. The real risk of these patients in developing amyloidosis is not clear but the persistent increase of SAA needs a close follow-up.
Keywords: Adolescent; Adult; Amyloidosis; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Drug Monitoring; Female; Humans; Immunosuppressive Agents; Interleukin-1beta; Male; Middle Aged; Serum Amyloid A Protein; Treatment Outcome; Young Adult

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Severe neonatal hyperbilirubinemia and UGT1A1 promoter polymorphism. - Travan, Laura; Lega, Sara; Crovella, Sergio; Montico, Marcella; Panontin, Elisa; Demarini, Sergio (J Pediatr, 2014)
OBJECTIVE: To assess whether UGT1A1 promoter polymorphisms associated with Gilbert Syndrome (GS) occur with a greater frequency in neonates with severe hyperbilirubinemia. STUDY DESIGN: In a case-control study performed at a single hospital center in Italy, 70 case subjects with severe hyperbilirubinemia (defined as bilirubin level ≥20 mg/dL or 340 μmol/L) and 70 controls (bilirubin level <12 mg/dL or 210 μmol/L) were enrolled. Both case and control subjects were full term newborns. Polymerase chain reaction analysis on blood spot was performed to determine the frequency of UGTA1A1 promoter polymorphisms in cases and controls. RESULTS: No statistical difference in the prevalence of UGTA1A1 gene variants was found between cases and controls (P = 1). Thirteen infants homozygous for (TA)7 polymorphism associated with GS were in the case group (18.6%) and 14 in the control group (20.0%). A heterozygous group was also equally distributed between cases (44.3%) and controls (42.9%). No (TA)8 repeat was found in the 2 groups. CONCLUSIONS: In our study population, GS polymorphism alone does not appear to play a major role in severe neonatal hyperbilirubinemia in neonates without signs of hemolysis.
Keywords: Case-Control Studies; Female; Genotype; Gilbert Disease; Glucuronosyltransferase; Humans; Hyperbilirubinemia, Neonatal; Infant, Newborn; Male; Polymerase Chain Reaction; Polymorphism, Genetic; Prevalence; Promoter Regions, Genetic

Short communication: novel truncating mutations in the CFTR gene causing a severe form of cystic fibrosis in Italian patients. - Lenarduzzi, S; Morgutti, M; Crovella, S; Coiana, A; Rosatelli, M C (Genet Mol Res, 2014)
Cystic fibrosis (CF) is a common recessive genetic disease caused by mutations in the gene encoding for the cystic fibrosis transmembrane conductance regulator (CFTR) protein. More than 1800 different mutations have been described to date. Here, we report 3 novel mutations in CFTR in 3 Italian CF patients. To detect and identify 36 frequent mutations in Caucasians, we used the INNO-LiPA CFTR19 and INNO-LiPA CFTR17+Tn Update kits (Innogenetics; Ghent, Belgium). Our first analysis did not reveal both of the responsible mutations; thus, direct sequencing of the CFTR gene coding region was performed. The 3 patients were compound heterozygous. In one allele, the F508del (c.1521_1523delCTT, p.PHE508del) mutation in exon 11 was observed in each case. For the second allele, in patient No.1, direct sequencing revealed an 11-base pair deletion (GAGGCGATACT) in exon 14 (c.2236_2246del; pGlu746Alafs*29). In patient No. 2, direct sequencing revealed a nonsense mutation at nucleotide 3892 (c.3892G>T) in exon 24. In patient No. 3, direct sequencing revealed a deletion of cytosine in exon 27 (c.4296delC; p.Asn1432Lysfs*16). These 3 novel mutations indicate the production of a truncated protein, which consequently results in a non-functional polypeptide.
Keywords: Alleles; Base Sequence; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; DNA Mutational Analysis; Exons; Female; Heterozygote; Humans; Infant; Infant, Newborn; Italy; Molecular Sequence Data; Mutation; Open Reading Frames; Severity of Illness Index

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Teleradiology for remote consultation using iPad improves the use of health system human resources for paediatric fractures: prospective controlled study in a tertiary care hospital in Italy. - Zennaro, Floriana; Grosso, Daniele; Fascetta, Riccardo; Marini, Marta; Odoni, Luca; Di Carlo, Valentina; Dibello, Daniela; Vittoria, Francesca; Lazzerini, Marzia (BMC Health Serv Res, 2014)
BACKGROUND: The growing cost of health care and lack of specialised staff have set e-Health high on the European political agenda. In a prospective study we evaluated the effect of providing images for remote consultation through an iPad on the number of in-hospital orthopaedic consultations for children with bone fractures. METHODS: Children from 0 to 18 years diagnosed with a bone fracture by the radiologist during the hours when an orthopaedic service is provided only on-call were eligible for enrollment. Cases were enrolled prospectively during September and October 2013. A standard approach (verbal information only, no X-Ray provided remotely) was compared to an experimental approach (standard approach plus the provision of X-ray for remote consultation through an iPad). The primary outcome was the number of orthopaedic in-hospital consultations that occurred. Other outcomes included: immediate activation of other services; time needed for decision-making; technical difficulties; quality of images and diagnostic confidence (on a likert scale of 1 to 10). RESULTS: Forty-two children were enrolled in the study. Number of in-hospital consultancies dropped from 32/42 (76.1%) when no X-ray was provided to 16/42 (38%) when the X-rays was provided (p < 0.001). With remote X-ray consultation in 14/42 (33.3%) cases services such as surgery and plaster room could be immediately activated, compared to no service activated without teleradiology (p < 0.001). Average time for decision making was 23.4 ± 21.8 minutes with remote X-ray consultation, compared to 56.2 ± 16.1 when the X-ray was not provided (p < 0.001). The comparison between images on the iPad and on the standard system for X- Ray visualisation resulted in a non statistically significant difference in the quality of images (average score 9.89 ± 0.37 vs 9.91 ± 0.30; p = 0.79), and in non statistically significant difference in diagnostic confidence (average score 9.91 ± 0.32 vs 9.92 ± 0.31; p = 0.88). CONCLUSIONS: Remote X-ray consultation through Aycan OsiriX PRO and iPad should be considered as a means for reducing the need of in-hospital orthopaedic consultation during on-call times, and potentially decrease the cost of care for the health system. In the future, alternative systems less expensive than Aycan OsiriX PRO should be further developed and tested.
Keywords: Adolescent; Child; Child, Preschool; Computers, Handheld; Decision Making; Fractures, Bone; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Remote Consultation; Teleradiology; Time Factors

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Use of placebo in a trial of thalidomide for pediatric Crohn disease--reply. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (JAMA, 2014)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Amenorrhea in women treated with thalidomide: report of two cases and literature review. - Lazzerini, Marzia; Bramuzzo, Matteo; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Ventura, Alessandro (Inflamm Bowel Dis, 2013)
Keywords: Adolescent; Amenorrhea; Colitis, Ulcerative; Crohn Disease; Female; Humans; Review Literature as Topic; Thalidomide

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Under pressure. - De Cunto, Angela; Berti, Irene; Minute, Marta; Longo, Giorgio (Eur J Pediatr, 2013)
Physical urticaria is a rare but challenging subset of chronic urticaria. Wheals of pressure urticaria are typically delayed in appearance. A pressure test can easily be done to confirm the diagnosis.
Keywords: Child; Humans; Male; Pressure; Urticaria

Accuracy of diagnostic antibody tests for coeliac disease in children: summary of an evidence report. - Giersiepen, Klaus; Lelgemann, Monika; Stuhldreher, Nina; Ronfani, Luca; Husby, Steffen; Koletzko, Sibylle; Korponay-Szabó, Ilma R (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: The aim of this study was to summarise the evidence from 2004 to September 2009 on the performance of laboratory-based serological and point of care (POC) tests for diagnosing coeliac disease (CD) in children using histology as reference standard. PATIENTS AND METHODS: We searched MEDLINE and EMBASE for studies reporting on children for tests based on IgA and IgG anti-gliadin (AGA), endomysial (EmA), anti-transglutaminase-2 (TG2), and anti-deamidated gliadin peptides (DGP) antibodies or POC tests. For inclusion, histological analysis of duodenal biopsies and sensitivity and specificity for index tests had to be reported. Data were pooled and summary measures calculated for sensitivity, specificity, positive and negative likelihood ratios ("LR+", "LR-"), and diagnostic odds ratios (DOR). In case of elevated statistical heterogeneity, studies reaching 90% sensitivity or specificity were reported. RESULTS: A total of 2510 articles were reviewed; 16 entered meta-analysis, reporting on 3110 patients (1876 with CD, 1234 without CD). For IgA-EmA, sensitivity was ≥90% in 7/11 studies and pooled specificity 98.2%. For IgA-anti-TG2, 11/15 studies yielded sensitivities ≥90% and 13/15 specificities ≥90%. For IgA-DGP, sensitivity ranged between 80.7% and 95.1% (specificity 86.3%-93.1%); for IgG-DGP between 80.1% and 98.6% (specificity 86.0-96.9%). IgA-EmA had the highest pooled DOR (554) and LR+ (31.8) for a laboratory test, followed by IgA-anti-TG2, IgG-DGP, IgA-DGP and IgA-AGA. POC tests showed a pooled sensitivity of 96.4% for IgA-TG2 (specificity 97.7%). CONCLUSIONS: IgA-EmA and IgA-anti-TG2 tests appear highly accurate to diagnose CD. IgG-anti-DGP tests may help in excluding CD. IgA-AGA and IgA-DGP tests show inferior accuracy. POC tests may achieve high accuracy in the hands of experienced readers, but IgA-anti-TG2/EmA were superior.
Keywords: Autoantibodies; Biological Markers; Celiac Disease; Child; Gliadin; GTP-Binding Proteins; Humans; Immunoglobulin A; Immunoglobulin G; Point-of-Care Systems; Sensitivity and Specificity; Transglutaminases

Adverse effects during specific oral tolerance induction: in home phase. - Barbi, E; Longo, G; Berti, I; Matarazzo, L; Rubert, L; Saccari, A; Lenisa, I; Ronfani, L; Radillo, O; Ventura, A (Allergol Immunopathol (Madr), 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach for severe food allergies. There are little data in the literature regarding the home-phase of SOTI, not only with regard to type and frequency of adverse reactions but also regarding the most suitable treatment and protocol. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of the home-phase of an original SOTI protocol in a large group of children with severe cow's milk (CM) allergy, after the hospital "rush" phase. METHODS: The study was conducted by recording in-home phase adverse events, success and failure as reported by parents, and calling families. Adverse reactions were treated following the International Guidelines, arbitrarily modified by introducing nebulised epinephrine for respiratory reactions, oral beclomethasone for acute gastric pain and oral cromolyn for recurrent gastric pain. RESULTS: Out of 140 patients, 132 were contacted; eight were inaccessible (follow-up 2-84 months). The number of adverse reactions was 1 in every 100 doses. The reactions were treated with nebulised epinephrine (221 reactions), IM epinephrine (6 reactions), and other drugs. Patients with high specific IgE levels (greater than 100 kU(A)/L) and lower CM dose (less than 5 ml) at the end of in-hospital phase showed a higher risk both for number of reactions and use of nebulised epinephrine. CONCLUSIONS: The home phase of SOTI was characterised by a significant number of adverse reactions, mostly managed with an acceptable rate of side effects. Nebulised epinephrine played a pivotal role in respiratory reactions.
Keywords: Adolescent; Adult; Age Factors; Allergens; Child; Child, Preschool; Desensitization, Immunologic; Epinephrine; Female; Food Hypersensitivity; Humans; Immune Tolerance; Immunoglobulin E; Male; Milk Hypersensitivity; Nebulizers and Vaporizers

Adverse effects during specific oral tolerance induction: in-hospital "rush" phase. - Barbi, E; Longo, G; Berti, I; Neri, E; Saccari, A; Rubert, L; Matarazzo, L; Montico, M; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach in the treatment of severe food allergies. Different protocols have demonstrated its efficacy. Nevertheless, SOTI is still considered an experimental method and should be limited to highly controlled settings. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of nebulized epinephrine as a first-line treatment of respiratory reactions during in-hospital SOTI for cow's milk allergy. MATERIALS AND METHODS: A retrospective study was conducted by reviewing the medical records of patients admitted for SOTI beginning in 2001. Reactions were classified as mild, moderate and severe on a partially modified Clark scale. Adverse reactions were treated following the International Guidelines with the introduction of nebulized epinephrine for level four reactions. RESULTS: Of 209 patients, 17 were excluded due to the absence of objective reactions. The remaining 192 were classified as follows: Mild Reactions (Clark Scale 1 to 3): 100 patients received either no treatment, oral antihistamines or nebulized steroids; Moderate Reactions (Clark Scale 4): 87 patients treated with nebulized epinephrine and, depending on their symptoms, oral antihistamines, corticosteroids (nebulized, oral or IV) or nebulized beta 2 agonists; Severe Reactions (Clark Scale 5): 5 children, 4 of whom initially underwent one nebulization of epinephrine and eventually required an IM dose. The fifth patient was immediately treated with IM epinephrine due to hypotension. DISCUSSION: adverse reactions during this in-hospital SOTI protocol were frequent but easily manageable. Nebulized epinephrine can play a relevant role in the treatment of respiratory reactions.
Keywords: Administration, Inhalation; Anaphylaxis; Animals; Bronchodilator Agents; Child; Desensitization, Immunologic; Epinephrine; Humans; Milk; Milk Hypersensitivity; Retrospective Studies

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

CD14 polymorphisms correlate with an augmented risk for celiac disease in Italian patients. - Catamo, E; Segat, L; Lenarduzzi, S; Petix, V; Morgutti, M; Crovella, S (Genes Immun, 2012)
Celiac disease (CD) is a T-cell-mediated chronic inflammatory disease characterized by autoimmune, immunological and environmental components, where genetic factors in addition to the main known risk factors (gliadin and human leukocyte antigen (HLA)-DQ haplotypes) are supposed to be involved. CD14 is a multifunctional receptor involved in the bacterial lipopolysaccharides-dependent signal transduction. The CD14 gene maps on the long arm of chromosome 5 (5q22-q32), a 'hotbed' region for CD; promoter polymorphisms are known to influence its expression. In this study we analyzed three CD14 promoter polymorphisms (c.-1359G>T, c.-1145A>G and c.-159C>T, ) in 938 CD Italian patients and 533 healthy controls, with known HLA-DQ haplotypes, with the aim of evaluating their possible association with the disease. The c.-1145A>G G and c.-159C>T T alleles (as well as the combination of the two alleles in the GT haplotype), were identified as susceptibility factors for CD development, being significantly more frequent in CD patients than in healthy controls. This association was also confirmed when the analysis was restricted to only those subjects characterized by HLA-DQ risk haplotypes. Our results indicate the involvement of CD14 gene polymorphisms in the susceptibility to CD.
Keywords: Adolescent; Adult; Aged; Antigens, CD14; Case-Control Studies; Celiac Disease; Child; Child, Preschool; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA Antigens; Humans; Infant; Italy; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Clinical and laboratory features of 103 patients from 42 Italian families with inherited thrombocytopenia derived from the monoallelic Ala156Val mutation of GPIbα (Bolzano mutation). - Noris, Patrizia; Perrotta, Silverio; Bottega, Roberta; Pecci, Alessandro; Melazzini, Federica; Civaschi, Elisa; Russo, Sabina; Magrin, Silvana; Loffredo, Giuseppe; Di Salvo, Veronica; Russo, Giovanna; Casale, Maddalena; et al. (Haematologica, 2012)
BACKGROUND: Bernard-Soulier syndrome is a very rare form of inherited thrombocytopenia that derives from mutations in GPIbα, GPIbβ, or GPIX and is typically inherited as a recessive disease. However, some years ago it was shown that the monoallelic c.515C>T transition in the GPIBA gene (Bolzano mutation) was responsible for macrothrombocytopenia in a few Italian patients. DESIGN AND METHODS: Over the past 10 years, we have searched for the Bolzano mutation in all subjects referred to our institutions because of an autosomal, dominant form of thrombocytopenia of unknown origin. RESULTS: We identified 42 new Italian families (103 cases) with a thrombocytopenia induced by monoallelic Bolzano mutation. Analyses of the geographic origin of affected pedigrees and haplotypes indicated that this mutation originated in southern Italy. Although the clinical expression was variable, patients with this mutation typically had a mild form of Bernard-Soulier syndrome with mild thrombocytopenia and bleeding tendency. The most indicative laboratory findings were enlarged platelets and reduced GPIb/IX/V platelet expression; in vitro platelet aggregation was normal in nearly all of the cases. CONCLUSIONS: Our study indicates that monoallelic Bolzano mutation is the most frequent cause of inherited thrombocytopenia in Italy, affecting 20% of patients recruited at our institutions during the last 10 years. Because many people from southern Italy have emigrated during the last century, this mutation may have spread to other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bernard-Soulier Syndrome; Child; Child, Preschool; Family Health; Female; Heterozygote; Humans; Infant; Italy; Male; Membrane Glycoproteins; Middle Aged; Mutation, Missense; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Genetic; Thrombocytopenia; Thrombopoietin; Tubulin; Young Adult

Dealing with abdominal pain in children affected by systemic lupus erythematosus. - Taddio, Andrea; Rosé, Carlos; Lepore, Loredana; Ventura, Alessandro (Semin Arthritis Rheum, 2012)
Keywords: Abdominal Pain; Female; Humans; Lupus Erythematosus, Systemic; Male

Diagnosed child, treated child: food challenge as the first step toward tolerance induction in cow's milk protein allergy. - Longo, G; Berti, I; Barbi, E; Calligaris, L; Matarazzo, L; Radillo, O; Ronfani, L; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Food challenge is required to assess tolerance in cow milk (CM) allergy. A positive challenge contraindicates the reintroduction of CM. Specific oral tolerance induction (SOTI) is a promising treatment. METHODS: All children admitted for a challenge were prospectively enrolled. To those tolerating between 2 and 150 ml a SOTI protocol was offered. Outcome, adverse reactions, parents' satisfaction were recorded. RESULTS: Out of 245 challenged patients, 175 reacted 122 out of 125, able to tolerate a minimum dose of 2 ml, underwent SOTI. After one year 75.4% were in an unrestricted diet, 16.1% tolerated between 5 and 150 ml, 8.5% stopped SOTI. Side effects were mild, parents' satisfaction was very high. CONCLUSIONS: The majority of children tolerating limited amounts of CM at the challenge acquires tolerance with SOTI without relevant side effects. Maintaining on an exclusion diet partially tolerant children should be considered debatable.
Keywords: Administration, Oral; Adolescent; Animals; Cattle; Child; Child, Preschool; Humans; Immune Tolerance; Infant; Milk Hypersensitivity; Milk Proteins; Self Administration

The dietary paradox in food allergy: yesterday's mistakes, today's evidence and lessons for tomorrow. - Badina, Laura; Barbi, Egidio; Berti, Irene; Radillo, Oriano; Matarazzo, Lorenza; Ventura, Alessandro; Longo, Giorgio (Curr Pharm Des, 2012)
During the last decades the prevalence of food allergy has significantly increased among children and antigen avoidance still remains the standard care for the management of this condition. Most reactions are IgE-mediated with a high risk of anaphylaxis requiring emergency medications in case of inadvertent ingestion. Recent studies showed that continuous administration of the offending food, rather than an elimination diet, could promote the development and maintenance of oral tolerance. Indeed, intestinal transit of food proteins and their interaction with gut-associated lymphoid tissue (GALT) is the essential prerequisite for oral tolerance. On the contrary, low-dose cutaneous exposure to environmental foods in children with atopic dermatitis and altered skin barrier facilitates allergic sensitization. The timing and the amount of cutaneous and oral exposure determine whether a child will have allergy or tolerance. Furthermore, previous preventive strategies such as the elimination diet during pregnancy and breastfeeding, prolonged exclusive breastfeeding and delayed weaning to solid foods did not succeed in preventing the development of food allergy. On the other hand, there could be an early narrow window of immunological opportunity to expose children to allergenic foods and induce natural tolerance. Finally, the gradual exposure to the offending food through special protocols of specific oral tolerance induction (SOTI) may be a promising approach to a proactive treatment of food allergy.
Keywords: Anaphylaxis; Antigens; Breast Feeding; Child; Dermatitis, Atopic; Female; Food Hypersensitivity; Humans; Immunoglobulin E; Pregnancy; Time Factors

Efficacy of rifaximin vaginal tablets in treatment of bacterial vaginosis: a molecular characterization of the vaginal microbiota. - Cruciani, Federica; Brigidi, Patrizia; Calanni, Fiorella; Lauro, Vittoria; Tacchi, Raffaella; Donders, Gilbert; Peters, Klaus; Guaschino, Secondo; Vitali, Beatrice (Antimicrob Agents Chemother, 2012)
Bacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, double-blind, randomized, placebo-controlled study. An integrated molecular approach based on quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the effects of vaginal tablets containing the antibiotic. An increase in members of the genus Lactobacillus and a decrease in the BV-related bacterial groups after the antibiotic treatment were demonstrated by qPCR. PCR-DGGE profiles confirmed the capability of rifaximin to modulate the composition of the vaginal microbial communities and to reduce their complexity. This molecular analysis supported the clinical observation that rifaximin at 25 mg/day for 5 days represents an effective treatment to be used in future pivotal studies for the treatment of BV.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Double-Blind Method; Female; Humans; Lactobacillus; Metagenome; Middle Aged; Rifamycins; RNA, Ribosomal, 16S; Vagina; Vaginal Creams, Foams, and Jellies; Vaginosis, Bacterial; Young Adult

Endoscopic treatment of primary vesicoureteral reflux. - Pennesi, Marco; L'erario, Ines; Barbi, Egidio (N Engl J Med, 2012)
Keywords: Female; Humans; Ureteroscopy; Vesico-Ureteral Reflux

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Exhaled nitric oxide as a guide to management of asthma in pregnancy. - Bibalo, Chiara; Badina, Laura; Longo, Giorgio; Ventura, Alessandro (Lancet, 2012)
Keywords: Asthma; Breath Tests; Female; Glucocorticoids; Humans; Nitric Oxide; Pregnancy; Pregnancy Complications

Extra-large letter spacing improves reading in dyslexia. - Zorzi, Marco; Barbiero, Chiara; Facoetti, Andrea; Lonciari, Isabella; Carrozzi, Marco; Montico, Marcella; Bravar, Laura; George, Florence; Pech-Georgel, Catherine; Ziegler, Johannes C (Proc Natl Acad Sci U S A, 2012)
Although the causes of dyslexia are still debated, all researchers agree that the main challenge is to find ways that allow a child with dyslexia to read more words in less time, because reading more is undisputedly the most efficient intervention for dyslexia. Sophisticated training programs exist, but they typically target the component skills of reading, such as phonological awareness. After the component skills have improved, the main challenge remains (that is, reading deficits must be treated by reading more--a vicious circle for a dyslexic child). Here, we show that a simple manipulation of letter spacing substantially improved text reading performance on the fly (without any training) in a large, unselected sample of Italian and French dyslexic children. Extra-large letter spacing helps reading, because dyslexics are abnormally affected by crowding, a perceptual phenomenon with detrimental effects on letter recognition that is modulated by the spacing between letters. Extra-large letter spacing may help to break the vicious circle by rendering the reading material more easily accessible.
Keywords: Attention; Awareness; Child; Dyslexia; Form Perception; France; Humans; Italy; Language; Pattern Recognition, Visual; Phonetics; Reading; Vision, Ocular; Visual Fields

Febrile urinary tract infections in young children: recommendations for the diagnosis, treatment and follow-up. - Ammenti, Anita; Cataldi, Luigi; Chimenz, Roberto; Fanos, Vassilios; La Manna, Angela; Marra, Giuseppina; Materassi, Marco; Pecile, Paolo; Pennesi, Marco; Pisanello, Lorena; Sica, Felice; Toffolo, Antonella; et al. (Acta Paediatr, 2012)
UNLABELLED: We report the recommendations for the diagnosis, treatment, imaging evaluation and use of antibiotic prophylaxis in children with the first febrile urinary tract infection, aged 2 months to 3 years. They were prepared by a working group of the Italian Society of Pediatric Nephrology after careful review of the available literature and a consensus decision, when clear evidence was not available. CONCLUSION: These recommendations are endorsed by the Italian Society of Pediatric Nephrology. They can also be a tool of comparison with other existing guidelines in issues in which much controversy still exists.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Fever; Follow-Up Studies; Humans; Infant; Male; Urinary Tract Infections

Genetics of food preferences: a first view from silk road populations. - Pirastu, Nicola; Robino, Antonietta; Lanzara, Carmela; Athanasakis, Emmanouil; Esposito, Laura; Tepper, Beverly J; Gasparini, Paolo (J Food Sci, 2012)
Food preferences are the main factor driving food intake and choice. There are good reasons to suspect some genetic influence on food acceptance, not least because genetic factors are implicated in a number of factors that are likely to be related to food choice. In addition, some food dislikes show themselves early in life, before there is any evidence for aversive experiences. Although taste has been widely studied in regards of pure tastes such as bitter or sweet perception, the relationship between taste-related genes and food preferences has seldom been explored. In this work we investigated relationship of 37 taste-related genes with food preferences. The study was carried out during a scientific expedition through Caucasus and Central Asia (Silk Road) analyzing more than 400 samples from 5 different countries. A food preference questionnaire was administered to each participant and a DNA sample was obtained. Other information, such as age, sex, life style and anthropometrical measures, were also collected. We found significant associations with variants of: (1) TAS1R2 [Correction added after initial online publication on 27 Aug 2012. TAS1R3 was changed to TAS1R2.] gene and liking of Vodka (P= 1.6 × 10(-3)), white wine (P= 4.0 × 10(-4)) and lamb meat (P= 1.6 × 10(-3)); (2) PCLB2 gene and preference for Hot Tea (P= 8.0 × 10(-4)); (3) TPRV1 gene and beet liking (P= 3.8 × 10(-5)); and (4) ITPR3 gene and liking of both lamb meat (5.8 × 10(-4)) and sheep cheese (8.9×10(-4)). These findings give a new insight on a better understanding, of genetic factors influencing food preferences which is critical to the development of effective dietary interventions, especially for people that may be genetically not predisposed for liking specific nutrients.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Azerbaijan; Child; Choice Behavior; Cohort Studies; Female; Food Habits; Food Preferences; Gene Frequency; Genotype; Georgia; Humans; Kazakhstan; Linear Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Questionnaires; Tajikistan; Taste; Uzbekistan; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. - Snowden, J A; Saccardi, R; Allez, M; Ardizzone, S; Arnold, R; Cervera, R; Denton, C; Hawkey, C; Labopin, M; Mancardi, G; Martin, R; Moore, J J; et al. (Bone Marrow Transplant, 2012)
In 1997, the first consensus guidelines for haematopoietic SCT (HSCT) in autoimmune diseases (ADs) were published, while an international coordinated clinical programme was launched. These guidelines provided broad principles for the field over the following decade and were accompanied by comprehensive data collection in the European Group for Blood and Marrow Transplantation (EBMT) AD Registry. Subsequently, retrospective analyses and prospective phase I/II studies generated evidence to support the feasibility, safety and efficacy of HSCT in several types of severe, treatment-resistant ADs, which became the basis for larger-scale phase II and III studies. In parallel, there has also been an era of immense progress in biological therapy in ADs. The aim of this document is to provide revised and updated guidelines for both the current application and future development of HSCT in ADs in relation to the benefits, risks and health economic considerations of other modern treatments. Patient safety considerations are central to guidance on patient selection and HSCT procedural aspects within appropriately experienced and Joint Accreditation Committee of International Society for Cellular Therapy and EBMT accredited centres. A need for prospective interventional and non-interventional studies, where feasible, along with systematic data reporting, in accordance with EBMT policies and procedures, is emphasized.
Keywords: Autoimmune Diseases; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; European Union; Female; Hematopoietic Stem Cell Transplantation; Humans; Male; Risk Factors; Safety; Severity of Illness Index

How the newly introduced compression, airway, and breathing sequence affects the training in pediatric cardiopulmonary resuscitation. - Lubrano, Riccardo; Messi, Gianni; Elli, Marco (Am J Emerg Med, 2012)
Keywords: Cardiopulmonary Resuscitation; Clinical Competence; Feedback; Female; Heart Massage; Humans; Inservice Training; Male

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

Lutein and zeaxanthin supplementation in preterm infants to prevent retinopathy of prematurity: a randomized controlled study. - Dani, Carlo; Lori, Ilaria; Favelli, Federica; Frosini, Saverio; Messner, Hubert; Wanker, Petra; De Marini, Sergio; Oretti, Chiara; Boldrini, Antonio; Massimiliano, Ciantelli; Bragetti, Patrizia; Germini, Cristiana (J Matern Fetal Neonatal Med, 2012)
OBJECTIVES: Lutein and its isomer zeaxanthin (L/Z) function in the eye as antioxidant agents and blue-light filters. Our aim was to evaluate whether their administration could help decrease the occurrence of retinopathy of prematurity (ROP) in preterm infants. METHODS: Infants with gestational age ≤32 weeks were randomly assigned to receive a daily dose of L/Z (0.14 + 0.006 mg) or placebo until discharge. RESULTS: ROP occurrence was similar in the L/Z (11/58; 19%) and placebo (15/56; 27%) groups, as the occurrence of ROP at each stage and the need of eye surgery. CONCLUSION: L/Z supplementation was ineffective in preventing ROP in preterm infants and did not affect the outcome at discharge of our patients.
Keywords: Antioxidants; Drug Administration Schedule; Drug Combinations; Female; Humans; Infant, Newborn; Infant, Premature; Logistic Models; Lutein; Male; Retinopathy of Prematurity; Risk Factors; Treatment Outcome; Xanthophylls; Zeaxanthins

Managing children under 36 months of age with febrile urinary tract infection: a new approach. - Pennesi, Marco; L'erario, Ines; Travan, Laura; Ventura, Alessandro (Pediatr Nephrol, 2012)
BACKGROUND: Recent guidelines on urinary tract infection (UTI) agree on reducing the number of invasive procedures. None of these has been validated by a long-term study. We describe our 11-years experience in the application of a diagnostic protocol that uses a reduced number of invasive procedures. METHODS: We reviewed retrospectively the records of 406 children aged between 1 and 36 months at their first UTI. All patients underwent renal ultrasound (RUS). Children with abnormal RUS and those with UTI recurrences underwent voiding cystourethrography (VCUG) and dimercaptosuccinic acid (DMSA) renal scans. RESULTS: RUS after the first UTI was pathological in 7.4% children; 4.4 % had a second UTI. We performed 48 VCUG: 14 patients (29%) had vesicoureteral reflux (VUR), 12 of which showed an abnormal RUS while 2 had recurrent UTI. After DMSA renal scan renal damage appeared in only 6 of them (12.5%); all these children showed grade IV VUR. CONCLUSIONS: The application of our guidelines leads to a decrease in invasive examinations without missing any useful diagnoses or compromising the child's health.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Humans; Infant; Male; Pediatrics; Recurrence; Retrospective Studies; Urinary Tract Infections

Mannose-binding lectin and MBL-associated serine protease-2 gene polymorphisms in a Brazilian population from Rio de Janeiro. - Ferraroni, N R; Segat, L; Guimarães, R L; Brandão, L A C; Crovella, S; Constantino-Silva, R N; Loja, C; da Silva Duarte, A J; Grumach, A S (Int J Immunogenet, 2012)
Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encoding gene (MBL2) have been associated, depending upon ethnicity, with several diseases in different populations, little is known about the distribution of MASP2 gene polymorphisms in human populations. The aim of our study was thus to determine the frequencies of MBL2 (exon 1 and promoter) and MASP2 (p.D371Y) polymorphisms in a Brazilian population from Rio de Janeiro. A total of 294 blood donor samples were genotyped for 27 polymorphisms in the MBL2 gene by direct sequencing of a region spanning from the promoter polymorphism H/L rs11003125 to the rs1800451 polymorphism (at codon 57 in the first exon of the gene). Genotyping for MASP2 p.D371Y was carried out using fluorogenic probes. To our knowledge, this is the first study reporting the prevalence of the MASP2 p.D371Y polymorphism in a Brazilian population. The C allele frequency 39% is something intermediate between the reported 14% in Europeans and 90% in Sub-Saharan Africans. MBL2 polymorphisms frequencies were quite comparable to those previously reported for admixed Brazilians. Both MBL2 and MASP2 polymorphisms frequencies reported in our study for the admixed Brazilian population are somehow intermediate between those reported in Europeans and Africans, reflecting the ethnic composition of the southern Brazilian population, estimated to derive from an admixture of Caucasian (31%), African (34%) and Native American (33%) populations. In conclusion, our population genetic study describes the frequencies of MBL2 and MASP2 functional SNPs in a population from Rio de Janeiro, with the aim of adding new information concerning the distribution of these SNPs in a previously unanalysed Brazilian population, thus providing a new genetic tool for the evaluation of the association of MBL2 and MASP2 functional SNPs with diseases in Brazil, with particular emphasis on the state of Rio de Janeiro.
Keywords: Adolescent; Adult; Brazil; Ethnic Groups; Exons; Female; Fluorescent Dyes; Gene Frequency; Genetics, Population; Genome, Human; HapMap Project; Humans; Male; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases; Middle Aged; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Analysis, DNA; Young Adult

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

miR-EdiTar: a database of predicted A-to-I edited miRNA target sites. - Laganà, Alessandro; Paone, Alessio; Veneziano, Dario; Cascione, Luciano; Gasparini, Pierluigi; Carasi, Stefania; Russo, Francesco; Nigita, Giovanni; Macca, Valentina; Giugno, Rosalba; Pulvirenti, Alfredo; Shasha, Dennis; et al. (Bioinformatics, 2012)
MOTIVATION: A-to-I RNA editing is an important mechanism that consists of the conversion of specific adenosines into inosines in RNA molecules. Its dysregulation has been associated to several human diseases including cancer. Recent work has demonstrated a role for A-to-I editing in microRNA (miRNA)-mediated gene expression regulation. In fact, edited forms of mature miRNAs can target sets of genes that differ from the targets of their unedited forms. The specific deamination of mRNAs can generate novel binding sites in addition to potentially altering existing ones. RESULTS: This work presents miR-EdiTar, a database of predicted A-to-I edited miRNA binding sites. The database contains predicted miRNA binding sites that could be affected by A-to-I editing and sites that could become miRNA binding sites as a result of A-to-I editing. AVAILABILITY: miR-EdiTar is freely available online at http://microrna.osumc.edu/mireditar. CONTACT: alessandro.lagana@osumc.edu or carlo.croce@osumc.edu SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Adenosine; Binding Sites; Databases, Genetic; Gene Expression Regulation; Humans; Inosine; Internet; MicroRNAs; Nucleic Acid Conformation; RNA Editing

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

Oral zinc for treating diarrhoea in children. - Lazzerini, Marzia; Ronfani, Luca (Cochrane Database Syst Rev, 2012)
BACKGROUND: In developing countries, diarrhoea causes around two million child deaths annually. Zinc supplementation during acute diarrhoea is currently recommended by the World Health Organization and UNICEF. OBJECTIVES: To evaluate oral zinc supplementation for treating children with acute or persistent diarrhoea. SEARCH METHODS: In February 2012, we searched the Cochrane Infectious Diseases Group Specialized Register, CENTRAL (The Cochrane Library 2011, Issue 11), MEDLINE, EMBASE, LILACS, CINAHL, mRCT, and reference lists. We also contacted researchers. SELECTION CRITERIA: Randomized controlled trials comparing oral zinc supplementation with placebo in children aged one month to five years with acute or persistent diarrhoea, including dysentery. DATA COLLECTION AND ANALYSIS: Both authors assessed trial eligibility and risk of bias, extracted and analysed data, and drafted the review. Diarrhoea duration and severity were the primary outcomes. We summarized dichotomous outcomes using risk ratios (RR) and continuous outcomes using mean differences (MD) with 95% confidence intervals (CI). Where appropriate, we combined data in meta-analyses (using the fixed- or random-effects model) and assessed heterogeneity.The quality of evidence has been assessed using the GRADE methods MAIN RESULTS: Twenty-four trials, enrolling 9128 children, met our inclusion criteria. The majority of the data is from Asia, from countries at high risk of zinc deficiency, and may not be applicable elsewhere.Acute diarrhoeaThere is currently not enough evidence from well conducted randomized controlled trials to be able to say whether zinc supplementation during acute diarrhoea reduces death or hospitalization (very low quality evidence).In children aged greater than six months with acute diarrhoea, zinc supplementation may shorten the duration of diarrhoea by around 10 hours (MD -10.44 hours, 95% CI -21.13 to 0.25; 2091 children, five trials, low quality evidence), and probably reduces the number of children whose diarrhoea persists until day seven (RR 0.73, 95% CI 0.61 to 0.88; 3865 children, six trials, moderate quality evidence). In children with signs of moderate malnutrition the effect appears greater, reducing the duration of diarrhoea by around 27 hours (MD -26.98 hours, 95% CI -14.62 to -39.34; 336 children, three trials, high quality evidence).Conversely, In children aged less than six months, the available evidence suggests zinc supplementation may have no effect on mean diarrhoea duration (MD 5.23 hours, 95% CI -4.00 to 14.45; 1334 children, two trials, low quality evidence), and may even increase the proportion of children whose diarrhoea persists until day seven (RR 1.24, 95% CI 0.99 to 1.54; 1074 children, one trial, moderate quality evidence).No trials reported serious adverse events, but zinc supplementation during acute diarrhoea causes vomiting in both age groups (RR 1.59, 95% 1.27 to 1.99; 5189 children, 10 trials, high quality evidence).Persistent diarrhoeaIn children with persistent diarrhoea, zinc supplementation probably shortens the duration of diarrhoea by around 16 hours (MD -15.84 hours, 95% CI -25.43 to -6.24; 529 children, five trials, moderate quality evidence). AUTHORS' CONCLUSIONS: In areas where the prevalence of zinc deficiency or the prevalence of moderate malnutrition is high, zinc may be of benefit in children aged six months or more.The current evidence does not support the use of zinc supplementation in children below six months of age.
Keywords: Acute Disease; Age Factors; Child; Child, Preschool; Diarrhea; Humans; Infant; Randomized Controlled Trials as Topic; Time Factors; Trace Elements; Zinc

Review of the scientific literature on the health of the Roma and Sinti in Italy. - Monasta, Lorenzo; Erenbourg, Anna; Restaino, Stefano; Lutje, Vittoria; Ronfani, Luca (Ethn Dis, 2012)
BACKGROUND: Roma and Sinti in Italy are excluded from the rest of society, often live in precarious housing conditions and have poor access to health services. In Italy, the Roma and Sinti minority (.3% of the overall population) is scarcely represented if compared with other European countries. METHODS: To establish what is known and how Roma and Sinti health is studied in Italy, we conducted a review of the scientific literature, including articles published between 2000 and 2010, found in Medline, Embase and Web of Science. RESULTS: We analyzed 15 relevant articles out of 32 references. Four papers describe rare autosomal recessive disorders. Four illustrate outbreaks of measles. The remaining papers describe health conditions suffered by this minority. All but two, however, are based on data collected at health services. CONCLUSIONS: The lack of prevalence data and analysis of determinants is a detriment to the health of the Roma and Sinti populations in Italy. Participatory research and evidence-based interventions are needed to improve health outcomes and living conditions of the Roma and Sinti people.
Keywords: Gypsies; Health Services Accessibility; Health Status; Housing; Humans; Italy; Minority Groups; Prejudice

Should cardiac involvement be included in the criteria for diagnosis of Churg Strauss syndrome? - Amaddeo, Alessandro; Ventura, Alessandro; Marchetti, Federico; Benettoni, Alessandra; Londero, Margherita (J Pediatr, 2012)
Keywords: Adolescent; Churg-Strauss Syndrome; Heart Diseases; Humans; Male

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

The submerged dyslexia iceberg: how many school children are not diagnosed? Results from an Italian study. - Barbiero, Chiara; Lonciari, Isabella; Montico, Marcella; Monasta, Lorenzo; Penge, Roberta; Vio, Claudio; Tressoldi, Patrizio Emanuele; Ferluga, Valentina; Bigoni, Anna; Tullio, Alessia; Carrozzi, Marco; Ronfani, Luca (PLoS One, 2012)
BACKGROUND: Although dyslexia is one of the most common neurobehavioral disorders affecting children, prevalence is uncertain and available data are scanty and dated. The objective of this study is to evaluate the prevalence of dyslexia in an unselected school population using clearly defined and rigorous diagnostic criteria and methods. METHODS: Cross sectional study. We selected a random cluster sample of 94 fourth grade elementary school classes of Friuli Venezia Giulia, a Region of North Eastern Italy. We carried out three consecutive levels of screening: the first two at school and the last at the Neuropsychiatry Unit of a third level Mother and Child Hospital. The main outcome measure was the prevalence of dyslexia, defined as the number of children positive to the third level of screening divided by the total number of children enrolled. RESULTS: We recruited 1774 children aged 8-10 years, of which 1528 received parents' consent to participate. After applying exclusion criteria, 1357 pupils constituted the final working sample. The prevalence of dyslexia in the enrolled population ranged from 3.1% (95% CI 2.2-4.1%) to 3.2% (95% CI 2.4-4.3%) depending on different criteria adopted. In two out of three children with dyslexia the disorder had not been previously diagnosed. CONCLUSIONS: This study shows that dyslexia is largely underestimated in Italy and underlines the need for reliable information on prevalence, in order to better allocate resources both to Health Services and Schools.
Keywords: Area Under Curve; Child; Cross-Sectional Studies; Delayed Diagnosis; Dyslexia; Female; Humans; Italy; Male; Neuropsychological Tests; Prevalence; Questionnaires; ROC Curve

Thoracoscopic removal of a bulky cystic mediastinal mature teratoma in a 4-year-old child: report of one case and few surgical tricks. - Codrich, Daniela; Lembo, Maria Antonietta; Schleef, Jurgen (Eur J Pediatr Surg, 2012)
Keywords: Child, Preschool; Female; Humans; Mediastinal Neoplasms; Teratoma; Thoracoscopy; Tomography, X-Ray Computed

Treatment with pamidronate for osteoporosis complicating long-term intestinal failure. - Pastore, S; Londero, M; Barbieri, F; Di Leo, G; Paparazzo, R; Ventura, A (J Pediatr Gastroenterol Nutr, 2012)
Long-term home parenteral nutrition (PN) is a potential risk for developing osteoporosis. Various attempts have been made to treat bone disease both by modifying the composition of PN and by administering hormones, such as calcitonin, parathyroid hormone, and sexual hormones. Bisphosphonates are recognized as a medication useful for the treatment of several bone disorders associated with excessive reabsorption. Nevertheless, there have been no paediatric studies on bisphosphonates use for intestinal failure-associated bone disease. Our study includes 6 paediatric patients receiving extremely long-term home PN (at least 3 years) who showed radiological and clinical signs of osteoporosis. Diagnosis of bone disease was made after a median period of 127.5 PN months. Treatment consisted in 2 cycles of intravenous pamidronate, 30 mg/m once per month for 6 months consecutively. They all showed a significant improvement in bone mineral density, evaluated after 6 and 12 months of pamidronate treatment. In our sample anthropometrical variables (weight, height, and body mass index) are not related with the z-score trend. Our patients had normal levels of calcium, phosphorus, and vitamin D, and proper nutrient intake. At the last follow-up, dual-energy x-ray absorptiometry scan showed that no patients had a z-score lower than -2.5; moreover, nobody developed bone fractures during the 108-month follow-up. The patients did not have any prominent adverse effect. Finally, in our experience, pamidronate is effective for improving bone mineral density and safe in patients with intestinal failure-associated bone disease.
Keywords: Absorptiometry, Photon; Adolescent; Bone Density; Bone Density Conservation Agents; Child; Child, Preschool; Diphosphonates; Female; Humans; Intestinal Diseases; Male; Osteoporosis; Parenteral Nutrition, Home

Acute cardiac valvular involvement in Kawasaki Disease. - Pellegrin, Maria Chiara; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2011)
Keywords: Adrenal Cortex Hormones; Child, Preschool; Female; Heart Valve Diseases; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant; Male; Mucocutaneous Lymph Node Syndrome; Treatment Outcome

Antibiotics in severely malnourished children: systematic review of efficacy, safety and pharmacokinetics. - Lazzerini, Marzia; Tickell, David (Bull World Health Organ, 2011)
OBJECTIVE: To systemically review the evidence in support of World Health Organization guidelines recommending broad-spectrum antibiotics for children with severe acute malnutrition (SAM). METHODS: CENTRAL, MEDLINE, EMBASE, LILACS, POPLINE, CAB Abstracts and ongoing trials registers were searched. Experts were contacted. Conference proceedings and reference lists were manually searched. All study types, except single case reports, were included. FINDINGS: Two randomized controlled trials (RCTs), one before-and-after study and two retrospective reports on clinical efficacy and safety were retrieved, together with 18 pharmacokinetic studies. Trial quality was generally poor and results could not be pooled due to heterogeneity. Oral amoxicillin for 5 days was as effective as intramuscular ceftriaxone for 2 days (1 RCT). For uncomplicated SAM, amoxicillin showed no benefit over placebo (1 retrospective study). The introduction of a standardized regimen using ampicillin and gentamicin significantly reduced mortality in hospitalized children (odds ratio, OR: 4.0; 95% confidence interval, CI: 1.7-9.8; 1 before-and-after study). Oral chloramphenicol was as effective as trimethoprim-sulfamethoxazole in children with pneumonia (1 RCT). Pharmacokinetic data suggest that normal doses of penicillins, cotrimoxazole and gentamicin are safe in malnourished children, while the dose or frequency of chloramphenicol requires adjustment. Existing evidence is not strong enough to further clarify recommendations for antibiotic treatment in children with SAM. CONCLUSION: Large RCTs are needed to define optimal antibiotic treatment in children with SAM with and without complications. Further research into gentamicin and chloramphenicol toxicity and into the pharmacokinetics of ceftriaxone and ciprofloxacin is also required.
Keywords: Anti-Bacterial Agents; Child; Child Nutrition Disorders; Child, Preschool; Humans; Severity of Illness Index; Treatment Outcome

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Atlanto-axial joint involvement as exclusive manifestation of juvenile idiopathic arthritis (JIA). - Taddio, A; Pellegrin, M C; Gregori, M; Wientroub, S; Padeh, S; Lepore, L (Clin Exp Rheumatol, 2011)
Keywords: Antirheumatic Agents; Arthritis, Juvenile; Atlanto-Axial Joint; Child; Dislocations; Female; Glucocorticoids; Humans; Magnetic Resonance Imaging; Pulse Therapy, Drug; Torticollis; Treatment Outcome; Uveitis

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Decreased levels of soluble TNF-related apoptosis-inducing ligand (TRAIL) in the conjunctival sac fluid of patients with diabetes affected by proliferative retinopathy. - Secchiero, P; Perri, P; Melloni, E; Martini, A; Lamberti, G; Sebastiani, A; Zauli, G (Diabet Med, 2011)
Keywords: Apoptosis Regulatory Proteins; Body Fluids; Conjunctiva; Diabetic Retinopathy; Female; Humans; Male; Middle Aged; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

ESPGHAN's 2008 recommendation for early introduction of complementary foods: how good is the evidence? - Cattaneo, Adriano; Williams, Carol; Pallás-Alonso, Carmen Rosa; Hernández-Aguilar, Maria Teresa; Lasarte-Velillas, Juan José; Landa-Rivera, Leonardo; Rouw, Elien; Pina, Mónica; Volta, Alessandro; Oudesluys-Murphy, Anne Marie (Matern Child Nutr, 2011)
Since 2002, the World Health Organization and many governments and professional associations have recommended exclusive breastfeeding for 6 months followed by complementary feeding (giving solid foods alongside breast milk) as optimal infant feeding practice. Several articles have been published challenging this recommendation. Arguably, the most influential has been the 2008 commentary of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Committee on Nutrition, which recommended that complementary foods should be introduced to all infants between 17 and 26 weeks. We challenge the validity of ESPGHAN's position, questioning the adequacy of the literature search, the interpretation and evidence used to reach their conclusions and the balance of an approach that focuses on disease prevention, with scant consideration of growth and neuromotor development. We contend that ESPGHAN's position should be understood as an expert opinion that may be influenced by conflicts of interest. In our view, the ESPGHAN position paper is not evidence based and does not justify a change of the current public health recommendation for 6 months of exclusive breastfeeding. At an individual level, health professionals should understand that developmental readiness for starting solid foods has an age range like other developmental milestones; that fewer infants will probably be ready to start complementary feeding before, rather than after, 6 months; and that their role is to equip parents with the confidence and skills to recognise the signs of developmental readiness. This empowerment process for infants and parents should be preferred over the prescriptive ESPGHAN approach.
Keywords: Breast Feeding; Evidence-Based Practice; Humans; Infant; Infant Food; Infant Nutritional Physiological Phenomena; Milk, Human; Nutritional Status; Public Health; Reproducibility of Results; World Health Organization

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

In vivo distribution of β2 glycoprotein I under various pathophysiologic conditions. - Agostinis, Chiara; Biffi, Stefania; Garrovo, Chiara; Durigutto, Paolo; Lorenzon, Andrea; Bek, Alpan; Bulla, Roberta; Grossi, Claudia; Borghi, Maria O; Meroni, Pierluigi; Tedesco, Francesco (Blood, 2011)
In vitro studies have documented β2 glycoprotein I (β2GPI) binding to endothelial cells (ECs) and trophoblast using antiphospholipid antibodies. The in vivo binding of β2GPI to these cells and the conditions that favor their interaction have not been investigated. We analyzed the in vivo distribution of cyanine 5.5-labeled β2GPI in mice and evaluated the effect of pregnancy and circulating antibodies on its tissue localization. The signal was detected in the liver by whole body scan and ex vivo analysis. The β2GPI failed to bind to the vascular endothelium and reacted only with the ECs of uterine vessels. In pregnant mice the protein was localized on ECs and trophoblast at the embryo implantation sites. Immunized mice showed a similar β2GPI biodistribution to naive mice but the immunized pregnant animals exhibited a significant increase in fetal loss associated with C3 and C9 deposition at the implantation sites. Treatment of mice with LPS after β2GPI-Cy5.5 injection promoted protein localization on gut and brain ECs associated with IgG, C1q, and C9 deposition in immunized mice. These findings indicate that β2GPI binding to EC requires priming with pro-inflammatory factors which is not needed for uterine and placental localization probably dependent on hormonal changes.
Keywords: Animals; beta 2-Glycoprotein I; Complement C1q; Complement C3; Complement C9; Endothelial Cells; Endothelium, Vascular; Female; Fetal Death; Humans; Mice; Mice, Inbred BALB C; Pregnancy; Trophoblasts; Uterus

Interventions for the prevention of overweight and obesity in preschool children: a systematic review of randomized controlled trials. - Monasta, L; Batty, G D; Macaluso, A; Ronfani, L; Lutje, V; Bavcar, A; van Lenthe, F J; Brug, J; Cattaneo, A (Obes Rev, 2011)
The objective of this study was to analyse interventions for the prevention of overweight and obesity in children under 5 years of age. We carried out a systematic review focusing exclusively on randomized controlled trials (RCTs). Data sources include Medline, Cochrane Library, EMBASE, CINHAL, PsychInfo and Web of Science. Data were extracted from seventeen articles describing seven RCTs identified through electronic search, screening of references in systematic reviews, own files and contact with authors. RCTs were assessed with the Jadad scale. Four trials were carried out in preschool settings, one with an exclusive educational component, two with an exclusive physical activity component and one with both. Two trials were family-based, with education and counselling for parents and children. The remaining trial was carried out in maternity hospitals, with a training intervention on breastfeeding. None of the interventions had an effect in preventing overweight and obesity. The failure to show an effect may be due to the choice of outcomes, the quality of the RCTs, the suboptimal implementation of the interventions, the lack of focus on social and environmental determinants. More rigorous research is needed on interventions and on social and environmental factors that could impact on lifestyle.
Keywords: Child Nutrition Sciences; Child Nutritional Physiological Phenomena; Child, Preschool; Exercise; Female; Health Promotion; Humans; Life Style; Male; Obesity; Overweight; Randomized Controlled Trials as Topic

Mannose-binding lectin gene (MBL-2) polymorphism in oral lichen planus. - Barkokebas, Andreza; de Albuquerque T Carvalho, Alessandra; de Souza, Paulo Roberto Eleutério; Gomez, Ricardo Santiago; Xavier, Guilherme Machado; Ribeiro, Camila Maria Beder; Crovella, Sergio; Porter, Stephen Ross; Leão, Jair Carneiro (Clin Oral Investig, 2011)
TNF-α may be associated with the etiopathogenesis of oral lichen planus (OLP), and it has been suggested that polymorphism of mannose-binding lectin (MBL) increases the in vitro production of TNF- α. The aim of the present study was to assess the relevance of genetic diversity of MBL in OLP. The study sample comprised 90 individuals, 45 OLP patients and 45 healthy volunteers. MBL-2 gene was amplified using real-time PCR. Frequency of A/A genotype was 55.6% in OLP and 53.3% in healthy volunteers. Likewise, A/0 heterozygote genotype was found in 42.2% and 35.6%; 2.2% and 11.1%, had the recessive 0/0 genotype respectively. Frequencies of the "A" and "0" alleles were 77% and 23% in the OLP group and 71.2% in control group. There were no statistically significant differences regarding genotype frequency (p = 0.546) or allele frequency (p = 0.497). In conclusion, no significant association was found between polymorphism of MBL-2 gene and OLP.
Keywords: Adolescent; Adult; Aged; Female; Gene Expression Regulation; Gene Frequency; Genes, Recessive; Genetic Variation; Genotype; Heterozygote; Homozygote; Humans; Lichen Planus, Oral; Male; Mannose-Binding Lectin; Middle Aged; Mutation; Polymorphism, Genetic; Real-Time Polymerase Chain Reaction; Tumor Necrosis Factor-alpha; Young Adult

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, Daniele; Arzuffi, Paola; Zordan, Mauro; Da Re, Caterina; Lamperti, Costanza; Benna, Clara; d'Adamo, Pio; Diodato, Daria; Costa, Rodolfo; Mariotti, Caterina; Uziel, Graziella; Smiderle, Cristina; et al. (Nat Genet, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.
Keywords: Adult; Animals; Brain; Codon, Nonsense; Drosophila melanogaster; Electron Transport Complex III; Female; Gene Knockdown Techniques; Humans; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Nervous System Diseases

Paediatric Behçet's disease presenting with recurrent papillitis and episcleritis: a case report. - Parentin, Fulvio; Lepore, Loredana; Rabach, Ingrid; Pensiero, Stefano (J Med Case Rep, 2011)
INTRODUCTION: Behçet's disease is a chronic multisystem vasculitis characterized by mucocutaneous, articular, neurological, gastrointestinal and ophthalmological lesions. Ocular involvement is mainly represented by recurrent uveitis, especially posterior uveitis; however, iridocyclitis, retinal and choroidal vasculitis, optic neuritis and retinal vascular occlusion can also occur. CASE PRESENTATION: A 12-year-old Caucasian boy with a history of recurrent buccal aphthosis and nonspecific gastrointestinal symptoms was admitted to our hospital with blurred vision associated with acute episcleritis and papillitis. The patient's pathergy test was positive, suggesting a diagnosis of Behçet's disease. Corticosteroid and cyclosporine therapy was started, but further episodes were noted in both eyes. The patient was then switched to intravenous infliximab, with complete resolution of the inflammation after the second infusion. CONCLUSION: Episcleritis and papillitis should be added to the list of uncommon manifestations of pediatric Behçet's disease. Infliximab is an effective, new therapeutic approach for Behçet's disease that is refractory to the conventional corticosteroid and immunosuppressive therapy.

A Phase II study on the safety and efficacy of a single dose of pegfilgrastim for mobilization and transplantation of autologous hematopoietic stem cells in pediatric oncohematology patients. - Cesaro, Simone; Zanazzo, Andrea Giulio; Frenos, Stefano; Luksch, Roberto; Pegoraro, Anna; Tridello, Gloria; Dallorso, Sandro (Transfusion, 2011)
BACKGROUND: Limited data are available on the use of pegfilgrastim in pediatric patients as a mobilizing agent in association with chemotherapy. STUDY DESIGN AND METHODS: This was a prospective, multicenter, Phase II study to evaluate the safety and efficacy of a single dose of 100 µg/kg pegfilgrastim in mobilizing peripheral blood stem cells (PBSCs) in pediatric patients. The primary endpoint of the study was the percentage of good mobilizers with pegfilgrastim (blood peak of CD34+ cells ≥ 20 × 10(6) /L). The results were compared with a historical control group. RESULTS: Thirty of 36 recruited patients were classified as good mobilizers (83%). The median value of circulating CD34+ at leukapheresis was 143 × 10(6) /L (range, 20 × 10(6) -1988 × 10(6) /L). No significant adverse effects were associated with the use of pegfilgrastim and no patient was withdrawn from using the drug. A blood peak of 20 × 10(6) /L or more CD34+ was observed in 33 of 36 control patients (92%) and the median CD34+ count at leukapheresis was 158 × 10(6) /kg (range, 28 × 10(6) -4529 × 10(6) /kg; p = 0.7). No significant differences were found between the two groups in terms of toxicity or other variables of mobilization. As at October 2008, 23 patients of the pegfilgrastim group and 32 patients of the filgrastim group underwent autologous transplant. No significant differences were found in terms of early toxicity, myeloid recovery, and Day 100 survival. CONCLUSION: A single dose of 100 µg/kg pegfilgrastim was safe and effective for PBSC collection in pediatric patients. We suggest that these results support the use of pegfilgrastim for pediatric patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Granulocyte Colony-Stimulating Factor; Hematopoietic Stem Cell Mobilization; Humans; Infant; Male; Neoplasms; Peripheral Blood Stem Cell Transplantation; Prospective Studies; Recombinant Proteins; Transplantation, Autologous

Phospholipase C-β3 is a key modulator of IL-8 expression in cystic fibrosis bronchial epithelial cells. - Bezzerri, Valentino; d'Adamo, Pio; Rimessi, Alessandro; Lanzara, Carmen; Crovella, Sergio; Nicolis, Elena; Tamanini, Anna; Athanasakis, Emmanouil; Tebon, Maela; Bisoffi, Giulia; Drumm, Mitchell L; Knowles, Michael R; et al. (J Immunol, 2011)
Respiratory insufficiency is the major cause of morbidity and mortality in patients affected by cystic fibrosis (CF). An excessive neutrophilic inflammation, mainly orchestrated by the release of IL-8 from bronchial epithelial cells and amplified by chronic bacterial infection with Pseudomonas aeruginosa, leads to progressive tissue destruction. The anti-inflammatory drugs presently used in CF patients have several limitations, indicating the need for identifying novel molecular targets. To address this issue, we preliminarily studied the association of 721 single nucleotide polymorphisms from 135 genes potentially involved in signal transduction implicated in neutrophil recruitment in a cohort of F508del homozygous CF patients with either severe or mild progression of lung disease. The top ranking association was found for a nonsynonymous polymorphism of the phospholipase C-β3 (PLCB3) gene. Studies in bronchial epithelial cells exposed to P. aeruginosa revealed that PLCB3 is implicated in extracellular nucleotide-dependent intracellular calcium signaling, leading to activation of the protein kinase Cα and Cβ and of the nuclear transcription factor NF-κB p65. The proinflammatory pathway regulated by PLCB3 acts by potentiating the Toll-like Receptors' signaling cascade and represents an interesting molecular target to attenuate the excessive recruitment of neutrophils without completely abolishing the inflammatory response.
Keywords: Adenosine Triphosphate; Calcium; Cell Line, Transformed; Cystic Fibrosis; Enzyme Activation; Epithelial Cells; Gene Expression; Gene Frequency; Genotype; Green Fluorescent Proteins; Host-Pathogen Interactions; Humans; Interleukin-8; Isoenzymes; Lung Diseases; Microscopy, Fluorescence; Phospholipase C beta; Polymorphism, Single Nucleotide; Protein Kinase C; Protein Kinase C beta; Pseudomonas aeruginosa; RNA Interference; Toll-Like Receptors; Transcription Factor RelA

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

Prevalence of anaemia in children with thromboembolism in IBD. - Bramuzzo, Matteo; Lazzerini, Marzia (Arch Dis Child, 2011)
Keywords: Anemia, Iron-Deficiency; Female; Humans; Male; Stroke

Refractory iron-deficiency anaemia in a child with portal cavernoma. - Pastore, Serena; Londero, Margherita; Cont, Gabriele; Di Leo, Grazia; Ventura, Alessandro (Gut, 2011)
Keywords: Anemia, Iron-Deficiency; Antihypertensive Agents; Child; Hemangioma, Cavernous; Humans; Hypertension, Portal; Ileal Diseases; Male; Propranolol; Vascular Neoplasms

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

The role of mannose-binding lectin gene polymorphisms in susceptibility to HIV-1 infection in Southern Brazilian patients. - da Silva, Gabriela Kniphoff; Guimarães, Rafael; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Brandão, Lucas; Crovella, Sergio; Chies, José Artur Bogo (AIDS, 2011)
OBJECTIVE: This study investigates the role of mannose-binding lectin (MBL) in the susceptibility to HIV-1 infection analyzing polymorphisms located at the MBL2 promoter and exon 1 regions. MATERIALS AND METHODS: The prevalence of MBL2 variant alleles was investigated in 410 HIV-1-infected patients from the South Brazilian HIV cohort and in 345 unexposed uninfected healthy individuals. The promoter variants were genotyped using polymerase chain reaction with sequence-specific primers (PCR-SSP) and exon 1 variants were analyzed by real-time PCR using a melting temperature assay and were confirmed by PCR-restriction fragment length polymorphism (RFLP). MBL2 genotypic and allelic frequencies were compared between HIV-1-infected patients and controls using the chi-squared tests. RESULTS: The analyses were performed subdividing the individuals according to their ethnic origin. Among Euro-derived individuals a higher frequency of the LX/LX genotype was observed in patients when compared to controls (P < 0.001). The haplotypic analysis also showed a higher frequency of the haplotypes associated with lower MBL levels among HIV-1-infected patients (P = 0.0001). Among Afro-derived individuals the frequencies of LY/LY and HY/HY genotypes were higher in patients when compared to controls (P = 0.009 and P = 0.02). CONCLUSIONS: An increased frequency of MBL2 genotypes associated with low MBL levels was observed in Euro-derived patients, suggesting a potential role for MBL in the susceptibility to HIV-1 infection in Euro-derived individuals.
Keywords: Adult; Aged; Brazil; Female; Genetic Predisposition to Disease; HIV Infections; HIV-1; Humans; Lectins, C-Type; Male; Mannose-Binding Lectin; Mannose-Binding Lectins; Middle Aged; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Cell Surface; Young Adult

A singular case of congenital self-healing histiocytosis with skin, liver and atypical eye involvement. - Parentin, Fulvio; Ventura, Giovanna; Pastore, Serena; Kiren, Valentina; Bibalo, Chiara; Pensiero, Stefano; Lepore, Loredana (Ocul Immunol Inflamm, 2011)
PURPOSE: To describe a rare case of congenital self-healing Langerhans cell histiocytosis (CSHLCH) presenting with atypical eye involvement. DESIGN: Case report. METHODS: A female newborn presented with purpuric lesions over the trunk, limbs, and face. Liver ultrasonography revealed hypoechogenic lesions with blurred borders. Biomicroscopy showed right posterior synechiae with fibrinoid deposits on the lens. At 7 months she presented with right acute glaucoma. RESULTS: Biomicroscopy showed the presence of inflammatory pseudo-membrane covering the anterior surface of the lens, iris, and iridocorneal angle. Ab externo trabeculotomy was performed; access to the anterior chamber with capsulorrhexis forceps permitted a peeling of the pseudo-membrane with normalization of the intraocular pressure. Histologic examination of the membrane revealed an inflammatory tissue with CD1a and S-100 positive histiocytic cells. CONCLUSIONS: This is the first case of CSHLCH describing acute glaucoma secondary to a pseudo-inflammatory membrane with typical histiocytic cells, occluding the iridocorneal angle.
Keywords: Antigens, CD1; Convalescence; Female; Glaucoma; Histiocytosis, Langerhans-Cell; Humans; Infant; Intraocular Pressure; Iridocorneal Endothelial Syndrome; Liver Diseases; S100 Proteins; Skin Diseases; Trabeculectomy

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Thromboembolism in pediatric inflammatory bowel disease: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Maschio, Massimo; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2011)
BACKGROUND: Several studies suggest an increased risk of venous and arterial thromboembolism (TE) in adults with inflammatory bowel disease (IBD) compared to the general population. We performed a systematic review of studies on incidence and characteristic of TE in children with IBD. METHODS: We searched Medline, LILACS, EMBASE, POPLINE, CINHAL, and reference lists of identified articles, without language restrictions, in August 2010. RESULTS: Population studies suggest that there is an increased risk of TE in children with IBD compared to controls. TE occurred in children with IBD in all age ranges, mostly (82.8%) during active disease, and more frequently in children with ulcerative colitis (odds ratio [OR] 3.7, 95% confidence interval [CI] 1.8-7.6). At least one specific risk factor for TE was recognized in 50% of cases; two risk factors were present in 24%. Out of 92 published cases of TE in children with IBD, 54.3% occurred in cerebral site, 26% in the limbs, 13% in the abdominal vessels, and the remaining in the retina and lungs. After a first episode of TE, an early recurrence was observed in 11.4% of children, a late recurrence in 10%. A number of different therapeutic schemes were used. Overall mortality was 5.7% and was mostly associated with cerebral TE. CONCLUSIONS: Population studies are needed to clarify the risk of TE in children with IBD, the relative weight of other risk factors, the characteristics of the events, and to define guidelines of therapy and prophylaxis.
Keywords: Adult; Child; Humans; Inflammatory Bowel Diseases; Risk Factors; Thromboembolism

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

X-ray fluorescence elemental mapping and microscopy to follow hepatic disposition of a Gd-based magnetic resonance imaging contrast agent. - Delfino, Riccarda; Altissimo, Matteo; Menk, Ralf Hendrik; Alberti, Roberto; Klatka, Tomasz; Frizzi, Tommaso; Longoni, Antonio; Salomè, Murielle; Tromba, Giuliana; Arfelli, Fulvia; Clai, Milan; Vaccari, Lisa; et al. (Clin Exp Pharmacol Physiol, 2011)
1. Spatially resolved X-ray fluorescence (XRF) spectroscopy with synchrotron radiation is a technique that allows imaging and quantification of chemical elements in biological specimens with high sensitivity. In the present study, we applied XRF techniques at a macro and micro level to carry out drug distribution studies on ex vivo models to confirm the hepatobiliary disposition of the Gd-based magnetic resonance imaging contrast agent B22956/1. 2. Gd presence was selectively quantified allowing the determination of the time dependent disappearance of the drug from blood and its hepatic accumulation in mice after administration. Elemental mapping highlighted the drug distribution differences between healthy and diseased livers. XRF microanalyses showed that in CCl(4) -induced hepatitis, B22956/1 has greatly reduced hepatic accumulation, shown as a 20-fold reduction of Gd presence. Furthermore, a significant increase of Fe presence was found in steatotic compared with healthy livers, in line with the disease features. 3. The present results show that XRF might be useful in preclinical pharmacological studies with drugs containing exogenous elements. Furthermore, quantitative and high-sensitivity elemental mapping allows simultaneous detection of chemical variation, showing pathological conditions. This approach was useful in suggesting reduced B22956/1 accumulation in steatotic livers, thus opening possible new diagnostic perspectives for this drug.
Keywords: Animals; Contrast Media; Fatty Liver; Female; Gadolinium; Hepatitis; Iron; Liver; Magnetic Resonance Imaging; Mice; Mice, Inbred CBA; Organometallic Compounds; Spectrometry, X-Ray Emission

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

A case of lymphedema-distichiasis syndrome carrying a new de novo frameshift FOXC2 mutation. - Fabretto, Antonella; Shardlow, Alison; Faletra, Flavio; Lepore, Loredana; Hladnik, Uros; Gasparini, Paolo (Ophthalmic Genet, 2010)
PURPOSE: Lymphedema-Distichiasis (LD, OMIM 153400) is an autosomal dominant disorder with variable expression. The mutated gene implicated is FOXC2, which encodes for a forkhead transcription factor involved in the development of the lymphatic and vascular system. LD is characterized by late childhood or pubertal onset lymphedema of the limbs and distichiasis. Other associations have been reported, including congenital heart disease, ptosis, scoliosis. CONCLUSIONS: Here we describe a case of LD carrying a de novo frameshift mutation of FOXC2 who presented a prepubertal onset of lower limbs lymphedema and mild distichiasis associated with other anomalies such as webbing neck and ptosis.
Keywords: Abnormalities, Multiple; Adolescent; Eye Abnormalities; Eyelashes; Face; Forkhead Transcription Factors; Frameshift Mutation; Humans; Lymphedema; Male; Syndrome

A child with pain after mild trauma. - Londero, Margherita; Pastore, Serena; Zanazzo, Giulio A; Bruno, Irene; Ventura, Alessandro (J Pediatr, 2010)
Keywords: Antigens, CD; Antigens, CD31; Antigens, CD34; Antigens, Differentiation, Myelomonocytic; Biopsy; Child; Factor VIII; Fingers; Hand Injuries; Hemangioendothelioma; Humans; Immunohistochemistry; Injury Severity Score; Male; Osteolysis; Pain; Pain Measurement; S100 Proteins; Vascular Neoplasms

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome

Incidence of bacteremias and invasive mycoses in children with acute non-lymphoblastic leukemia: results from a multi-center Italian study. - Castagnola, Elio; Rossi, Mario R; Cesaro, Simone; Livadiotti, Susanna; Giacchino, Mareva; Zanazzo, Giulio; Fioredda, Francesca; Beretta, Chiara; Ciocchello, Francesca; Carli, Modesto; Putti, Maria Caterina; Pansini, Valeria; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: Data on the epidemiology of bacteremias and invasive fungal diseases (IFD) in children with acute myeloid leukemia (AML) are scarce. DESIGN AND METHODS: In a multi-center, retrospective study, we analyzed proportion, rate per 1,000 person-days at risk, and cumulative risk of bacteremias and IFD in children with AML. RESULTS: Between January 1998 and December 2005, 240 children were treated for AML at 8 Italian Centers, for a total of 521 treatment courses and 63,232 person-days at risk. Bacteremia was observed in 32% of treatment courses and IFD was seen in 10% (P < 0.0001), with rates of 2.62 and 0.84, respectively (P < 0.001). There was a significantly higher frequency of IFD during relapse treatment: proportion 15% versus 9% (P = 0.05), rate 2.10 versus 0.64 (P = 0.008) and cumulative risk 32% versus 12% (P = 0.007), while there were no differences in the proportion, rate and cumulative risk of bacteremia during front-line or relapse treatment. The epidemiology of bacteremias and IFD was different during front-line therapy for M3 as compared to other types of AML, but the differences were not statistically significant. CONCLUSIONS: Severe infectious complications are frequent during the treatment of pediatric AML, especially during relapse treatment, and bacteremias are more frequent than IFD.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bacteremia; Child; Female; Follow-Up Studies; Humans; Incidence; Italy; Leukemia, Myeloid, Acute; Male; Mycoses; Neoplasm Recurrence, Local; Retrospective Studies

Individual differences in prefrontal cortex activity during perception of bitter taste using fNIRS methodology. - Bembich, Stefano; Lanzara, Carmela; Clarici, Andrea; Demarini, Sergio; Tepper, Beverly J; Gasparini, Paolo; Grasso, Domenico L (Chem Senses, 2010)
Although bitter taste has a crucial role in nutrition by preventing the ingestion of toxic foods, there are few studies on bitter taste neuroimaging. To identify cortical areas involved in bitter taste perception and to determine if individual differences in taste sensitivity to 6-n-propylthiouracil (PROP) are represented in the brain by different cortical activation patterns, we examined 48 healthy volunteers using functional near-infrared spectroscopy. Participants rated the perceived intensity of filter paper disks impregnated with PROP and NaCl during the imaging procedure and were then classified as PROP tasters and nontasters. We monitored cortical activity in both the anterior and posterior regions of the dorsolateral prefrontal cortex (DLPFC) and in the ventrolateral prefrontal cortex (VLPFC). No activity was detected in the anterior DLPFC in any of the participants. However, during the administration of PROP, significant cortical activation was detected in the more posterior regions of the left DLPFC and in the left and right VLPFC but only in PROP tasters. PROP nontasters showed no cortical activity in these areas. These data suggest that the prefrontal cortex is involved in the conscious perception of the bitter taste of PROP and that the pattern of activity is consistent with individual differences in the ability to taste this compound. Thus, the PROP phenotype is associated with fundamental differences in cortical taste processing.
Keywords: Adult; Eating; Female; Food Preferences; Humans; Individuality; Male; Perception; Phenotype; Prefrontal Cortex; Propylthiouracil; Sodium Chloride; Spectroscopy, Near-Infrared; Taste; Taste Threshold; Young Adult

Insights into the binding of Phenyltiocarbamide (PTC) agonist to its target human TAS2R38 bitter receptor. - Biarnés, Xevi; Marchiori, Alessandro; Giorgetti, Alejandro; Lanzara, Carmela; Gasparini, Paolo; Carloni, Paolo; Born, Stephan; Brockhoff, Anne; Behrens, Maik; Meyerhof, Wolfgang (PLoS One, 2010)
Humans' bitter taste perception is mediated by the hTAS2R subfamily of the G protein-coupled membrane receptors (GPCRs). Structural information on these receptors is currently limited. Here we identify residues involved in the binding of phenylthiocarbamide (PTC) and in receptor activation in one of the most widely studied hTAS2Rs (hTAS2R38) by means of structural bioinformatics and molecular docking. The predictions are validated by site-directed mutagenesis experiments that involve specific residues located in the putative binding site and trans-membrane (TM) helices 6 and 7 putatively involved in receptor activation. Based on our measurements, we suggest that (i) residue N103 participates actively in PTC binding, in line with previous computational studies. (ii) W99, M100 and S259 contribute to define the size and shape of the binding cavity. (iii) W99 and M100, along with F255 and V296, play a key role for receptor activation, providing insights on bitter taste receptor activation not emerging from the previously reported computational models.
Keywords: Amino Acid Sequence; Calcium; Cell Line; Computational Biology; Dose-Response Relationship, Drug; Humans; Intracellular Space; Ligands; Models, Molecular; Molecular Sequence Data; Mutagenesis, Site-Directed; Phenylthiourea; Protein Binding; Protein Structure, Secondary; Receptors, G-Protein-Coupled

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Morbidity of pandemic H1N1 influenza in children with cancer. - Caselli, Désirée; Carraro, Francesca; Castagnola, Elio; Ziino, Ottavio; Frenos, Stefano; Milano, Giuseppe Maria; Livadiotti, Susanna; Cesaro, Simone; Marra, Nicoletta; Zanazzo, Giulio; Meazza, Cristina; Cellini, Monica; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: To define the mortality and the current impact of the H1N1 pandemic in pediatric hematology-oncology centers, we performed a specific survey. PROCEDURE: Pharyngeal swabs from patients with fevers of unknown origin, flu-like symptoms or bronchopneumonia were screened for H1N1 using PCR. RESULTS: Sixty-two patients with documented H1N1 infection were reported: 16 had recently stopped therapy, 2 were at the diagnosis stage, and 44 were receiving therapy. The clinical course was severe (requiring ICU admission) in only 1 patient, moderate (requiring hospital admission) in 38, and mild in the remaining 23 (37%), treated as outpatients. While none of the patients died of H1N1-related complications, two patients died of progressive cancer; in all of the remaining cases, symptoms resolved within 11 days. The clinical course was complicated by respiratory distress or bronchopneumonia in 10 cases. Oseltamivir was given to 82% of patients. Chemotherapy was temporarily withdrawn in 54% of cases for a median time of 21 days (range, 4-43 days). CONCLUSION: H1N1 infection in children with cancer was not reported as the cause of death in any case but resulted in reduced intensity of anti-cancer therapy.
Keywords: Adolescent; Antineoplastic Agents; Cause of Death; Child; Child, Preschool; Data Collection; Disease Outbreaks; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Leukemia; Lymphoma, Non-Hodgkin; Morbidity; Neoplasms; Treatment Outcome; Young Adult

Multidrug resistant Pseudomonas aeruginosa infection in children undergoing chemotherapy and hematopoietic stem cell transplantation. - Caselli, Désirée; Cesaro, Simone; Ziino, Ottavio; Zanazzo, Giulio; Manicone, Rosaria; Livadiotti, Susanna; Cellini, Monica; Frenos, Stefano; Milano, Giuseppe M; Cappelli, Barbara; Licciardello, Maria; Beretta, Chiara; et al. (Haematologica, 2010)
Pseudomonas aeruginosa is one leading gram-negative organism associated with nosocomial infections. Bacteremia is life-threatening in the immunocompromised host. Increasing frequency of multi-drug-resistant (MDRPA) strains is concerning. We started a retrospective survey in the pediatric hematology oncology Italian network. Between 2000 and 2008, 127 patients with Pseudomonas aeruginosa bacteremia were reported from 12 centers; 31.4% of isolates were MDRPA. Death within 30 days of a positive blood culture occurred in 19.6% (25/127) of total patients; in patients with MDRPA infection it occurred in 35.8% (14/39). In the multivariate analysis, only MDRPA had significant association with infection-related death. This is the largest series of Pseudomonas aeruginosa bacteremia cases from pediatric hematology oncology centers. Monitoring local bacterial isolates epidemiology is mandatory and will allow empiric antibiotic therapy to be tailored to reduce fatalities.
Keywords: Adolescent; Antineoplastic Agents; Bacteremia; Child; Child, Preschool; Drug Resistance, Multiple; Female; Hematopoietic Stem Cell Transplantation; Humans; Immunocompromised Host; Infant; Infant, Newborn; Italy; Male; Pseudomonas aeruginosa; Pseudomonas Infections; Retrospective Studies; Young Adult

Prepregnancy BMI influences maternal and fetal outcomes in women with isolated gestational hyperglycaemia: a multicentre study. - Lapolla, A; Bonomo, M; Dalfrà, M G; Parretti, E; Mannino, D; Mello, G; Di Cianni, G (Diabetes Metab, 2010)
AIM: This multicentre study analyzed the maternal and fetal outcomes of women who had one elevated 3-h oral glucose tolerance test (isolated gestational hyperglycaemia [IGH]). METHODS: From 1999 to 2003, data were collected for 606 IGH women from 31 Italian obstetric or diabetic centres, including time and mode of delivery, gestational hypertension, preeclampsia, eclampsia, congenital malformations, and neonatal mortality and morbidity, to compare them with the general pregnant Italian population. A prognostic model for the outcome of pregnancy was constructed, and the concurrence of certain specified conditions was considered a positive outcome, whereas pregnancies that failed to meet one or more of the stated conditions were classified as "complicated". RESULTS: Macrosomia was significantly more frequent in women with IGH than in the normal pregnant population (10.7 vs 7.4%, respectively; P=0.003). Stillbirth and neonatal mortality rates did not differ from those in normal pregnancies, while a slight rise in the frequency of major malformations was not statistically significant (1.48 vs 0.89%, respectively; P<0.11). Multivariate logistic analyses confirmed that the prepregnancy body mass index (BMI) was an independent predictor of a complicated pregnancy. As for fetal growth, multivariate logistic analyses according to BMI showed that being overweight or obese were strong predictors of macrosomia. CONCLUSION: These findings in a large cohort of Italian women with IGH confirm the detrimental effect of even minimally altered glucose tolerance on fetal outcome. Also, prepregnancy obesity plays an important role in raising the risk of adverse perinatal outcomes in such patients.
Keywords: Adult; Blood Glucose; Body Mass Index; Female; Fetal Macrosomia; Glucose Tolerance Test; Humans; Hyperglycemia; Italy; Models, Statistical; Obesity; Pregnancy; Pregnancy Complications; Pregnancy Outcome; Prognosis; Retrospective Studies; Risk Factors; Time Factors

Screening for GJB2 and GJB6 gene mutations in patients from Campania region with sensorineural hearing loss. - Chinetti, Viviana; Iossa, Sandra; Auletta, Gennaro; Laria, Carla; De Luca, Maria; Di Leva, Francesca; Riccardi, Pasquale; Giannini, Pasquale; Gasparini, Paolo; Ciccodicola, Alfredo; Marciano, Elio; Franzè, Annamaria (Int J Audiol, 2010)
The aim of this study was to screen 349 patients affected by sensorineural hearing loss (SNHL), mostly from the Campania region (southern Italy), for GJB2 gene mutations and for two deletions of the GJB6 gene (del GJB6 -D13S1830 and del GJB6 -D13S1854). We identified pathogenetic GJB2 mutations in 51 cases (15% of patients). No GJB6 mutation was found. We also examined the audiologic features of the patients for whom we had an etiologic diagnosis, in order to identify correlations between the severity of hearing loss and the type of mutation.
Keywords: Acoustic Stimulation; Adolescent; Adult; Audiometry; Auditory Perception; Child; Child, Preschool; Connexins; Genetic Predisposition to Disease; Genetic Testing; Hearing Loss, Sensorineural; Heterozygote; Homozygote; Humans; Italy; Mass Screening; Middle Aged; Mutation; Phenotype; Risk Factors; Severity of Illness Index; Young Adult

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Breastfeed Rev, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low-income settings, the original KMC modelis implemented. This consists of continuous (24 h/day; 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding and, adequate follow up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC modelin all types of settings was discussed at the 7th International Workshop on KMC Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents'role, modification of the NICU environment, performance of care in KMC, and KMCin case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Acta Paediatr, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low income settings, the original KMC model is implemented. This consists of continuous (24 h/day, 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding; and, adequate follow-up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC model in all types of settings was discussed at the 7th International Workshop on KMC. Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents' role, modification of the NICU environment, performance of care in KMC, and KMC in case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.
Keywords: Attitude of Health Personnel; Female; Humans; Infant Care; Infant, Newborn; Intensive Care Units, Neonatal; Male; Parent-Child Relations; Practice Guidelines as Topic; Professional-Patient Relations; Role; Skin; Visitors to Patients

[Strategies for cardiovascular prevention in children]. - Spinelli, Angela; Nardone, Paola; Lamberti, Anna; Baglio, Giovanni (G Ital Cardiol (Rome), 2010)
Keywords: Body Mass Index; Cardiovascular Diseases; Child; Diet, Mediterranean; Food Habits; Humans; Life Style; Motor Activity; Obesity; Overweight; Patient Education as Topic; Population Surveillance; Questionnaires; Risk Factors

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Toward a consensus on guiding principles for health systems strengthening. - Swanson, Robert C; Bongiovanni, Annette; Bradley, Elizabeth; Murugan, Varnee; Sundewall, Jesper; Betigeri, Arvind; Nyonator, Frank; Cattaneo, Adriano; Harless, Brandi; Ostrovsky, Andrey; Labonté, Ronald (PLoS Med, 2010)
Keywords: Global Health; Humans; Public Health

Towards universal Kangaroo Mother Care: recommendations and report from the First European conference and Seventh International Workshop on Kangaroo Mother Care. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ibe, O; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Ruiz Peláez, J G; et al. (Acta Paediatr, 2010)
UNLABELLED: The hallmark of Kangaroo Mother Care (KMC) is the kangaroo position: the infant is cared for skin-to-skin vertically between the mother's breasts and below her clothes, 24 h/day, with father/substitute(s) participating as KMC providers. Intermittent KMC (for short periods once or a few times per day, for a variable number of days) is commonly employed in high-tech neonatal intensive care units. These two modalities should be regarded as a progressive adaptation of the mother-infant dyad, ideally towards continuous KMC, starting gradually and progressively with intermittent KMC. The other components in KMC are exclusive breastfeeding (ideally) and early discharge in kangaroo position with strict follow-up. Current evidence allows the following general statements about KMC in affluent and low-income settings: KMC enhances bonding and attachment; reduces maternal postpartum depression symptoms; enhances infant physiologic stability and reduces pain, increases parental sensitivity to infant cues; contributes to the establishment and longer duration of breastfeeding and has positive effects on infant development and infant/parent interaction. Therefore, intrapartum and postnatal care in all types of settings should adhere to a paradigm of nonseparation of infants and their mothers/families. Preterm/low-birth-weight infants should be regarded as extero-gestational foetuses needing skin-to-skin contact to promote maturation. CONCLUSION: Kangaroo Mother Care should begin as soon as possible after birth, be applied as continuous skin-to-skin contact to the extent that this is possible and appropriate and continue for as long as appropriate.
Keywords: Congresses as Topic; Female; Global Health; Humans; Infant Care; Infant, Newborn; Male; Parent-Child Relations; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Skin

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult